Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2021)
A dataset containing 262344677 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is one of (Aaptosyax grypus Rainboth, 1991, Abalistes stellatus (Anonymous, 1798), Abalistes stellatus (Anonymous, 1798), Abavorana luctuosa (Peters, 1871), Abbottina rivularis (Basilewsky, 1855), Ablabys taenianotus (Cuvier, 1829), Ablennes hians (Valenciennes, 1846), Aborichthys elongatus Hora, 1921, Abramis brama (Linnaeus, 1758), Abramites eques (Steindachner, 1878), Abramites hypselonotus (Günther, 1868), Abronia bogerti Tihen, 1954, Abronia deppii (Wiegmann, 1828), Abronia graminea (Cope, 1864), Abronia lythrochila Smith & Alvarez Del Toro, 1963, Abronia mixteca Bogert & Porter, 1967, Abronia oaxacae (Günther, 1885), Abronia taeniata (Wiegmann, 1828), Abudefduf saxatilis (Linnaeus, 1758), Acantharchus pomotis (Baird, 1855), Acanthemblemaria crockeri Beebe & Tee-Van, 1938, Acanthemblemaria hancocki Myers & Reid, 1936, Acanthemblemaria macrospilus Brock, 1940, Acanthicus adonis Isbrücker & Nijssen, 1988, Acanthicus hystrix Spix & Agassiz, 1829, Acanthobrama centisquama Heckel, 1843, Acanthobrama hadiyahensis Coad, Alkahem & Behnke, 1983, Acanthobrama lissneri Tortonese, 1952, Acanthobrama marmid Heckel, 1843, Acanthobrama telavivensis Goren, Fishelson & Trewavas, 1973, Acanthobrama terraesanctae Steinitz, 1952, Acanthobunocephalus nicoi Friel, 1995, Acanthocepola indica (Day, 1888), Acanthocercus atricollis (Smith, 1849), Acanthocharax microlepis Eigenmann, 1912, Acanthochelys macrocephala (Rhodin, Mittermeier & Mcmorris, 1984), Acanthochelys pallidipectoris (Freiberg, 1945), Acanthochelys spixii (Duméril & Bibron, 1835), Acanthochromis polyacanthus (Bleeker, 1855), Acanthocleithron chapini Nichols & Griscom, 1917, Acanthocobitis botia (Hamilton, 1822), Acanthocobitis rubidipinnis (Blyth, 1860), Acanthocobitis urophthalmus (Günther, 1868), Acanthocobitis zonalternans (Blyth, 1860), Acanthodoras cataphractus (Linnaeus, 1758), Acanthodoras spinosissimus (Eigenmann & Eigenmann, 1888), Acanthophis antarcticus (Shaw, 1802), Acanthophis rugosus Loveridge, 1948, Acanthopsoides delphax Siebert, 1991, Acanthopsoides gracilentus (Smith, 1945), Acanthopsoides gracilis Fowler, 1934, Acanthopsoides hapalias Siebert, 1991, Acanthopsoides molobrion Siebert, 1991, Acanthopsoides robertsi Siebert, 1991, Acanthosaura armata Boulenger, 1885, Acanthosaura capra Günther, 1861, Acanthosaura crucigera Daltry & Chenag, 2000, Acanthosaura lepidogaster (Cuvier, 1829), Acanthostracion quadricornis (Linnaeus, 1758), Acanthurus achilles Shaw, 1803, Acanthurus auranticavus Randall, 1956, Acanthurus bahianus Castelnau, 1855, Acanthurus bariene Lesson, 1831, Acanthurus blochii Valenciennes, 1835, Acanthurus chirurgus (Bloch, 1787), Acanthurus chronixis Randall, 1960, Acanthurus coeruleus Bloch & Schneider, 1801, Acanthurus dussumieri Valenciennes, 1835, Acanthurus fowleri de Beaufort, 1951, Acanthurus guttatus Forster, 1801, Acanthurus japonicus (Schmidt, 1931), Acanthurus leucocheilus Herre, 1927, Acanthurus leucopareius (Jenkins, 1903), Acanthurus leucosternon Bennett, 1833, Acanthurus lineatus (Linnaeus, 1758), Acanthurus maculiceps (Ahl, 1923), Acanthurus mata (Cuvier, 1829), Acanthurus nigricans (Linnaeus, 1758), Acanthurus nigricauda Duncker & Mohr, 1929, Acanthurus nigrofuscus (Forsskål, 1775), Acanthurus nigroris Valenciennes, 1835, Acanthurus olivaceus Bloch & Schneider, 1801, Acanthurus pyroferus Kittlitz, 1834, Acanthurus sohal (Forsskål, 1775), Acanthurus tennentii Günther, 1861, Acanthurus thompsoni (Fowler, 1923), Acanthurus triostegus (Linnaeus, 1758), Acanthurus tristis Tickell, 1888, Acanthurus xanthopterus Valenciennes, 1835, Acantopsis choirorhynchos (Bleeker, 1854), Acantopsis dialuzona Van Hasselt, 1823, Acantopsis thiemmedhi Sontirat, 1999, Acapoeta tanganicae (Boulenger, 1900), Acarichthys heckelii (Müller & Troschel, 1849), Acaronia nassa (Heckel, 1840), Acaronia vultuosa Kullander, 1989, Accipiter albogularis G.R.Gray, 1870, Accipiter butleri (Gurney & Jr., 1898), Accipiter gentilis (Linnaeus, 1758), Accipiter melanoleucus A.Smith, 1830, Accipiter nisus (Linnaeus, 1758), Accipiter princeps Mayr, 1934, Accipiter rufiventris A.Smith, 1830, Acentrogobius chlorostigmatoides (Bleeker, 1849), Acentrogobius viridipunctatus (Valenciennes, 1837), Acentronichthys leptos Eigenmann & Eigenmann, 1889, Acerodon humilis K.Andersen, 1909, Aceros corrugatus (Temminck, 1832), Acestridium dichromum Retzer, Nico & Provenzano, 1999, Acestridium discus Haseman, 1911, Acestridium martini Retzer, Nico & Provenzano, 1999, Acestrocephalus anomalus (Steindachner, 1880), Acestrocephalus boehlkei Menezes, 1977, Acestrocephalus sardina (Fowler, 1913), Acestrorhynchus abbreviatus (Cope, 1878), Acestrorhynchus altus Menezes, 1969, Acestrorhynchus britskii Menezes, 1969, Acestrorhynchus falcatus (Bloch, 1794), Acestrorhynchus falcirostris (Cuvier, 1819), Acestrorhynchus grandoculis Menezes & Géry, 1983, Acestrorhynchus heterolepis (Cope, 1878), Acestrorhynchus isalineae Menezes & Géry, 1983, Acestrorhynchus lacustris (Lütken, 1875), Acestrorhynchus maculipinna Menezes & Géry, 1983, Acestrorhynchus microlepis (Jardine, 1841), Acestrorhynchus minimus Menezes, 1969, Acestrorhynchus nasutus Eigenmann, 1912, Acestrorhynchus pantaneiro Menezes, 1992, Acheilognathus barbatulus Günther, 1873, Acheilognathus cyanostigma Jordan & Fowler, 1903, Acheilognathus deignani (Smith, 1945), Acheilognathus imberbis Günther, 1868, Acheilognathus koreensis Kim & Kim, 1990, Acheilognathus macropterus (Bleeker, 1871), Acheilognathus macropterus (Bleeker, 1871), Acheilognathus majusculus Kim & Yang, 1998, Acheilognathus melanogaster Bleeker, 1860, Acheilognathus microphysa Yang, Chu & Chen, 1990, Acheilognathus peihoensis (Fowler, 1910), Acheilognathus rhombeus (Temminck & Schlegel, 1846), Acheilognathus tabira Jordan & Thompson, 1914, Acheilognathus tonkinensis (Vaillant, 1892), Acheilognathus yamatsutae Mori, 1928, Achirus achirus (Linnaeus, 1758), Achirus lineatus (Linnaeus, 1758), Achirus mazatlanus (Steindachner, 1869), Achirus novoae Cervigón, 1982, Achondrostoma arcasii (Steindachner, 1866), Achondrostoma occidentale (Robalo, Almada, Sousa Santos, Moreira & Doadrio, 2005), Achondrostoma oligolepis (Robalo, Doadrio, Almada & Kottelat, 2005), Achondrostoma salmantinum Doadrio & Elvira, 2007, Acinocheirodon melanogramma Malabarba & Weitzman, 1999, Acinonyx jubatus (Schreber, 1775), Acipenser baerii Brandt, 1869, Acipenser gueldenstaedtii Brandt & Ratzeburg, 1833, Acipenser naccarii Bonaparte, 1836, Acipenser oxyrinchus Mitchill, 1815, Acipenser oxyrinchus Mitchill, 1815, Acipenser ruthenus Linnaeus, 1758, Acipenser sinensis Gray, 1835, Acipenser stellatus Pallas, 1771, Acnodon normani Gosline, 1951, Acnodon oligacanthus (Müller & Troschel, 1844), Acnodon senai Jégu & Santos, 1990, Acomys cahirinus (É.Geoffroy, 1803), Acomys cahirinus (É.Geoffroy, 1803), Acrantophis dumerili Jan, 1860, Acrantophis madagascariensis (Duméril & Bibron, 1844), Acreichthys radiatus (Popta, 1900), Acreichthys tomentosus (Linnaeus, 1758), Acridotheres cristatellus (Linnaeus, 1758), Acridotheres tristis (Linnaeus, 1766), Acris gryllus (LeConte, 1825), Acrobates pygmaeus (Shaw, 1793), Acrocephalus familiaris (Rothschild, 1892), Acrocheilus alutaceus Agassiz & Pickering, 1855, Acrochordonichthys guttatus Ng & Ng, 2001, Acrochordonichthys rugosus (Bleeker, 1846), Acrochordonichthys strigosus Ng & Ng, 2001, Acrochordus granulatus (Schneider, 1799), Acrochordus javanicus Hornstedt, 1787, Acrocodia indica (Desmarest, 1819), Acrossocheilus beijiangensis Wu & Lin, 1977, Acrossocheilus fasciatus (Steindachner, 1892), Acrossocheilus iridescens (Nichols & Pope, 1927), Acrossocheilus iridescens (Nichols & Pope, 1927), Acrossocheilus parallens (Nichols, 1931), Acrossocheilus xamensis Kottelat, 2000, Acrossocheilus yunnanensis (Regan, 1904), Acryllium vulturinum (Hardwicke, 1834), Actinemys marmorata (Baird & Girard, 1852), Actinemys marmorata (Baird & Girard, 1852), Actitis hypoleucos (Linnaeus, 1758), Actophilornis africanus (Gmelin, 1789), Addax nasomaculatus (Blainville, 1816), Adelphobates galactonotus (Steindachner, 1864), Adelphobates galactonotus (Steindachner, 1864), Adelphobates quinquevittatus (Steindachner, 1864), Adelphobates quinquevittatus (Steindachner, 1864), Adinia xenica (Jordan & Gilbert, 1882), Adontosternarchus balaenops (Cope, 1878), Adontosternarchus clarkae Mago-Leccia, Lundberg & Baskin, 1985, Adontosternarchus devenanzii Mago-Leccia, Lundberg & Baskin, 1985, Adontosternarchus sachsi (Peters, 1877), Aegithalos caudatus (Linnaeus, 1758), Aegypius monachus (Linnaeus, 1766), Aeluroscalabotes felinus (Günther, 1864), Aeoliscus strigatus (Günther, 1861), Aepyceros melampus (Lichtenstein, 1812), Aequidens chimantanus Inger, 1956, Aequidens diadema (Heckel, 1840), Aequidens epae Kullander, 1995, Aequidens gerciliae Kullander, 1995, Aequidens hoehnei (Miranda Ribeiro, 1918), Aequidens mauesanus Kullander, 1997, Aequidens metae Eigenmann, 1922, Aequidens michaeli Kullander, 1995, Aequidens pallidus (Heckel, 1840), Aequidens paloemeuensis Kullander & Nijssen, 1989, Aequidens patricki Kullander, 1984, Aequidens plagiozonatus Kullander, 1984, Aequidens potaroensis Eigenmann, 1912, Aequidens rivulatus (Günther, 1860), Aequidens rondoni (Miranda Ribeiro, 1918), Aequidens sapayensis (Regan, 1903), Aequidens tetramerus (Heckel, 1840), Aequidens tubicen Kullander & Ferreira, 1991, Aequidens viridis (Heckel, 1840), Aeronautes saxatalis (Woodhouse, 1853), Aethia cristatella (Pallas, 1769), Aethia psittacula (Pallas, 1769), Aetobatus narinari (Euphrasen, 1790), Afrixalus dorsalis (Peters, 1875), Afrixalus fornasini (Bianconi, 1849), Afrixalus fulvovittatus (Cope, 1861), Afrixalus paradorsalis Perret, 1960, Afroedura africana (Boulenger, 1888), Afropavo congensis Chapin, 1936, Afrotyphlops congestus (Duméril & Bibron, 1844), Agalychnis annae (Duellman, 1963), Agalychnis callidryas (Cope, 1862), Agalychnis dacnicolor (Cope, 1864), Agalychnis lemur (Boulenger, 1882), Agalychnis lemur (Boulenger, 1882), Agalychnis lemur (Boulenger, 1882), Agalychnis moreletii (Duméril, 1853), Agalychnis spurrelli Boulenger, 1913, Agama aculeata Merrem, 1820, Agama agama (Linnaeus, 1758), Agama atra Daudin, 1802, Agama hartmanni Peters, 1869, Agama mwanzae Loveridge, 1923, Agama sankaranica Chabanaud, 1918, Agama spinosa Gray, Agamura persica (Duméril, 1856), Agamyxis albomaculatus (Peters, 1877), Agamyxis pectinifrons (Cope, 1870), Agapornis canus (Gmelin, 1788), Agapornis fischeri Reichenow, 1887, Agapornis lilianae Shelley, 1894, Agapornis nigrigenis W.L.Sclater, 1906, Agapornis personatus Reichenow, 1887, Agapornis pullarius (Linnaeus, 1758), Agapornis roseicollis (Stanley, 1814), Agapornis taranta (Stanley, 1814), Ageneiosus atronasus Eigenmann & Eigenmann, 1888, Ageneiosus brevis Steindachner, 1881, Ageneiosus inermis (Linnaeus, 1766), Ageneiosus magoi Castillo & Brull G., 1989, Ageneiosus marmoratus Eigenmann, 1912, Ageneiosus militaris Valenciennes, 1835, Ageneiosus pardalis Lütken, 1874, Ageneiosus piperatus (Eigenmann, 1912), Ageneiosus polystictus Steindachner, 1915, Ageneiosus rondoni Miranda Ribeiro, 1914, Ageneiosus ucayalensis Castelnau, 1855, Ageneiosus vittatus Steindachner, 1908, Agkistrodon bilineatus Günther, 1863, Agkistrodon contortrix (Linnaeus, 1766), Agkistrodon piscivorus (Lacépède, 1789), Aglaeactis cupripennis (Bourcier, 1843), Aglaiocercus kingii (Hartert, 1898), Agoniates anchovia Eigenmann, 1914, Agoniates halecinus Müller & Troschel, 1845, Agonopsis vulsa (Jordan & Gilbert, 1880), Agonostomus catalai Pellegrin, 1932, Agonostomus monticola (Bancroft, 1834), Agonostomus telfairii Bennett, 1832, Aguarunichthys inpai Zuanon, Rapp Py-Daniel & Jégu, 1993, Aguarunichthys torosus Stewart, 1986, Ahaetulla nasuta (Lacépède, 1789), Ahaetulla prasina (Boie, 1827), Ahaetulla prasina (Boie, 1827), Ailia coila (Hamilton, 1822), Ailuroedus buccoides (Temminck, 1836), Ailuropoda melanoleuca (David, 1869), Ailurops ursinus (Temminck, 1824), Ailurus fulgens F.G.Cuvier, 1825, Aioliops megastigma Rennis & Hoese, 1987, Aipysurus laevis Lacépède, 1804, Aix galericulata (Linnaeus, 1758), Aix sponsa (Linnaeus, 1758), Akysis ephippifer Ng & Kottelat, 1998, Akysis hendricksoni Alfred, 1966, Akysis heterurus Ng, 1996, Akysis maculipinnis Fowler, 1934, Akysis pictus Günther, 1883, Akysis prashadi Hora, 1936, Akysis recavus Ng & Kottelat, 1998, Akysis varius Ng & Kottelat, 1998, Albulichthys albuloides (Bleeker, 1855), Alburnoides bipunctatus (Bloch, 1782), Alburnus albidus (Costa, 1838), Alburnus alburnus (Linnaeus, 1758), Alburnus caeruleus Heckel, 1843, Alburnus chalcoides (Güldenstädt, 1772), Alburnus escherichii Steindachner, 1897, Alburnus filippii Kessler, 1877, Alburnus hohenackeri Kessler, 1877, Alburnus mossulensis Heckel, 1843, Alburnus nasreddini Battalgil, 1943, Alburnus orontis Sauvage, 1882, Alburnus sellal Heckel, 1843, Alburnus tarichi (Güldenstädt, 1814), Alces alces (Linnaeus, 1758), Alcippe morrisonia Swinhoe, 1863, Aldabrachelys gigantea (Schweigger, 1812), Aldabrachelys gigantea (Schweigger, 1812), Aldrichetta forsteri (Valenciennes, 1836), Alectis indicus (Rüppell, 1830), Alectoris chukar (J.E.Gray, 1830), Alectoris philbyi Lowe, 1934, Alestes baremoze (Joannis, 1835), Alestes grandisquamis Boulenger, 1899, Alestopetersius caudalis (Boulenger, 1899), Alestopetersius smykalai Poll, 1967, Alfaro cultratus (Regan, 1908), Alfaro huberi (Fowler, 1923), Algansea aphanea Barbour & Miller, 1978, Algansea avia Barbour & Miller, 1978, Algansea barbata Álvarez & Cortés, 1964, Algansea lacustris Steindachner, 1895, Algansea monticola Barbour & Contreras-Balderas, 1968, Algansea popoche (Jordan & Snyder, 1899), Algansea tincella (Valenciennes, 1844), Alisterus scapularis (Lichtenstein, 1816), Alle alle (Linnaeus, 1758), Allenbatrachus grunniens (Linnaeus, 1758), Allenopithecus nigroviridis (Pocock, 1907), Alligator mississippiensis (Daudin, 1801), Allobates femoralis (Boulenger, 1884), Allobates femoralis (Boulenger, 1884), Allobates zaparo (Silverstone, 1976), Allobates zaparo (Silverstone, 1976), Allochromis welcommei (Greenwood, 1966), Allodontichthys hubbsi Miller & Uyeno, 1980, Allodontichthys polylepis Rauchenberger, 1988, Allodontichthys tamazulae Turner, 1946, Allodontichthys zonistius (Hubbs, 1932), Alloophorus robustus (Bean, 1892), Allophryne ruthveni Gaige, 1926, Allosmerus elongatus (Ayres, 1854), Allotoca catarinae (de Buen, 1942), Allotoca diazi (Meek, 1902), Allotoca dugesii (Bean, 1887), Allotoca goslinei Smith & Miller, 1987, Allotoca maculata Smith & Miller, 1980, Allotoca zacapuensis Meyer, Radda & Domínguez-Domínguez, 2001, Alopochen aegyptiaca (Linnaeus, 1766), Alouatta caraya (Humboldt, 1812), Alticorpus macrocleithrum (Stauffer & McKaye, 1985), Alticorpus mentale Stauffer & McKaye, 1988, Alticorpus peterdaviesi (Burgess & Axelrod, 1973), Alticus arnoldorum (Curtiss, 1938), Alticus saliens (Forster, 1788), Altolamprologus calvus (Poll, 1978), Altolamprologus compressiceps (Boulenger, 1898), Aluterus schoepfii (Walbaum, 1792), Aluterus scriptus (Osbeck, 1765), Alytes muletensis (Sanchíz & Adrover, 1979), Amadina fasciata (Gmelin, 1789), Amandava amandava (Linnaeus, 1758), Amandava subflava (Vieillot, 1819), Amaralia hypsiura (Kner, 1855), Amarginops platus Nichols & Griscom, 1917, Amaurornis olivacea (Meyen, 1834), Amazilia amabilis (Gould, 1853), Amazilia amazilia (R.Lesson & Garnot, 1827), Amazona aestiva (Linnaeus, 1758), Amazona albifrons (Sparrman, 1788), Amazona amazonica (Linnaeus, 1766), Amazona arausiaca (Statius Muller, 1776), Amazona auropalliata (Lesson, 1842), Amazona autumnalis (Linnaeus, 1758), Amazona barbadensis (Gmelin, 1788), Amazona dufresniana (Shaw, 1812), Amazona farinosa (Boddaert, 1783), Amazona festiva (Linnaeus, 1758), Amazona finschi (P.L.Sclater, 1864), Amazona imperialis Richmond, 1899, Amazona leucocephala (Linnaeus, 1758), Amazona ochrocephala (Gmelin, 1788), Amazona oratrix Ridgway, 1887, Amazona pretrei (Temminck, 1830), Amazona ventralis (Statius Muller, 1776), Amazona viridigenalis (Cassin, 1853), Amazona xantholora (G.R.Gray, 1859), Amazona xanthops (Spix, 1824), Amazonetta brasiliensis (Gmelin, 1789), Ambassis agrammus Günther, 1867, Ambassis ambassis (Lacepède, 1802), Amblonyx cinereus (Illiger, 1815), Amblonyx cinereus (Illiger, 1815), Ambloplites ariommus Viosca, 1936, Ambloplites constellatus Cashner & Suttkus, 1977, Amblyceps apangi Nath & Dey, 1989, Amblyceps caecutiens Blyth, 1858, Amblyceps foratum Ng & Kottelat, 2000, Amblyceps laticeps (McClelland, 1842), Amblyceps mangois (Hamilton, 1822), Amblyceps murraystuarti Chaudhuri, 1919, Amblyceps serratum Ng & Kottelat, 2000, Amblyceps variegatum Ng & Kottelat, 2000, Amblycirrhitus bimacula (Jenkins, 1903), Amblycirrhitus pinos (Mowbray, 1927), Amblydoras affinis (Kner, 1855), Amblydoras bolivarensis (Fernández-Yépez, 1968), Amblydoras gonzalezi (Fernández-Yépez, 1968), Amblydoras monitor (Cope, 1872), Amblydoras nauticus (Cope, 1874), Amblyeleotris arcupinna Mohlmann & Munday, 1999, Amblyeleotris aurora (Polunin & Lubbock, 1977), Amblyeleotris callopareia Polunin & Lubbock, 1979, Amblyeleotris diagonalis Polunin & Lubbock, 1979, Amblyeleotris fasciata (Herre, 1953), Amblyeleotris guttata (Fowler, 1938), Amblyeleotris gymnocephala (Bleeker, 1853), Amblyeleotris randalli Hoese & Steene, 1978, Amblyeleotris steinitzi (Klausewitz, 1974), Amblyeleotris sungami (Klausewitz, 1969), Amblyeleotris wheeleri (Polunin & Lubbock, 1977), Amblyeleotris yanoi Aonuma & Yoshino, 1996, Amblyglyphidodon aureus (Cuvier, 1830), Amblyglyphidodon leucogaster (Bleeker, 1847), Amblyglyphidodon melanopterus Allen & Randall, 2002, Amblyglyphidodon ternatensis (Bleeker, 1853), Amblygobius bynoensis (Richardson, 1844), Amblygobius decussatus (Bleeker, 1855), Amblygobius hectori (Smith, 1957), Amblygobius phalaena (Valenciennes, 1837), Amblygobius sphynx (Valenciennes, 1837), Amblyopsis rosae (Eigenmann, 1898), Amblyopsis spelaea DeKay, 1842, Amblyospiza albifrons (Vigors, 1831), Amblypharyngodon atkinsonii (Blyth, 1860), Amblypharyngodon chulabhornae Vidthayanon & Kottelat, 1990, Amblypharyngodon melettinus (Valenciennes, 1844), Amblypharyngodon microlepis (Bleeker, 1853), Amblypharyngodon mola (Hamilton, 1822), Amblypomacentrus breviceps (Schlegel & Müller, 1839), Amblyrhynchichthys micracanthus Ng & Kottelat, 2004, Amblyrhynchichthys truncatus (Bleeker, 1850), Ambystoma andersoni Krebs & Brandon, 1984, Ambystoma laterale Hallowell, 1856, Ambystoma macrodactylum Baird, 1850, Ambystoma maculatum (Shaw, 1802), Ambystoma mexicanum (Shaw & Nodder, 1798), Ambystoma opacum (Gravenhorst, 1807), Ambystoma talpoideum (Holbrook, 1838), Ameca splendens Gartner, 1981, Ameerega altamazonica Twomey & Brown, 2008, Ameerega bassleri (Melin, 1941), Ameerega bassleri (Melin, 1941), Ameerega bilinguis (Jungfer, 1989), Ameerega cainarachi (Schulte, 1989), Ameerega cainarachi (Schulte, 1989), Ameerega hahneli (Boulenger, 1884), Ameerega hahneli (Boulenger, 1884), Ameerega parvula (Boulenger, 1882), Ameerega pepperi Brown & Twomey, 2009, Ameerega picta (Tschudi, 1838), Ameerega silverstonei (Myers & Daly, 1979), Ameerega trivittata (Spix, 1824), Ameerega trivittata (Spix, 1824), Ameiurus serracanthus (Yerger & Relyea, 1968), Ameiva ameiva (Linnaeus, 1758), Ameiva chaitzami Stuart, 1942, Ameiva festiva (Lichtenstein, 1856), Ameiva undulata (Wiegmann, 1834), Ammocrypta beanii Jordan, 1877, Ammocrypta pellucida (Putnam, 1863), Ammocrypta vivax Hay, 1882, Ammocryptocharax elegans Weitzman & Kanazawa, 1976, Ammocryptocharax lateralis (Eigenmann, 1909), Ammocryptocharax minutus Buckup, 1993, Ammocryptocharax vintonae (Eigenmann, 1909), Ammotragus lervia (Pallas, 1777), Amniataba affinis (Mees & Kailola, 1977), Amniataba caudavittata (Richardson, 1845), Amniataba percoides (Günther, 1864), Amnirana galamensis (Duméril & Bibron, 1841), Amolops larutensis (Boulenger, 1899), Amolops ricketti (Boulenger, 1899), Amphiesma stolatum Duméril, Bibron & Duméril, 1854, Amphilius atesuensis Boulenger, 1904, Amphilius jacksonii Boulenger, 1912, Amphilius kivuensis Pellegrin, 1933, Amphilius longirostris (Boulenger, 1901), Amphilius maesii Boulenger, 1919, Amphilius natalensis Boulenger, 1917, Amphilius platychir (Günther, 1864), Amphilius rheophilus Daget, 1959, Amphilius uranoscopus (Pfeffer, 1889), Amphilophus alfari (Meek, 1907), Amphilophus altifrons (Kner, 1863), Amphilophus amarillo Stauffer & McKaye, 2002, Amphilophus bussingi Loiselle, 1997, Amphilophus diquis (Bussing, 1974), Amphilophus hogaboomorum (Carr & Giovannoli, 1950), Amphilophus longimanus (Günther, 1867), Amphilophus lyonsi (Gosse, 1966), Amphilophus macracanthus (Günther, 1864), Amphilophus nourissati (Allgayer, 1989), Amphilophus robertsoni (Regan, 1905), Amphilophus rostratus (Gill, 1877), Amphilophus sagittae Stauffer & McKaye, 2002, Amphilophus xiloaensis Stauffer & McKaye, 2002, Amphilophus zaliosus (Barlow, 1976), Amphiprion akallopisos Bleeker, 1853, Amphiprion akindynos Allen, 1972, Amphiprion allardi Klausewitz, 1970, Amphiprion bicinctus Rüppell, 1830, Amphiprion chrysopterus Cuvier, 1830, Amphiprion clarkii (Bennett, 1830), Amphiprion ephippium (Bloch, 1790), Amphiprion frenatus Brevoort, 1856, Amphiprion latezonatus Waite, 1900, Amphiprion leucokranos Allen, 1973, Amphiprion mccullochi Whitley, 1929, Amphiprion melanopus Bleeker, 1852, Amphiprion nigripes Regan, 1908, Amphiprion ocellaris Cuvier, 1830, Amphiprion percula (Lacepède, 1802), Amphiprion perideraion Bleeker, 1855, Amphiprion polymnus (Linnaeus, 1758), Amphiprion rubrocinctus Richardson, 1842, Amphiprion sandaracinos Allen, 1972, Amphiprion sebae Bleeker, 1853, Amphiprion tricinctus Schultz & Welander, 1953, Amyda cartilaginea (Boddaert, 1770), Anabarilius grahami (Regan, 1908), Anabas cobojius (Hamilton, 1822), Anabas testudineus (Bloch, 1792), Anableps anableps (Linnaeus, 1758), Anableps dowei Gill, 1861, Anableps microlepis Müller & Troschel, 1844, Anadoras grypus (Cope, 1872), Anadoras insculptus (Miranda Ribeiro, 1912), Anadoras regani (Steindachner, 1908), Anadoras weddellii (Castelnau, 1855), Anaecypris hispanica (Steindachner, 1866), Anampses caeruleopunctatus Rüppell, 1829, Anampses chrysocephalus Randall, 1958, Anampses cuvier Quoy & Gaimard, 1824, Anampses femininus Randall, 1972, Anampses geographicus Valenciennes, 1840, Anampses lineatus Randall, 1972, Anampses melanurus Bleeker, 1857, Anampses meleagrides Valenciennes, 1840, Anampses neoguinaicus Bleeker, 1878, Anarhichas lupus Linnaeus, 1758, Anarhichas minor Olafsen, 1772, Anas acuta Linnaeus, 1758, Anas americana Gmelin, 1789, Anas bahamensis Linnaeus, 1758, Anas bernieri (Hartlaub, 1860), Anas capensis Gmelin, 1789, Anas castanea (Eyton, 1838), Anas clypeata Linnaeus, 1758, Anas crecca Linnaeus, 1758, Anas cyanoptera Vieillot, 1816, Anas discors Linnaeus, 1766, Anas erythrorhyncha Gmelin, 1789, Anas falcata Georgi, 1775, Anas flavirostris Vieillot, 1816, Anas formosa Georgi, 1775, Anas georgica Gmelin, 1789, Anas penelope Linnaeus, 1758, Anas platalea Vieillot, 1816, Anas platyrhynchos Linnaeus, 1758, Anas poecilorhyncha Sibley & Monroe, 1990, Anas querquedula Linnaeus, 1758, Anas rhynchotis Latham, 1802, Anas rubripes Brewster, 1902, Anas sibilatrix Poeppig, 1829, Anas smithii (Hartert, 1891), Anas strepera Linnaeus, 1758, Anas superciliosa Gmelin, 1789, Anas undulata C.F.Dubois, 1839, Anas versicolor Vieillot, 1816, Anas wyvilliana P.L.Sclater, 1878, Anaspidoglanis macrostoma (Pellegrin, 1909), Anaxyrus americanus (Holbrook, 1836), Anaxyrus baxteri (Porter, 1968), Anaxyrus boreas (Baird & Girard, 1852), Anaxyrus debilis (Girard, 1854), Anaxyrus debilis (Girard, 1854), Anaxyrus exsul (Myers, 1942), Anaxyrus hemiophrys (Cope, 1886), Anaxyrus microscaphus (Cope, 1867), Anaxyrus punctatus (Baird & Girard, 1852), Anaxyrus quercicus (Holbrook, 1840), Anaxyrus terrestris (Bonnaterre, 1789), Anaxyrus woodhousii (Girard, 1854), Ancharius fuscus Steindachner, 1880, Ancherythroculter lini Luo, 1994, Anchoviella alleni (Myers, 1940), Ancistrus aguaboensis Fisch-Muller, Mazzoni & Weber, 2001, Ancistrus bolivianus (Steindachner, 1915), Ancistrus brevifilis Eigenmann, 1920, Ancistrus brevipinnis (Regan, 1904), Ancistrus bufonius (Valenciennes, 1840), Ancistrus caucanus Fowler, 1943, Ancistrus centrolepis Regan, 1913, Ancistrus chagresi Eigenmann & Eigenmann, 1889, Ancistrus cirrhosus (Valenciennes, 1836), Ancistrus claro Knaack, 1999, Ancistrus clementinae Rendahl, 1937, Ancistrus cuiabae Knaack, 1999, Ancistrus dolichopterus Kner, 1854, Ancistrus dubius Eigenmann & Eigenmann, 1889, Ancistrus erinaceus (Valenciennes, 1840), Ancistrus formoso Sabino & Trajano, 1997, Ancistrus galani Pérez & Viloria, 1994, Ancistrus gymnorhynchus Kner, 1854, Ancistrus hoplogenys (Günther, 1864), Ancistrus jelskii (Steindachner, 1876), Ancistrus leucostictus (Günther, 1864), Ancistrus lineolatus Fowler, 1943, Ancistrus lithurgicus Eigenmann, 1912, Ancistrus macrophthalmus (Pellegrin, 1912), Ancistrus malacops (Cope, 1872), Ancistrus maracasae Fowler, 1946, Ancistrus martini Schultz, 1944, Ancistrus megalostomus Pearson, 1924, Ancistrus minutus Fisch-Muller, Mazzoni & Weber, 2001, Ancistrus multispinis (Regan, 1912), Ancistrus nudiceps (Müller & Troschel, 1849), Ancistrus occidentalis (Regan, 1904), Ancistrus pirareta Muller, 1989, Ancistrus piriformis Muller, 1989, Ancistrus ranunculus Muller, Rapp Py-Daniel & Zuanon, 1994, Ancistrus spinosus Meek & Hildebrand, 1916, Ancistrus stigmaticus Eigenmann & Eigenmann, 1889, Ancistrus tamboensis Fowler, 1945, Ancistrus taunayi Miranda Ribeiro, 1918, Ancistrus temminckii (Valenciennes, 1840), Ancistrus trinitatis (Günther, 1864), Ancistrus triradiatus Eigenmann, 1918, Ancistrus variolus (Cope, 1872), Andamia tetradactylus (Bleeker, 1858), Andersonia leptura Boulenger, 1900, Andigena laminirostris Gould, 1851, Andinobates fulguritus (Silverstone, 1975), Andinobates minutus (Shreve, 1935), Andrias davidianus (Blanchard, 1871), Andrias japonicus (Temminck, 1836), Anduzedoras oxyrhynchus (Valenciennes, 1821), Anguilla anguilla (Linnaeus, 1758), Anguilla australis Richardson, 1841, Anguilla bengalensis (Gray, 1831), Anguilla bicolor McClelland, 1844, Anguilla borneensis Popta, 1924, Anguilla celebesensis Kaup, 1856, Anguilla dieffenbachii Gray, 1842, Anguilla japonica Temminck & Schlegel, 1846, Anguilla marmorata Quoy & Gaimard, 1824, Anguilla megastoma Kaup, 1856, Anguilla mossambica (Peters, 1852), Anguilla nebulosa McClelland, 1844, Anguilla obscura Günther, 1872, Anguilla reinhardtii Steindachner, 1867, Anhinga anhinga (Linnaeus, 1766), Anilius scytale (Linnaeus, 1758), Anisognathus somptuosus (Lesson, 1831), Anisotremus interruptus (Gill, 1862), Anisotremus virginicus (Linnaeus, 1758), Annamia normani (Hora, 1931), Anniella pulchra Gray, 1852, Anodontiglanis dahli Rendahl, 1922, Anodorhynchus hyacinthinus (Latham, 1790), Anodus orinocensis (Steindachner, 1887), Anolis allisoni Barbour, 1928, Anolis angusticeps Smith et al., 1968, Anolis argenteolus Cope, 1861, Anolis armouri (Cochran, 1934), Anolis baracoae Schwartz, 1964, Anolis barbatus (Garrido, 1982), Anolis barbouri (Schmidt, 1919), Anolis bartschi (Cochran, 1928), Anolis bimaculatus (Sparrman, 1784), Anolis brevirostris Bocourt, 1870, Anolis brunneus Cope, 1894, Anolis carolinensis Voigt, 1832, Anolis chlorocyanus Duméril & Bibron, 1837, Anolis christophei Williams, 1960, Anolis coelestinus Cope, 1862, Anolis cristatellus Duméril & Bibron, 1837, Anolis cupreus Hallowell, 1860, Anolis cybotes Cope, 1862, Anolis distichus Cope, 1862, Anolis equestris Merrem, 1820, Anolis etheridgei Williams, Anolis frenatus Cope, 1899, Anolis grahami Gray, 1845, Anolis hendersoni Cochran, 1923, Anolis humilis Peters, 1863, Anolis insolitus Williams & Rand, 1969, Anolis isolepis (Cope, 1861), Anolis leachii Duméril & Bibron, 1837, Anolis lemurinus Cope, 1861, Anolis limifrons Cope, 1862, Anolis marcanoi Williams, 1975, Anolis oculatus (Cope, 1879), Anolis olssoni Schmidt, 1919, Anolis oxylophus Cope, 1875, Anolis poecilopus Cope, 1862, Anolis porcatus Gray, 1840, Anolis roquet (Bonnaterre, 1789), Anolis sabanus Garman, 1887, Anolis sagrei Duméril & Bibron, 1837, Anolis semilineatus Cope, 1864, Anolis smallwoodi Schwartz, 1964, Anolis smaragdinus Barbour & Shreve, 1935, Anolis valencienni Duméril & Bibron, 1837, Anolis vermiculatus Cocteau, 1837, Anomalochromis thomasi (Boulenger, 1915), Anomalops katoptron (Bleeker, 1856), Anoplocapros lenticularis (Richardson, 1841), Anoplopoma fimbria (Pallas, 1814), Anostomoides atrianalis Pellegrin, 1909, Anostomoides laticeps (Eigenmann, 1912), Anostomus anostomus (Linnaeus, 1758), Anostomus brevior Géry, 1961, Anostomus ternetzi Fernández-Yépez, 1949, Anoura geoffroyi Gray, 1838, Anser albifrons (Scopoli, 1769), Anser anser (Linnaeus, 1758), Anser brachyrhynchus Baillon, 1834, Anser cygnoides (Linnaeus, 1758), Anser erythropus (Linnaeus, 1758), Anser fabalis (Latham, 1787), Anser indicus (Latham, 1790), Anseranas semipalmata (Latham, 1798), Antaresia childreni (Gray, 1842), Antaresia childreni (Gray, 1842), Antaresia maculosa (Peters, 1873), Antaresia perthensis (Stull, 1932), Antaresia stimsoni (Smith, 1985), Antennarius commerson (Latreille, 1804), Antennarius maculatus (Desjardins, 1840), Antennarius pictus (Shaw, 1794), Antennarius striatus (Shaw, 1794), Antennatus tuberosus (Cuvier, 1817), Anthochaera paradoxa (Daudin, 1800), Anthracoceros coronatus (Boddaert, 1783), Anthropoides virgo (Linnaeus, 1758), Anthus gustavi Swinhoe, 1863, Antidorcas marsupialis (Zimmermann, 1780), Antilocapra americana (Ord, 1815), Antilope cervicapra (Linnaeus, 1758), Antrostomus ridgwayi Nelson, 1897, Aonyx capensis (Schinz, 1821), Aotus nancymaae Hershkovitz, 1983, Aotus trivirgatus (Humboldt, 1811), Aotus vociferans (Spix, 1823), Apareiodon affinis (Steindachner, 1879), Apareiodon argenteus Pavanelli & Britski, 2003, Apareiodon cavalcante Pavanelli & Britski, 2003, Apareiodon davisi Fowler, 1941, Apareiodon gransabana Starnes & Schindler, 1993, Apareiodon hasemani Eigenmann, 1916, Apareiodon ibitiensis Amaral Campos, 1944, Apareiodon itapicuruensis Eigenmann & Henn, 1916, Apareiodon machrisi Travassos, 1957, Apareiodon orinocensis Bonilla, Machado-Allison, Silvera, Chernoff, López & Lasso, 1999, Apareiodon piracicabae (Eigenmann, 1907), Apareiodon vittatus Garavello, 1977, Aphanius apodus (Gervais, 1853), Aphanius asquamatus (Sözer, 1942), Aphanius baeticus Doadrio, Carmona & Fernández-Delgado, 2002, Aphanius dispar (Rüppell, 1829), Aphanius fasciatus (Valenciennes, 1821), Aphanius ginaonis (Holly, 1929), Aphanius iberus (Valenciennes, 1846), Aphanius mento (Heckel, 1843), Aphanius sirhani Villwock, Scholl & Krupp, 1983, Aphanius sophiae (Heckel, 1847), Aphanius splendens (Kosswig & Sözer, 1945), Aphanius stiassnyae (Getahun & Lazara, 2001), Aphanius sureyanus (Neu, 1937), Aphanius vladykovi Coad, 1988, Aphyocharacidium bolivianum Géry, 1973, Aphyocharacidium melandetum (Eigenmann, 1912), Aphyocharax alburnus (Günther, 1869), Aphyocharax anisitsi Eigenmann & Kennedy, 1903, Aphyocharax colifax Taphorn & Thomerson, 1991, Aphyocharax dentatus Eigenmann & Kennedy, 1903, Aphyocharax nattereri (Steindachner, 1882), Aphyocharax nattereri (Steindachner, 1882), Aphyocharax pusillus Günther, 1868, Aphyocharax rathbuni Eigenmann, 1907, Aphyocharax yekwanae Willink, Chernoff & Machado-Allison, 2003, Aphyocheirodon hemigrammus Eigenmann, 1915, Aphyocypris chinensis Günther, 1868, Aphyocypris kikuchii (Oshima, 1919), Aphyodite grammica Eigenmann, 1912, Aphyolebias peruensis (Myers, 1954), Aphyolebias rubrocaudatus (Seegers, 1984), Aphyosemion australe (Rachow, 1921), Aphyosemion bitaeniatum (Ahl, 1924), Aphyosemion bivittatum (Lönnberg, 1895), Aphyosemion bualanum (Ahl, 1924), Aphyosemion calliurum (Boulenger, 1911), Aphyosemion cameronense (Boulenger, 1903), Aphyosemion cyanostictum Lambert & Géry, 1968, Aphyosemion decorsei (Pellegrin, 1904), Aphyosemion escherichi (Ahl, 1924), Aphyosemion exiguum (Boulenger, 1911), Aphyosemion franzwerneri Scheel, 1971, Aphyosemion hera Huber, 1998, Aphyosemion joergenscheeli Huber & Radda, 1977, Aphyosemion lamberti Radda & Huber, 1977, Aphyosemion mimbon Huber, 1977, Aphyosemion ocellatum Huber & Radda, 1977, Aphyosemion passaroi Huber, 1994, Aphyosemion polli Radda & Pürzl, 1987, Aphyosemion primigenium Radda & Huber, 1977, Aphyosemion splendopleure (Brüning, 1929), Aphyosemion tirbaki Huber, 1999, Apionichthys dumerili Kaup, 1858, Apionichthys menezesi Ramos, 2003, Apionichthys sauli Ramos, 2003, Apionichthys seripierriae Ramos, 2003, Apistogramma acrensis Staeck, 2003, Apistogramma agassizii (Steindachner, 1875), Apistogramma alacrina Kullander, 2004, Apistogramma arua Römer & Warzel, 1998, Apistogramma atahualpa Römer, 1997, Apistogramma bitaeniata Pellegrin, 1936, Apistogramma borellii (Regan, 1906), Apistogramma brevis Kullander, 1980, Apistogramma cacatuoides Hoedeman, 1951, Apistogramma caetei Kullander, 1980, Apistogramma commbrae (Regan, 1906), Apistogramma cruzi Kullander, 1986, Apistogramma diplotaenia Kullander, 1987, Apistogramma elizabethae Kullander, 1980, Apistogramma eunotus Kullander, 1981, Apistogramma geisleri Meinken, 1971, Apistogramma gephyra Kullander, 1980, Apistogramma gibbiceps Meinken, 1969, Apistogramma gossei Kullander, 1982, Apistogramma guttata Antonio C., Kullander & Lasso A., 1989, Apistogramma hippolytae Kullander, 1982, Apistogramma hoignei Meinken, 1965, Apistogramma hongsloi Kullander, 1979, Apistogramma inconspicua Kullander, 1983, Apistogramma iniridae Kullander, 1979, Apistogramma inornata Staeck, 2003, Apistogramma juruensis Kullander, 1986, Apistogramma linkei Koslowski, 1985, Apistogramma luelingi Kullander, 1976, Apistogramma macmasteri Kullander, 1979, Apistogramma martini Römer, Hahn, Römer, Soares & Wöhler, 2003, Apistogramma meinkeni Kullander, 1980, Apistogramma mendezi Römer, 1994, Apistogramma moae Kullander, 1980, Apistogramma nijsseni Kullander, 1979, Apistogramma norberti Staeck, 1991, Apistogramma ortmanni (Eigenmann, 1912), Apistogramma panduro Römer, 1997, Apistogramma paucisquamis Kullander & Staeck, 1988, Apistogramma payaminonis Kullander, 1986, Apistogramma personata Kullander, 1980, Apistogramma pertensis (Haseman, 1911), Apistogramma pulchra Kullander, 1980, Apistogramma regani Kullander, 1980, Apistogramma resticulosa Kullander, 1980, Apistogramma rubrolineata Hein, Zarske & Zapata, 2002, Apistogramma rupununi Fowler, 1914, Apistogramma staecki Koslowski, 1985, Apistogramma steindachneri (Regan, 1908), Apistogramma taeniata (Günther, 1862), Apistogramma trifasciata (Eigenmann & Kennedy, 1903), Apistogramma tucurui Staeck, 2003, Apistogramma uaupesi Kullander, 1980, Apistogramma urteagai Kullander, 1986, Apistogramma velifera Staeck, 2003, Apistogramma viejita Kullander, 1979, Apistogrammoides pucallpaensis Meinken, 1965, Apistoloricaria condei Isbrücker & Nijssen, 1986, Apistoloricaria laani Nijssen & Isbrücker, 1988, Apistoloricaria ommation Nijssen & Isbrücker, 1988, Apistus carinatus (Bloch & Schneider, 1801), Aplocheilichthys spilauchen (Duméril, 1861), Aplocheilus blockii Arnold, 1911, Aplocheilus dayi Steindachner, 1892, Aplocheilus lineatus (Valenciennes, 1846), Aplocheilus panchax (Hamilton, 1822), Aplocheilus parvus (Sundara Raj, 1916), Aplochiton taeniatus Jenyns, 1842, Aplochiton zebra Jenyns, 1842, Aplopeltura boa (Boie, 1828), Apodichthys flavidus Girard, 1854, Apodora papuana (Peters & Doria, 1878), Apogon angustatus (Smith & Radcliffe, 1911), Apogon annularis Rüppell, 1829, Apogon aureus (Lacepède, 1802), Apogon compressus (Smith & Radcliffe, 1911), Apogon crassiceps Garman, 1903, Apogon cyanosoma Bleeker, 1853, Apogon dovii Günther, 1862, Apogon fraenatus Valenciennes, 1832, Apogon holotaenia Regan, 1905, Apogon leptacanthus Bleeker, 1856, Apogon limenus Randall & Hoese, 1988, Apogon luteus Randall & Kulbicki, 1998, Apogon maculatus (Poey, 1860), Apogon nigrofasciatus Lachner, 1953, Apogon oxina Fraser, 1999, Apogon parvulus (Smith & Radcliffe, 1912), Apogon pseudomaculatus Longley, 1932, Apogon quadrisquamatus Longley, 1934, Apogon retrosella (Gill, 1862), Apogon selas Randall & Hayashi, 1990, Apogon semiornatus Peters, 1876, Apogon thermalis Cuvier, 1829, Apogon timorensis Bleeker, 1854, Apogon townsendi (Breder, 1927), Apogon urostigma (Bleeker, 1874), Apolemichthys arcuatus (Gray, 1831), Apolemichthys griffisi (Carlson & Taylor, 1981), Apolemichthys trimaculatus (Cuvier, 1831), Apolemichthys xanthopunctatus Burgess, 1973, Apolemichthys xanthotis (Fraser-Brunner, 1950), Apolemichthys xanthurus (Bennett, 1833), Apomys hylocetes Mearns, 1905, Aposturisoma myriodon Isbrücker, Britski, Nijssen & Ortega, 1983, Aptenodytes forsteri G.R.Gray, 1844, Aptenodytes patagonicus J.F.Miller, 1778, Apteronotus albifrons (Linnaeus, 1766), Apteronotus apurensis Fernández-Yépez, 1968, Apteronotus bonapartii (Castelnau, 1855), Apteronotus brasiliensis (Reinhardt, 1852), Apteronotus caudimaculosus de Santana, 2003, Apteronotus cuchillejo (Schultz, 1949), Apteronotus cuchillo Schultz, 1949, Apteronotus ellisi (Alonso de Arámburu, 1957), Apteronotus eschmeyeri de Santana, Maldonado-Ocampo, Severi & Mendes, 2004, Apteronotus jurubidae (Fowler, 1944), Apteronotus leptorhynchus (Ellis, 1912), Apteronotus macrolepis (Steindachner, 1881), Apteronotus macrostomus (Fowler, 1943), Apteronotus magdalenensis (Miles, 1945), Apteronotus mariae (Eigenmann & Fisher, 1914), Apteronotus rostratus (Meek & Hildebrand, 1913), Apteronotus spurrellii (Regan, 1914), Apteryx australis Shaw, 1813, Aptocyclus ventricosus (Pallas, 1769), Aquila fasciata Vieillot, 1822, Aquila nipalensis Hodgson, 1833, Aquila pomarina C.L.Brehm, 1831, Aquila rapax (Temminck, 1828), Aquila spilogaster (Bonaparte, 1850), Aquila verreauxii Lesson, 1831, Ara ambiguus (Bechstein, 1811), Ara ararauna (Linnaeus, 1758), Ara chloropterus G.R.Gray, 1859, Ara chloropterus G.R.Gray, 1859, Ara glaucogularis Dabbene, 1921, Ara macao (Linnaeus, 1758), Ara militaris (Linnaeus, 1766), Ara rubrogenys Lafresnaye, 1847, Ara severus (Linnaeus, 1758), Ara severus (Linnaeus, 1758), Aracana aurita (Shaw, 1798), Aracana ornata (Gray, 1838), Aramides ypecaha (Vieillot, 1819), Arapaima gigas (Schinz, 1822), Arapaima gigas (Schinz, 1822), Aratinga acuticaudata (Vieillot, 1818), Aratinga aurea (Gmelin, 1788), Aratinga auricapillus (Kuhl, 1820), Aratinga auricapillus (Kuhl, 1820), Aratinga canicularis (Linnaeus, 1758), Aratinga chloroptera (Souance, 1856), Aratinga erythrogenys (Lesson, 1844), Aratinga euops (Wagler, 1832), Aratinga finschi (Salvin, 1871), Aratinga holochlora (P.L.Sclater, 1859), Aratinga holochlora (P.L.Sclater, 1859), Aratinga jandaya (Gmelin, 1788), Aratinga leucophthalma (Statius Muller, 1776), Aratinga leucophthalma (Statius Muller, 1776), Aratinga mitrata (Tschudi, 1844), Aratinga nana (Vigors, 1830), Aratinga pertinax (Linnaeus, 1758), Aratinga solstitialis (Linnaeus, 1758), Aratinga wagleri (G.R.Gray, 1845), Aratinga weddellii (Deville, 1851), Archamia fucata (Cantor, 1849), Archamia macroptera (Cuvier, 1828), Archelaphe bella (Stanley, 1917), Archocentrus centrarchus (Gill, 1877), Archolaemus blax Korringa, 1970, Arctictis binturong (Raffles, 1821), Arctocephalus pusillus (Schreber, 1775), Ardeotis kori (Burchell, 1822), Argonectes longiceps (Kner, 1858), Argonectes robertsi Langeani, 1999, Argopleura chocoensis (Eigenmann, 1913), Argopleura conventus (Eigenmann, 1913), Argopleura diquensis (Eigenmann, 1913), Argopleura magdalenensis (Eigenmann, 1913), Argusianus argus (Linnaeus, 1766), Ariopsis assimilis (Günther, 1864), Ariopsis felis (Linnaeus, 1766), Ariopsis graeffei (Kner & Steindachner, 1867), Ariopsis guatemalensis (Günther, 1864), Ariopsis seemanni (Günther, 1864), Aristochromis christyi Trewavas, 1935, Arius acutirostris Day, 1877, Arius africanus Frost, 1926, Arius heudelotii Valenciennes, 1840, Arius latiscutatus Günther, 1864, Arius maculatus (Thunberg, 1792), Arius oetik Bleeker, 1846, Arius venosus Valenciennes, 1840, Arizona elegans Kennicot In Baird, 1859, Arothron hispidus (Linnaeus, 1758), Arothron immaculatus (Bloch & Schneider, 1801), Arothron manilensis (Marion de Procé, 1822), Arothron mappa (Lesson, 1831), Arothron meleagris (Anonymous, 1798), Arothron nigropunctatus (Bloch & Schneider, 1801), Arothron reticularis (Bloch & Schneider, 1801), Arothron stellatus (Anonymous, 1798), Arrhamphus sclerolepis Günther, 1866, Artibeus jamaicensis Leach, 1821, Asio otus (Linnaeus, 1758), Aspidelaps lubricus (Laurenti, 1768), Aspidelaps scutatus Smith, 1849, Aspidites melanocephalus (Krefft, 1864), Aspidites ramsayi (Macleay, 1882), Aspidontus taeniatus Quoy & Gaimard, 1834, Aspidoparia jaya (Hamilton, 1822), Aspidoras albater Nijssen & Isbrücker, 1976, Aspidoras belenos Britto, 1998, Aspidoras depinnai Britto, 2000, Aspidoras fuscoguttatus Nijssen & Isbrücker, 1976, Aspidoras menezesi Nijssen & Isbrücker, 1976, Aspidoras microgalaeus Britto, 1998, Aspidoras pauciradiatus (Weitzman & Nijssen, 1970), Aspidoras poecilus Nijssen & Isbrücker, 1976, Aspidoras raimundi (Steindachner, 1907), Aspidoras taurus Lima & Britto, 2001, Aspidoras virgulatus Nijssen & Isbrücker, 1980, Aspredinichthys filamentosus (Valenciennes, 1840), Aspredinichthys tibicen (Valenciennes, 1840), Aspredo aspredo (Linnaeus, 1758), Assessor flavissimus Allen & Kuiter, 1976, Assessor macneilli Whitley, 1935, Assessor randalli Allen & Kuiter, 1976, Astatoreochromis alluaudi Pellegrin, 1904, Astatotilapia burtoni (Günther, 1894), Astatotilapia flaviijosephi (Lortet, 1883), Asterophysus batrachus Kner, 1858, Asthenes hudsoni (P.L.Sclater, 1874), Astrapogon stellatus (Cope, 1867), Astroblepus boulengeri (Regan, 1904), Astroblepus chotae (Regan, 1904), Astroblepus cirratus (Regan, 1912), Astroblepus cyclopus (Humboldt, 1805), Astroblepus festae (Boulenger, 1898), Astroblepus fissidens (Regan, 1904), Astroblepus grixalvii Humboldt, 1805, Astroblepus guentheri (Boulenger, 1887), Astroblepus heterodon (Regan, 1908), Astroblepus homodon (Regan, 1904), Astroblepus mancoi Eigenmann, 1928, Astroblepus marmoratus (Regan, 1904), Astroblepus micrescens Eigenmann, 1918, Astroblepus orientalis (Boulenger, 1903), Astroblepus retropinnus (Regan, 1908), Astroblepus sabalo (Valenciennes, 1840), Astroblepus simonsii (Regan, 1904), Astroblepus supramollis Pearson, 1937, Astrochelys radiata (Shaw, 1802), Astrochelys radiata (Shaw, 1802), Astrochelys yniphora (Vaillant, 1885), Astrodoras asterifrons (Kner, 1853), Astronotus crassipinnis (Heckel, 1840), Astyanacinus moorii (Boulenger, 1892), Astyanacinus multidens Pearson, 1924, Astyanax abramis (Jenyns, 1842), Astyanax altiparanae Garutti & Britski, 2000, Astyanax anterior Eigenmann, 1908, Astyanax argyrimarginatus Garutti, 1999, Astyanax asuncionensis Géry, 1972, Astyanax atratoensis Eigenmann, 1907, Astyanax bimaculatus (Linnaeus, 1758), Astyanax brachypterygium Bertaco & Malabarba, 2001, Astyanax brevirhinus Eigenmann, 1908, Astyanax caucanus (Steindachner, 1879), Astyanax cordovae (Günther, 1880), Astyanax correntinus (Holmberg, 1891), Astyanax cremnobates Bertaco & Malabarba, 2001, Astyanax daguae Eigenmann, 1913, Astyanax eigenmanniorum (Cope, 1894), Astyanax erythropterus (Holmberg, 1891), Astyanax fasciatus (Cuvier, 1819), Astyanax festae (Boulenger, 1898), Astyanax filiferus (Eigenmann, 1913), Astyanax gisleni Dahl, 1943, Astyanax giton Eigenmann, 1908, Astyanax goyacensis Eigenmann, 1908, Astyanax guaporensis Eigenmann, 1911, Astyanax guianensis Eigenmann, 1909, Astyanax gymnogenys Eigenmann, 1911, Astyanax hastatus Myers, 1928, Astyanax integer Myers, 1930, Astyanax intermedius Eigenmann, 1908, Astyanax ita Almirón, Azpelicueta & Casciotta, 2002, Astyanax jacuhiensis (Cope, 1894), Astyanax janeiroensis Eigenmann, 1908, Astyanax jenynsii (Steindachner, 1877), Astyanax kullanderi Costa, 1995, Astyanax latens Mirande, Aguilera & Azpelicueta, 2004, Astyanax laticeps (Cope, 1894), Astyanax leonidas Azpelicueta, Casciotta & Almirón, 2002, Astyanax leopoldi Géry, Planquette & Le Bail, 1988, Astyanax lineatus (Perugia, 1891), Astyanax longior (Cope, 1878), Astyanax maculisquamis Garutti & Britski, 1997, Astyanax magdalenae Eigenmann & Henn, 1916, Astyanax marionae Eigenmann, 1911, Astyanax maximus (Steindachner, 1876), Astyanax megaspilura Fowler, 1944, Astyanax microlepis Eigenmann, 1913, Astyanax multidens Eigenmann, 1908, Astyanax mutator Eigenmann, 1909, Astyanax nasutus Meek, 1907, Astyanax nicaraguensis Eigenmann & Ogle, 1907, Astyanax obscurus (Hensel, 1870), Astyanax ojiara Azpelicueta & Garcia, 2000, Astyanax orthodus Eigenmann, 1907, Astyanax paraguayensis (Fowler, 1918), Astyanax parahybae Eigenmann, 1908, Astyanax paris Azpelicueta, Almirón & Casciotta, 2002, Astyanax ribeirae Eigenmann, 1911, Astyanax ruberrimus Eigenmann, 1913, Astyanax saguazu Casciotta, Almirón & Azpelicueta, 2003, Astyanax saltor Travassos, 1960, Astyanax scabripinnis (Jenyns, 1842), Astyanax schubarti Britski, 1964, Astyanax scintillans Myers, 1928, Astyanax stenohalinus Messner, 1962, Astyanax stilbe (Cope, 1870), Astyanax superbus Myers, 1942, Astyanax symmetricus Eigenmann, 1908, Astyanax taeniatus (Jenyns, 1842), Astyanax trierythropterus Godoy, 1970, Astyanax troya Azpelicueta, Casciotta & Almirón, 2002, Astyanax turmalinensis Triques, Vono & Caiafa, 2003, Astyanax validus Géry, Planquette & Le Bail, 1991, Astyanax venezuelae Schultz, 1944, Astyanax villwocki Zarske & Géry, 1999, Ataeniobius toweri (Meek, 1904), Atelerix albiventris (Wagner, 1841), Atelerix algirus (Lereboullet, 1842), Atelerix frontalis (A.Smith, 1831), Ateles geoffroyi Kuhl, 1820, Atelomycterus marmoratus, Atelopus barbotini Lescure, 1981, Atelopus limosus Ibáñez, Jaramillo & Solís, 1995, Atelopus spumarius Cope, 1871, Atelopus varius (Lichtenstein & Martens, 1856), Atelopus zeteki Dunn, 1933, Athene cunicularia (Molina, 1782), Athene cunicularia (Molina, 1782), Athene noctua (Scopoli, 1769), Atheresthes stomias (Jordan & Gilbert, 1880), Atherinella alvarezi (Díaz-Pardo, 1972), Atherinella ammophila Chernoff & Miller, 1984, Atherinella argentea Chernoff, 1986, Atherinella blackburni (Schultz, 1949), Atherinella brasiliensis (Quoy & Gaimard, 1825), Atherinella chagresi (Meek & Hildebrand, 1914), Atherinella colombiensis (Hubbs, 1920), Atherinella crystallina (Jordan & Culver, 1895), Atherinella eriarcha Jordan & Gilbert, 1882, Atherinella guatemalensis (Günther, 1864), Atherinella guija (Hildebrand, 1925), Atherinella hubbsi (Bussing, 1979), Atherinella lisa (Meek, 1904), Atherinella marvelae (Chernoff & Miller, 1982), Atherinella meeki (Miller, 1907), Atherinella milleri (Bussing, 1979), Atherinella nepenthe (Myers & Wade, 1942), Atherinella nocturna (Myers & Wade, 1942), Atherinella pachylepis (Günther, 1864), Atherinella panamensis Steindachner, 1875, Atherinella sallei (Regan, 1903), Atherinella sardina (Meek, 1907), Atherinella schultzi (Álvarez & Carranza, 1952), Atherinella serrivomer Chernoff, 1986, Atherinella starksi (Meek & Hildebrand, 1923), Atherinops affinis (Ayres, 1860), Atherinopsis californiensis Girard, 1854, Atheris broadleyi Lawson, 1999, Atheris desaixi Ashe, 1968, Atheris nitschei Tornier, 1902, Atherurus africanus Gray, 1842, Atimastillas flavicollis (Swainson, 1837), Atopochilus savorgnani Sauvage, 1879, Atopochilus vogti Pellegrin, 1922, Atopomesus pachyodus Myers, 1927, Atractaspis bibronii Smith, 1849, Atractaspis irregularis (Reinhardt, 1843), Atractaspis micropholis Günther, 1872, Atractosteus tristoechus (Bloch & Schneider, 1801), Atractosteus tropicus Gill, 1863, Atractus badius (Boie, 1827), Atropoides nummifer (Rüppel, 1845), Atrosalarias fuscus (Rüppell, 1838), Attonitus bounites Vari & Ortega, 2000, Attonitus ephimeros Vari & Ortega, 2000, Attonitus irisae Vari & Ortega, 2000, Atypichthys strigatus (Günther, 1860), Auchenipterichthys coracoideus (Eigenmann & Allen, 1942), Auchenipterichthys longimanus (Günther, 1864), Auchenipterichthys punctatus (Valenciennes, 1840), Auchenipterichthys thoracatus (Kner, 1858), Auchenipterus ambyiacus Fowler, 1915, Auchenipterus brachyurus (Cope, 1878), Auchenipterus britskii Ferraris & Vari, 1999, Auchenipterus demerarae Eigenmann, 1912, Auchenipterus dentatus Valenciennes, 1840, Auchenipterus nigripinnis (Boulenger, 1895), Auchenipterus nuchalis (Spix & Agassiz, 1829), Auchenoglanis biscutatus (Geoffroy Saint-Hilaire, 1809), Auchenoglanis occidentalis (Valenciennes, 1840), Aulacorhynchus coeruleicinctis d'Orbigny, 1840, Aulacorhynchus haematopygus (Gould, 1835), Aulacorhynchus prasinus (Gould, 1833), Aulixidens eugeniae Böhlke, 1952, Aulonocara baenschi Meyer & Riehl, 1985, Aulonocara brevirostre (Trewavas, 1935), Aulonocara ethelwynnae Meyer, Riehl & Zetzsche, 1987, Aulonocara guentheri Eccles, 1989, Aulonocara hueseri Meyer, Riehl & Zetzsche, 1987, Aulonocara jacobfreibergi (Johnson, 1974), Aulonocara maylandi Trewavas, 1984, Aulonocara nyassae Regan, 1922, Aulonocara rostratum Trewavas, 1935, Aulonocara stuartgranti Meyer & Riehl, 1985, Aulonocranus dewindti (Boulenger, 1899), Aulopyge huegelii Heckel, 1843, Aulorhynchus flavidus Gill, 1861, Aulostomus chinensis (Linnaeus, 1766), Auriglobus amabilis (Roberts, 1982), Auriglobus nefastus (Roberts, 1982), Auriglobus silus (Roberts, 1982), Austrelaps superbus (Günther, 1858), Austroglanis barnardi (Skelton, 1981), Austroglanis gilli (Barnard, 1943), Austroglanis sclateri (Boulenger, 1901), Austrolebias adloffi (Ahl, 1922), Austrolebias affinis (Amato, 1986), Austrolebias alexandri (Castello & López, 1974), Austrolebias arachan Loureiro, Azpelicueta & García, 2004, Austrolebias bellottii (Steindachner, 1881), Austrolebias charrua Costa & Cheffe, 2001, Austrolebias cinereus (Amato, 1986), Austrolebias cyaneus (Amato, 1987), Austrolebias gymnoventris (Amato, 1986), Austrolebias jaegari Costa & Cheffe, 2002, Austrolebias luteoflammulatus (Vaz-Ferreira, Sierra de Soriano & Scaglia de Paulete, 1965), Austrolebias melanoorus (Amato, 1986), Austrolebias minuano Costa & Cheffe, 2001, Austrolebias nigripinnis (Regan, 1912), Austrolebias nigrofasciatus Costa & Cheffe, 2001, Austrolebias nioni (Berkenkamp, Reichert & Prieto, 1997), Austrolebias patriciae (Huber, 1995), Austrolebias periodicus (Costa, 1999), Austrolebias vandenbergi (Huber, 1995), Austrolebias vazferreirai (Berkenkamp, Etzel, Reichert & Salvia, 1994), Austrolebias viarius (Vaz-Ferreira, Sierra de Soriano & Scaglia de Paulete, 1965), Awaous banana (Valenciennes, 1837), Awaous flavus (Valenciennes, 1837), Awaous grammepomus (Bleeker, 1849), Awaous lateristriga (Duméril, 1861), Awaous tajasica (Lichtenstein, 1822), Axelrodia lindeae Géry, 1973, Axelrodia riesei Géry, 1966, Axelrodia stigmatias (Fowler, 1913), Axis axis (Erxleben, 1777), Axis calamianensis (Heude, 1888), Ayarnangra estuarius Roberts, 2001, Aythya affinis (Eyton, 1838), Aythya americana (Eyton, 1838), Aythya baeri (Radde, 1863), Aythya collaris (Donovan, 1809), Aythya ferina (Linnaeus, 1758), Aythya fuligula (Linnaeus, 1758), Aythya marila (Linnaeus, 1761), Aythya nyroca (Guldenstadt, 1770), Aythya valisineria (A.Wilson, 1814), Azemiops feae Boulenger, 1888, Aztecula sallaei (Günther, 1868), Babyrousa celebensis (Deninger, 1909), Bachia heteropa (Weigmann, 1856), Badis assamensis Ahl, 1937, Badis badis (Hamilton, 1822), Badis blosyrus Kullander & Britz, 2002, Badis chittagongis Kullander & Britz, 2002, Badis corycaeus Kullander & Britz, 2002, Badis ferrarisi Kullander & Britz, 2002, Badis kanabos Kullander & Britz, 2002, Badis khwae Kullander & Britz, 2002, Badis kyar Kullander & Britz, 2002, Badis pyema Kullander & Britz, 2002, Badis ruber Schreitmüller, 1923, Badis siamensis Klausewitz, 1957, Bagarius bagarius (Hamilton, 1822), Bagarius rutilus Ng & Kottelat, 2000, Bagarius suchus Roberts, 1983, Bagarius yarrelli (Sykes, 1839), Bagre marinus (Mitchill, 1815), Bagre panamensis (Gill, 1863), Bagre pinnimaculatus (Steindachner, 1876), Bagrichthys macracanthus (Bleeker, 1854), Bagrichthys macropterus (Bleeker, 1854), Bagrichthys majusculus Ng, 2002, Bagrichthys obscurus Ng, 1999, Bagrichthys vaillantii (Popta, 1906), Bagrus bajad (Forsskål, 1775), Bagrus caeruleus Roberts & Stewart, 1976, Bagrus docmak (Forsskål, 1775), Bagrus filamentosus Pellegrin, 1924, Bagrus meridionalis Günther, 1894, Bagrus orientalis Boulenger, 1902, Bagrus ubangensis Boulenger, 1902, Bagrus urostigma Vinciguerra, 1895, Baileychromis centropomoides (Bailey & Stewart, 1977), Baillonius bailloni (Vieillot, 1819), Balaeniceps rex Gould, 1850, Balantiocheilos melanopterus (Bleeker, 1850), Balearica pavonina (Linnaeus, 1758), Balistapus undulatus (Park, 1797), Balistes capriscus Gronow, 1854, Balistes capriscus Gronow, 1854, Balistes polylepis Steindachner, 1876, Balistes vetula Linnaeus, 1758, Balistoides conspicillum (Bloch & Schneider, 1801), Balistoides viridescens (Bloch & Schneider, 1801), Balitora brucei Gray, 1830, Bambusicola fytchii Anderson, 1871, Bangana behri (Fowler, 1937), Bangana lemassoni (Pellegrin & Chevey, 1936), Bangana lippus (Fowler, 1936), Bangana sinkleri (Fowler, 1934), Bangana tonkinensis (Pellegrin & Chevey, 1934), Barbatula barbatula (Linnaeus, 1758), Barbatula nuda (Bleeker, 1864), Barbatula toni (Dybowski, 1869), Barbichthys laevis (Valenciennes, 1842), Barbodes carnaticus (Jerdon, 1849), Barbodes colemani (Fowler, 1937), Barbodes sunieri (Weber & de Beaufort, 1916), Barbodes wynaadensis (Day, 1873), Barboides gracilis Brüning, 1929, Barbonymus altus (Günther, 1868), Barbonymus gonionotus (Bleeker, 1849), Barbonymus schwanenfeldii (Bleeker, 1854), Barbonymus schwanenfeldii (Bleeker, 1854), Barbucca diabolica Roberts, 1989, Barbulifer pantherinus (Pellegrin, 1901), Barbus ablabes (Bleeker, 1863), Barbus aboinensis Boulenger, 1911, Barbus afrohamiltoni Crass, 1960, Barbus afrovernayi Nichols & Boulton, 1927, Barbus albanicus Steindachner, 1870, Barbus amatolicus Skelton, 1990, Barbus andrewi Barnard, 1937, Barbus anema Boulenger, 1903, Barbus annectens Gilchrist & Thompson, 1917, Barbus anoplus Weber, 1897, Barbus apleurogramma Boulenger, 1911, Barbus arabicus Trewavas, 1941, Barbus arcislongae Keilhack, 1908, Barbus argenteus Günther, 1868, Barbus atakorensis Daget, 1957, Barbus atkinsoni Bailey, 1969, Barbus atromaculatus Nichols & Griscom, 1917, Barbus balcanicus Kotlík, Tsigenopoulos, Ráb & Berrebi, 2002, Barbus barbus (Linnaeus, 1758), Barbus barnardi Jubb, 1965, Barbus barotseensis Pellegrin, 1920, Barbus baudoni Boulenger, 1918, Barbus bawkuensis Hopson, 1965, Barbus bifrenatus Fowler, 1935, Barbus bigornei Lévêque, Teugels & Thys van den Audenaerde, 1988, Barbus borysthenicus Dybowski, 1862, Barbus brazzai Pellegrin, 1901, Barbus breviceps Trewavas, 1936, Barbus brevidorsalis Boulenger, 1915, Barbus brevipinnis Jubb, 1966, Barbus bynni (Forsskål, 1775), Barbus cadenati Daget, 1962, Barbus calidus Barnard, 1938, Barbus callensis Valenciennes, 1842, Barbus callipterus Boulenger, 1907, Barbus camptacanthus (Bleeker, 1863), Barbus caninus Bonaparte, 1839, Barbus carpathicus Kotlík, Tsigenopoulos, Ráb & Berrebi, 2002, Barbus cercops Whitehead, 1960, Barbus chicapaensis Poll, 1967, Barbus chiumbeensis Pellegrin, 1936, Barbus chlorotaenia Boulenger, 1911, Barbus choloensis Norman, 1925, Barbus ciscaucasicus Kessler, 1877, Barbus clauseni Thys van den Audenaerde, 1976, Barbus collarti Poll, 1945, Barbus cyclolepis Heckel, 1837, Barbus deserti Pellegrin, 1909, Barbus dorsolineatus Trewavas, 1936, Barbus eburneensis Poll, 1941, Barbus erubescens Skelton, 1974, Barbus ethiopicus Zolezzi, 1939, Barbus euboicus Stephanidis, 1950, Barbus eutaenia Boulenger, 1904, Barbus fasciolatus Günther, 1868, Barbus foutensis Lévêque, Teugels & Thys van den Audenaerde, 1988, Barbus fritschii Günther, 1874, Barbus gananensis Vinciguerra, 1895, Barbus greenwoodi Poll, 1967, Barbus grypus Heckel, 1843, Barbus guildi Loiselle, 1973, Barbus guineensis Pellegrin, 1913, Barbus guirali Thominot, 1886, Barbus gurneyi Günther, 1868, Barbus haasi Mertens, 1925, Barbus haasianus David, 1936, Barbus holotaenia Boulenger, 1904, Barbus hospes Barnard, 1938, Barbus humilis Boulenger, 1902, Barbus innocens Pfeffer, 1896, Barbus jacksoni Günther, 1889, Barbus jae Boulenger, 1903, Barbus janssensi Poll, 1976, Barbus kerstenii Peters, 1868, Barbus lacerta Heckel, 1843, Barbus lagensis (Günther, 1868), Barbus laticeps Pfeffer, 1889, Barbus leonensis Boulenger, 1915, Barbus lineomaculatus Boulenger, 1903, Barbus longiceps Valenciennes, 1842, Barbus lornae Ricardo-Bertram, 1943, Barbus lorteti Sauvage, 1882, Barbus lufukiensis Boulenger, 1917, Barbus luikae Ricardo, 1939, Barbus macedonicus Karaman, 1928, Barbus macinensis Daget, 1954, Barbus macrolepis Pfeffer, 1889, Barbus macrops Boulenger, 1911, Barbus macrotaenia Worthington, 1933, Barbus manicensis Pellegrin, 1919, Barbus mariae Holly, 1929, Barbus martorelli Roman, 1971, Barbus mattozi Guimarães, 1884, Barbus meridionalis Risso, 1827, Barbus mocoensis Trewavas, 1936, Barbus motebensis Steindachner, 1894, Barbus multilineatus Worthington, 1933, Barbus musumbi Boulenger, 1910, Barbus nasus Günther, 1874, Barbus neefi Greenwood, 1962, Barbus neumayeri Fischer, 1884, Barbus nigeriensis Boulenger, 1903, Barbus niokoloensis Daget, 1959, Barbus nyanzae Whitehead, 1960, Barbus oligogrammus David, 1937, Barbus oxyrhynchus Pfeffer, 1889, Barbus pallidus Smith, 1841, Barbus paludinosus Peters, 1852, Barbus parablabes Daget, 1957, Barbus pellegrini Poll, 1939, Barbus peloponnesius Valenciennes, 1842, Barbus perince Rüppell, 1835, Barbus petitjeani Daget, 1962, Barbus plebejus Bonaparte, 1839, Barbus pleurogramma Boulenger, 1902, Barbus pobeguini Pellegrin, 1911, Barbus poechii Steindachner, 1911, Barbus prespensis Karaman, 1924, Barbus prionacanthus Mahnert & Géry, 1982, Barbus profundus Greenwood, 1970, Barbus punctitaeniatus Daget, 1954, Barbus quadripunctatus Pfeffer, 1896, Barbus radiatus Peters, 1853, Barbus raimbaulti Daget, 1962, Barbus reinii Günther, 1874, Barbus rubrostigma Poll & Lambert, 1964, Barbus sacratus Daget, 1963, Barbus salessei Pellegrin, 1908, Barbus serengetiensis Farm, 2000, Barbus serra Peters, 1864, Barbus stauchi Daget, 1967, Barbus stigmatopygus Boulenger, 1903, Barbus subinensis Hopson, 1965, Barbus sublineatus Daget, 1954, Barbus sylvaticus Loiselle & Welcomme, 1971, Barbus tanapelagius Graaf, Dejen, Sibbing & Osse, 2000, Barbus tauricus Kessler, 1877, Barbus tegulifer Fowler, 1936, Barbus thamalakanensis Fowler, 1935, Barbus thessalus Stephanidis, 1971, Barbus thysi Trewavas, 1974, Barbus toppini Boulenger, 1916, Barbus traorei Lévêque, Teugels & Thys van den Audenaerde, 1987, Barbus treurensis Groenewald, 1958, Barbus trevelyani Günther, 1877, Barbus trimaculatus Peters, 1852, Barbus trispilomimus Boulenger, 1907, Barbus trispilopleura Boulenger, 1902, Barbus trispilos (Bleeker, 1863), Barbus tropidolepis Boulenger, 1900, Barbus tyberinus Bonaparte, 1839, Barbus unitaeniatus Günther, 1867, Barbus viviparus Weber, 1897, Barbus walkeri Boulenger, 1904, Barbus wurtzi Pellegrin, 1908, Barbus yongei Whitehead, 1960, Barbus zanzibaricus Peters, 1868, Barilius bakeri Day, 1865, Barilius barila (Hamilton, 1822), Barilius barna (Hamilton, 1822), Barilius bendelisis (Hamilton, 1807), Barilius canarensis (Jerdon, 1849), Barilius caudiocellatus Chu, 1984, Barilius dogarsinghi Hora, 1921, Barilius gatensis (Valenciennes, 1844), Barilius huahinensis Fowler, 1934, Barilius infrafasciatus Fowler, 1934, Barilius mesopotamicus Berg, 1932, Barilius ngawa Vishwanath & Manojkumar, 2002, Barilius ornatus Sauvage, 1883, Barilius radiolatus Günther, 1868, Barilius shacra (Hamilton, 1822), Barilius tileo (Hamilton, 1822), Barilius vagra (Hamilton, 1822), Bario steindachneri (Eigenmann, 1893), Barisia imbricata (Wiegmann, 1828), Barnardius zonarius (Vigors & Horsfield, 1827), Barnardius zonarius (Vigors & Horsfield, 1827), Baryancistrus longipinnis (Kindle, 1895), Baryancistrus niveatus (Castelnau, 1855), Basileuterus rufifrons (Swainson, 1838), Basilichthys australis Eigenmann, 1928, Basilichthys microlepidotus (Jenyns, 1841), Basilichthys semotilus (Cope, 1874), Basiliscus basiliscus (Linnaeus, 1758), Basiliscus plumifrons Cope, 1875, Basiliscus vittatus Wiegmann, 1828, Batagur baska (Gray, 1831), Batagur borneoensis (Schlegel & Müller, 1844), Batagur borneoensis (Schlegel & Müller, 1844), Batagur dhongoka (Gray, 1834), Batagur kachuga (Gray, 1831), Batasio affinis Blyth, 1860, Batasio batasio (Hamilton, 1822), Batasio dayi (Vinciguerra, 1890), Batasio macronotus Ng & Edds, 2004, Batasio merianiensis (Chaudhuri, 1913), Batasio tengana (Hamilton, 1822), Batasio tigrinus Ng & Kottelat, 2001, Batasio travancoria Hora & Law, 1941, Bathybates fasciatus Boulenger, 1901, Bathybates graueri Steindachner, 1911, Bathybates leo Poll, 1956, Bathybates vittatus Boulenger, 1914, Bathyclarias nyasensis (Worthington, 1933), Bathygobius andrei (Sauvage, 1880), Bathygobius cyclopterus (Valenciennes, 1837), Bathymaster caeruleofasciatus Gilbert & Burke, 1912, Batrachocephalus mino (Hamilton, 1822), Batrachoides goldmani Evermann & Goldsborough, 1902, Batrachoides pacifici (Günther, 1861), Batrachoides surinamensis (Bloch & Schneider, 1801), Batrachoides waltersi Collette & Russo, 1981, Batrachomoeus trispinosus (Günther, 1861), Batrachoseps stebbinsi Brame & Murray, 1968, Batrochoglanis acanthochiroides (Güntert, 1942), Batrochoglanis raninus (Valenciennes, 1840), Batrochoglanis transmontanus (Regan, 1913), Batrochoglanis villosus (Eigenmann, 1912), Bavayia cyclura (Günther, 1872), Bavayia geitaina Wright, Bauer & Sadlier, 2000, Bavayia montana Roux, 1913, Bavayia robusta Wright, Bauer & Sadlier, 2000, Bavayia sauvagii (Boulenger, 1883), Beaufortia leveretti (Nichols & Pope, 1927), Bedotia geayi Pellegrin, 1907, Bedotia longianalis Pellegrin, 1914, Bedotia madagascariensis Regan, 1903, Bedotia marojejy Stiassny & Harrison, 2000, Bedotia masoala Sparks, 2001, Belodontichthys dinema (Bleeker, 1851), Belodontichthys truncatus Kottelat & Ng, 1999, Belonepterygion fasciolatum (Ogilby, 1889), Belonoglanis tenuis Boulenger, 1902, Belonoperca chabanaudi Fowler & Bean, 1930, Belonophago hutsebouti Giltay, 1929, Belontia hasselti (Cuvier, 1831), Belontia signata (Günther, 1861), Benitochromis batesii (Boulenger, 1901), Benitochromis nigrodorsalis Lamboj, 2001, Benitochromis riomuniensis (Thys van den Audenaerde, 1981), Benitochromis ufermanni Lamboj, 2001, Benthochromis melanoides (Poll, 1984), Benthochromis tricoti (Poll, 1948), Bergiaria westermanni (Lütken, 1874), Betta akarensis Regan, 1910, Betta albimarginata Kottelat & Ng, 1994, Betta anabatoides Bleeker, 1851, Betta balunga Herre, 1940, Betta bellica Sauvage, 1884, Betta brownorum Witte & Schmidt, 1992, Betta chloropharynx Kottelat & Ng, 1994, Betta coccina Vierke, 1979, Betta edithae Vierke, 1984, Betta enisae Kottelat, 1995, Betta falx Tan & Kottelat, 1998, Betta hipposideros Ng & Kottelat, 1994, Betta imbellis Ladiges, 1975, Betta livida Ng & Kottelat, 1992, Betta macrostoma Regan, 1910, Betta miniopinna Tan & Tan, 1994, Betta ocellata de Beaufort, 1933, Betta patoti Weber & de Beaufort, 1922, Betta persephone Schaller, 1986, Betta pi Tan, 1998, Betta picta (Valenciennes, 1846), Betta pinguis Tan & Kottelat, 1998, Betta prima Kottelat, 1994, Betta pugnax (Cantor, 1849), Betta pulchra Tan & Tan, 1996, Betta rubra Perugia, 1893, Betta schalleri Kottelat & Ng, 1994, Betta simorum Tan & Ng, 1996, Betta simplex Kottelat, 1994, Betta smaragdina Ladiges, 1972, Betta splendens Regan, 1910, Betta strohi Schaller & Kottelat, 1989, Betta taeniata Regan, 1910, Betta tussyae Schaller, 1985, Betta waseri Krummenacher, 1986, Bettongia penicillata Gray, 1837, Bettongia tropica Wakefield, 1967, Bidyanus bidyanus (Mitchell, 1838), Bidyanus welchi (McCulloch & Waite, 1917), Biotodoma cupido (Heckel, 1840), Biotodoma wavrini (Gosse, 1963), Biotoecus dicentrarchus Kullander, 1989, Biotoecus opercularis (Steindachner, 1875), Bison bison (Linnaeus, 1758), Bitis arietans Merrem, 1820, Bitis atropos (Linnaeus, 1758), Bitis caudalis (Smith, 1839), Bitis cornuta (Daudin, 1803), Bitis gabonica Duméril, Bibron & Duméril, 1854, Bitis nasicornis (Shaw & Nodder, 1792), Bitis parviocula Böhme, 1976, Bitis peringueyi (Boulenger, 1888), Bitis worthingtoni Parker, 1932, Bivibranchia bimaculata Vari, 1985, Bivibranchia fowleri (Steindachner, 1908), Bivibranchia notata Vari & Goulding, 1985, Bivibranchia simulata Géry, Planquette & Le Bail, 1991, Bivibranchia velox (Eigenmann & Myers, 1927), Biwia zezera (Ishikawa, 1895), Blaesodactylus boivini (Duméril, 1856), Blaesodactylus sakalava (Grandidier, 1867), Bleda syndactylus (Swainson, 1837), Blenniella chrysospilos (Bleeker, 1857), Blenniella periophthalmus (Valenciennes, 1836), Blennodesmus scapularis Günther, 1872, Blepsias cirrhosus (Pallas, 1814), Blicca bjoerkna (Linnaeus, 1758), Boa constrictor Linnaeus, 1758, Boaedon capensis Duméril, Bibron & Duméril, 1854, Boaedon fuliginosus (Boie, 1827), Boaedon lineatus Duméril, Bibron & Duméril, 1854, Boaedon olivaceus (Duméril, 1856), Boana boans (Linnaeus, 1758), Boana calcarata (Troschel, 1848), Boana calcarata (Troschel, 1848), Boana cinerascens (Spix, 1824), Boana crepitans (Wied-Neuwied, 1824), Boana fasciata (Günther, 1858), Boana geographica (Spix, 1824), Boana heilprini (Noble, 1923), Boana heilprini (Noble, 1923), Boana lanciformis (Cope, 1871), Boana picturata (Boulenger, 1899), Boana picturata (Boulenger, 1899), Boana punctata (Schneider, 1799), Bodianus anthioides (Bennett, 1832), Bodianus axillaris (Bennett, 1832), Bodianus bilunulatus (Lacepède, 1801), Bodianus bimaculatus Allen, 1973, Bodianus diana (Lacepède, 1801), Bodianus diplotaenia (Gill, 1862), Bodianus macrourus (Lacepède, 1801), Bodianus masudai Araga & Yoshino, 1975, Bodianus mesothorax (Bloch & Schneider, 1801), Bodianus opercularis (Guichenot, 1847), Bodianus perditio (Quoy & Gaimard, 1834), Bodianus pulchellus (Poey, 1860), Bodianus rufus (Linnaeus, 1758), Boehlkea fredcochui Géry, 1966, Bogertophis subocularis (Brown, 1901), Bogertophis subocularis (Brown, 1901), Boiga cyanea (Duméril, Bibron & Duméril, 1854), Boiga cynodon (Boie, 1827), Boiga dendrophila (Boie, 1827), Boiga drapiezii (Boie, 1827), Boiga irregularis (Bechstein, 1802), Boiga jaspidea (Duméril, Bibron & Duméril, 1854), Boiga multomaculata (Boie, 1827), Boiga nigriceps (Günther, 1863), Bolborhynchus lineola (Cassin, 1853), Boleophthalmus boddarti (Pallas, 1770), Bolitoglossa dofleini (Werner, 1903), Bolitoglossa mexicana Duméril, Bibron & Duméril, 1854, Bombina bombina (Linnaeus, 1761), Bombina maxima (Boulenger, 1905), Bombina microdeladigitora Liu, Hu & Yang, 1960, Bombina orientalis (Boulenger, 1890), Bombina variegata (Linnaeus, 1758), Bombycilla cedrorum Vieillot, 1808, Bonasa umbellus (Linnaeus, 1766), Boophis albilabris (Boulenger, 1888), Boophis ankaratra Andreone, 1993, Boophis boehmei Glaw & Vences, 1992, Boophis elenae Andreone, 1993, Boophis erythrodactylus (Guibé, 1953), Boophis luteus (Boulenger, 1882), Boophis madagascariensis (Peters, 1874), Boophis microtympanum (Boettger, 1881), Boophis picturatus Glaw, Vences, Andreone & Vallan, 2001, Boophis rappiodes (Ahl, 1928), Boophis tephraeomystax (Duméril, 1853), Boophis viridis Blommers-Schlösser, 1979, Boraras brigittae (Vogt, 1978), Boraras maculatus (Duncker, 1904), Boraras merah (Kottelat, 1991), Boraras micros Kottelat & Vidthayanon, 1993, Boraras urophthalmoides (Kottelat, 1991), Bos grunniens Linnaeus, 1766, Bos taurus Linnaeus, 1758, Boselaphus tragocamelus (Pallas, 1766), Bostockia porosa Castelnau, 1873, Bostrychia hagedash (Latham, 1790), Bostrychus africanus (Steindachner, 1879), Bostrychus sinensis Lacepède, 1801, Bostrychus zonatus Weber, 1907, Bothriechis aurifer (Salvin, 1860), Bothriechis lateralis Peters, 1862, Bothriechis nigroviridis Peters, 1859, Bothriechis schlegelii (Berthold, 1846), Bothrochilus albertisii (Peters & Doria, 1878), Bothrochilus boa (Schlegel, 1837), Bothrophthalmus lineatus Peters, 1863, Bothrops alternatus Duméril, Bibron & Duméril, 1854, Bothrops asper (Garman, 1883), Bothrops atrox (Linnaeus, 1758), Bothrops bilineatus (Wied-Neuwied, 1821), Bothrops bilineatus (Wied-Neuwied, 1821), Bothrops jararaca (Wied-Neuwied, 1824), Bothrops leucurus Wagler, Bothrops moojeni Hoge, 1966, Bothrops neuwiedi Wagler, 1824, Bothrops pictus (Tschudi, 1845), Bothrops venezuelensis Sandner-Montilla, 1952, Bothus lunatus (Linnaeus, 1758), Botia almorhae Gray, 1831, Botia dario (Hamilton, 1822), Botia histrionica Blyth, 1860, Botia lohachata Chaudhuri, 1912, Botia rostrata Günther, 1868, Botia striata Narayan Rao, 1920, Boulengerella cuvieri (Spix & Agassiz, 1829), Boulengerella lateristriga (Boulenger, 1895), Boulengerella lucius (Cuvier, 1816), Boulengerella maculata (Valenciennes, 1850), Boulengerella xyrekes Vari, 1995, Boulengerochromis microlepis (Boulenger, 1899), Boulengeromyrus knoepffleri Taverne & Géry, 1968, Brachaluteres jacksonianus (Quoy & Gaimard, 1824), Brachirus harmandi (Sauvage, 1878), Brachirus orientalis (Bloch & Schneider, 1801), Brachirus pan (Hamilton, 1822), Brachirus panoides (Bleeker, 1851), Brachirus salinarum Ogilby, 1910, Brachirus siamensis (Sauvage, 1878), Brachychalcinus copei (Steindachner, 1882), Brachychalcinus nummus Böhlke, 1958, Brachychalcinus orbicularis (Valenciennes, 1850), Brachychalcinus parnaibae Reis, 1989, Brachychalcinus retrospina Boulenger, 1892, Brachygalaxias bullocki (Regan, 1908), Brachyglanis magoi Fernández-Yépez, 1967, Brachyglanis melas Eigenmann, 1912, Brachyglanis microphthalmus Bizerril, 1991, Brachyglanis nocturnus Myers, 1928, Brachyglanis phalacra Eigenmann, 1912, Brachygobius aggregatus Herre, 1940, Brachygobius doriae (Günther, 1868), Brachygobius kabiliensis Inger, 1958, Brachygobius mekongensis Larson & Vidthayanon, 2000, Brachygobius nunus (Hamilton, 1822), Brachygobius sabanus Inger, 1958, Brachygobius xanthomelas Herre, 1937, Brachygobius xanthozonus (Bleeker, 1849), Brachyhypopomus beebei (Schultz, 1944), Brachyhypopomus brevirostris (Steindachner, 1868), Brachyhypopomus diazi (Fernández-Yépez, 1972), Brachyhypopomus janeiroensis (Costa & Campos-da-Paz, 1992), Brachyhypopomus occidentalis (Regan, 1914), Brachyhypopomus pinnicaudatus (Hopkins, 1991), Brachyistius frenatus Gill, 1862, Brachylophus fasciatus (Brongniart, 1800), Brachymystax lenok (Pallas, 1773), Brachymystax savinovi Mitrofanov, 1959, Brachyplatystoma filamentosum (Lichtenstein, 1819), Brachyplatystoma juruense (Boulenger, 1898), Brachyplatystoma rousseauxii (Castelnau, 1855), Brachyplatystoma vaillantii (Valenciennes, 1840), Brachyrhamdia heteropleura (Eigenmann, 1912), Brachyrhamdia imitator Myers, 1927, Brachyrhamdia meesi Sands & Black, 1985, Brachyrhaphis cascajalensis (Meek & Hildebrand, 1913), Brachyrhaphis episcopi (Steindachner, 1878), Brachyrhaphis hartwegi Rosen & Bailey, 1963, Brachyrhaphis holdridgei Bussing, 1967, Brachyrhaphis parismina (Meek, 1912), Brachyrhaphis punctifer (Hubbs, 1926), Brachyrhaphis rhabdophora (Regan, 1908), Brachyrhaphis roseni Bussing, 1988, Brachyrhaphis roswithae Meyer & Etzel, 1998, Brachyrhaphis terrabensis (Regan, 1907), Bradypodion damaranum (Boulenger, 1887), Bradypodion pumilum (Gmelin, 1789), Bradypodion thamnobates Raw, 1976, Bradypodion transvaalense (Fitzsimons, 1930), Bradypus variegatus Schinz, 1825, Bramocharax baileyi Rosen, 1972, Bramocharax bransfordii Gill, 1877, Bramocharax caballeroi Contreras-Balderas & Rivera-Teillery, 1985, Bramocharax dorioni Rosen, 1970, Branta bernicla (Linnaeus, 1758), Branta canadensis (Linnaeus, 1758), Branta leucopsis (Bechstein, 1803), Branta ruficollis (Pallas, 1769), Branta sandvicensis (Vigors, 1834), Breviceps adspersus Peters, 1882, Breviceps mossambicus Peters, 1854, Brienomyrus brachyistius (Gill, 1862), Brienomyrus longianalis (Boulenger, 1901), Brittanichthys axelrodi Géry, 1965, Brittanichthys myersi Géry, 1965, Brochiloricaria macrodon (Kner, 1853), Brochis britskii Nijssen & Isbrücker, 1983, Brochis multiradiatus (Orcés V., 1960), Brochis splendens (Castelnau, 1855), Bronchocela cristatella (Kuhl, 1820), Bronchocela jubata Duméril & Bibron, 1837, Brookesia betschi Brygoo, Blanc & Domergue, 1974, Brookesia brygooi Raxworthy & Nussbaum, 1995, Brookesia decaryi Angel, 1939, Brookesia ebenaui (Boettger, 1880), Brookesia griveaudi Brygoo, Blanc & Domergue, 1974, Brookesia minima Boettger, 1893, Brookesia perarmata (Angel, 1933), Brookesia stumpffi Boettger, 1894, Brookesia superciliaris (Kuhl, 1820), Brookesia therezieni Brygoo & Domergue, 1970, Brookesia thieli Brygoo & Domergue, 1969, Brotogeris chiriri (Vieillot, 1818), Brotogeris jugularis (Statius Muller, 1776), Brotogeris pyrrhoptera (Latham, 1802), Brotogeris versicolurus (Statius Muller, 1776), Brotulina fusca Fowler, 1946, Brycinus brevis (Boulenger, 1903), Brycinus imberi (Peters, 1852), Brycinus lateralis (Boulenger, 1900), Brycinus longipinnis (Günther, 1864), Brycinus longipinnis (Günther, 1864), Brycinus macrolepidotus Valenciennes, 1850, Brycinus nurse (Rüppell, 1832), Brycon alburnus (Günther, 1860), Brycon amazonicus (Spix & Agassiz, 1829), Brycon argenteus Meek & Hildebrand, 1913, Brycon atrocaudatus (Kner, 1863), Brycon behreae Hildebrand, 1938, Brycon bicolor Pellegrin, 1909, Brycon cephalus (Günther, 1869), Brycon chagrensis (Kner, 1863), Brycon coxeyi Fowler, 1943, Brycon dentex Günther, 1860, Brycon falcatus Müller & Troschel, 1844, Brycon ferox Steindachner, 1877, Brycon fowleri Dahl, 1955, Brycon guatemalensis Regan, 1908, Brycon henni Eigenmann, 1913, Brycon hilarii (Valenciennes, 1850), Brycon insignis Steindachner, 1877, Brycon labiatus Steindachner, 1879, Brycon medemi Dahl, 1960, Brycon meeki Eigenmann & Hildebrand, 1918, Brycon melanopterus (Cope, 1872), Brycon moorei Steindachner, 1878, Brycon nattereri Günther, 1864, Brycon obscurus Hildebrand, 1938, Brycon oligolepis Regan, 1913, Brycon opalinus (Cuvier, 1819), Brycon orbignyanus (Valenciennes, 1850), Brycon orthotaenia Günther, 1864, Brycon pesu Müller & Troschel, 1845, Brycon petrosus Meek & Hildebrand, 1913, Brycon polylepis Mosco Morales, 1988, Brycon rubricauda Steindachner, 1879, Brycon sinuensis Dahl, 1955, Brycon stolzmanni Steindachner, 1879, Brycon striatulus (Kner, 1863), Brycon vermelha Lima & Castro, 2000, Brycon whitei Myers & Weitzman, 1960, Bryconacidnus ellisi (Pearson, 1924), Bryconaethiops boulengeri Pellegrin, 1900, Bryconaethiops microstoma Günther, 1873, Bryconamericus agna Azpelicueta & Almirón, 2001, Bryconamericus alpha Eigenmann, 1914, Bryconamericus andresoi Román-Valencia, 2003, Bryconamericus bayano (Fink, 1976), Bryconamericus brevirostris (Günther, 1860), Bryconamericus caucanus Eigenmann, 1913, Bryconamericus cismontanus Eigenmann, 1914, Bryconamericus dahli Román-Valencia, 2000, Bryconamericus deuterodonoides Eigenmann, 1914, Bryconamericus diaphanus (Cope, 1878), Bryconamericus emperador (Eigenmann & Ogle, 1907), Bryconamericus exodon Eigenmann, 1907, Bryconamericus grosvenori Eigenmann, 1927, Bryconamericus guaytarae Eigenmann & Henn, 1914, Bryconamericus guizae Román-Valencia, 2003, Bryconamericus huilae Román-Valencia, 2003, Bryconamericus hyphesson Eigenmann, 1909, Bryconamericus icelus Dahl, 1964, Bryconamericus ichoensis Román-Valencia, 2000, Bryconamericus iheringii (Boulenger, 1887), Bryconamericus ikaa Casciotta, Almirón & Azpelicueta, 2004, Bryconamericus loisae Géry, 1964, Bryconamericus megalepis Fowler, 1941, Bryconamericus mennii Miquelarena, Protogino, Filiberto & López, 2002, Bryconamericus microcephalus (Miranda Ribeiro, 1908), Bryconamericus motatanensis Schultz, 1944, Bryconamericus multiradiatus Dahl, 1960, Bryconamericus novae Eigenmann & Henn, 1914, Bryconamericus orinocoense Román-Valencia, 2003, Bryconamericus ornaticeps Bizerril & Perez-Neto, 1995, Bryconamericus osgoodi Eigenmann & Allen, 1942, Bryconamericus pachacuti Eigenmann, 1927, Bryconamericus pectinatus Vari & Siebert, 1990, Bryconamericus peruanus (Müller & Troschel, 1845), Bryconamericus phoenicopterus (Cope, 1872), Bryconamericus plutarcoi Román-Valencia, 2001, Bryconamericus pyahu Azpelicueta, Casciotta & Almirón, 2003, Bryconamericus rubropictus (Berg, 1901), Bryconamericus scleroparius (Regan, 1908), Bryconamericus stramineus Eigenmann, 1908, Bryconamericus subtilisform Román-Valencia, 2003, Bryconamericus sylvicola Braga, 1998, Bryconamericus tenuis Bizerril & Auraujo, 1992, Bryconamericus terrabensis Meek, 1914, Bryconamericus zeteki Hildebrand, 1938, Bryconella pallidifrons (Fowler, 1946), Bryconexodon juruenae Géry, 1980, Bryconexodon trombetasi Jégu, Santos & Ferreira, 1991, Bryconops affinis (Günther, 1864), Bryconops alburnoides Kner, 1858, Bryconops caudomaculatus (Günther, 1864), Bryconops colanegra Chernoff & Machado-Allison, 1999, Bryconops colaroja Chernoff & Machado-Allison, 1999, Bryconops cyrtogaster (Norman, 1926), Bryconops disruptus Machado-Allison & Chernoff, 1997, Bryconops durbini (Eigenmann, 1908), Bryconops giacopinii (Fernández-Yépez, 1950), Bryconops gracilis (Eigenmann, 1908), Bryconops humeralis Machado-Allison, Chernoff & Buckup, 1996, Bryconops imitator Chernoff & Machado-Allison, 2002, Bryconops inpai Knöppel, Junk & Géry, 1968, Bryconops melanurus (Bloch, 1794), Bryconops transitoria (Steindachner, 1915), Bryconops vibex Machado-Allison, Chernoff & Buckup, 1996, Bubalornis niger A.Smith, 1836, Bubalus bubalis (Linnaeus, 1758), Bubo africanus (Temminck, 1821), Bubo ascalaphus Savigny, 1809, Bubo bengalensis (Franklin, 1831), Bubo bubo (Linnaeus, 1758), Bubo lacteus (Temminck, 1820), Bubo scandiacus (Linnaeus, 1758), Bubo virginianus (J.F.Gmelin, 1788), Bubulcus ibis (Linnaeus, 1758), Bucanetes mongolicus (Swinhoe, 1870), Buccochromis heterotaenia (Trewavas, 1935), Buccochromis lepturus (Regan, 1922), Buccochromis nototaenia (Boulenger, 1902), Buccochromis rhoadesii (Boulenger, 1908), Buccochromis spectabilis (Trewavas, 1935), Bucephala albeola (Linnaeus, 1758), Bucephala clangula (Linnaeus, 1758), Bucephala islandica (Gmelin, 1789), Buceros bicornis Linnaeus, 1758, Buceros hydrocorax Linnaeus, 1766, Buceros rhinoceros Linnaeus, 1758, Bucorvus abyssinicus (Boddaert, 1783), Bucorvus leadbeateri (Vigors, 1825), Budorcas taxicolor Hodgson, 1850, Bufo bankorensis Barbour, 1908, Bufo gargarizans Cantor, 1842, Bufotes viridis (Laurenti, 1768), Bugeranus carunculatus (Gmelin, 1789), Bujurquina apoparuana Kullander, 1986, Bujurquina cordemadi Kullander, 1986, Bujurquina eurhinus Kullander, 1986, Bujurquina hophrys Kullander, 1986, Bujurquina huallagae Kullander, 1986, Bujurquina mariae (Eigenmann, 1922), Bujurquina megalospilus Kullander, 1986, Bujurquina moriorum Kullander, 1986, Bujurquina ortegai Kullander, 1986, Bujurquina peregrinabunda Kullander, 1986, Bujurquina robusta Kullander, 1986, Bujurquina syspilus (Cope, 1872), Bujurquina tambopatae Kullander, 1986, Bujurquina vittata (Heckel, 1840), Bujurquina zamorensis (Regan, 1905), Bullockia maldonadoi (Eigenmann, 1920), Bunaka gyrinoides (Bleeker, 1853), Bungarus candidus (Linnaeus, 1758), Bungarus fasciatus (Schneider, 1801), Bungarus flaviceps Reinhardt, 1843, Bunocephalus aleuropsis Cope, 1870, Bunocephalus amaurus Eigenmann, 1912, Bunocephalus chamaizelus Eigenmann, 1912, Bunocephalus colombianus Eigenmann, 1912, Bunocephalus coracoideus (Cope, 1874), Bunocephalus doriae Boulenger, 1902, Bunocephalus knerii Steindachner, 1882, Bunocephalus larai Ihering, 1930, Bunocephalus verrucosus (Walbaum, 1792), Bunopus tuberculatus Blanford, 1874, Burhinus bistriatus (Wagler, 1829), Burhinus capensis (Lichtenstein, 1823), Burhinus senegalensis (Swainson, 1837), Buteo auguralis Salvadori, 1865, Buteo buteo (Linnaeus, 1758), Buteo jamaicensis (Gmelin, 1788), Buteo regalis (G.R.Gray, 1844), Buteo rufofuscus (J.R.Forster, 1798), Butis amboinensis (Bleeker, 1853), Butis butis (Hamilton, 1822), Butis gymnopomus (Bleeker, 1853), Butis humeralis (Valenciennes, 1837), Butis koilomatodon (Bleeker, 1849), Bycanistes brevis Friedmann, 1929, Bycanistes cylindricus (Temminck, 1831), Bycanistes fistulator (Cassin, 1850), Bycanistes subcylindricus (P.L.Sclater, 1871), Cacajao calvus (I.Geoffroy Saint-Hilaire, 1847), Cacatua alba (Statius Muller, 1776), Cacatua ducorpsii Pucheran, 1853, Cacatua galerita (Latham, 1790), Cacatua goffiniana C.S.Roselaar & Michaels, 2004, Cacatua goffiniana C.S.Roselaar & Michaels, 2004, Cacatua leadbeateri (Vigors, 1831), Cacatua moluccensis (Gmelin, 1788), Cacatua ophthalmica P.L.Sclater, 1864, Cacatua pastinator (Gould, 1841), Cacatua sanguinea Gould, 1843, Cacatua sulphurea (Gmelin, 1788), Cacatua tenuirostris (Kuhl, 1820), Cacicus cela (Linnaeus, 1758), Cacicus haemorrhous (Linnaeus, 1766), Caecocypris basimi Banister & Bunni, 1980, Caenotropus labyrinthicus (Kner, 1858), Caenotropus maculosus (Eigenmann, 1912), Caenotropus mestomorgmatos Vari, Castro & Raredon, 1995, Caesio caerulaurea Lacepède, 1801, Caesio cuning (Bloch, 1791), Caesio teres Seale, 1906, Caiapobrycon tucurui Malabarba & Vari, 2000, Caiman yacare (Daudin, 1801), Cairnsichthys rhombosomoides (Nichols & Raven, 1928), Calabaria reinhardtii (Schlegel, 1851), Calabaria reinhardtii (Schlegel, 1851), Calidris acuminata (Horsfield, 1821), Calidris alpina (Linnaeus, 1758), Callaeas cinereus (Gmelin, 1788), Callichthys callichthys (Linnaeus, 1758), Callichthys fabricioi Román-Valencia, Lehmann A. & Muñoz, 1999, Callichthys serralabium Lehmann A. & Reis, 2004, Callimedusa atelopoides (Duellman, Cadle & Cannatella, 1988), Callimedusa tomopterna (Cope, 1868), Callimico goeldii (Thomas, 1904), Callionymus decoratus (Gilbert, 1905), Callionymus delicatulus Smith, 1963, Callipepla californica (Shaw, 1798), Callipepla gambelii (Gambel, 1843), Callisaurus draconoides Blainville, 1835, Callithrix geoffroyi (Humboldt, 1812), Callithrix jacchus (Linnaeus, 1758), Callithrix penicillata (É.Geoffroy Saint-Hilaire, 1812), Callocephalon fimbriatum (J.Grant, 1803), Callochromis macrops (Boulenger, 1898), Callochromis melanostigma (Boulenger, 1906), Callochromis pleurospilus (Boulenger, 1906), Callopanchax occidentalis (Clausen, 1966), Calloplesiops altivelis (Steindachner, 1903), Callosciurus finlaysonii (Horsfield, 1823), Callosciurus notatus (Boddaert, 1785), Callosciurus prevostii (Desmarest, 1822), Calloselasma rhodostoma (Kuhl, 1824), Caloenas nicobarica (Linnaeus, 1758), Calomys laucha (Fischer, 1814), Calophysus macropterus (Lichtenstein, 1819), Calotes calotes (Linnaeus, 1758), Calotes emma Gray, 1845, Calotes mystaceus Duméril & Bibron, 1837, Calotes versicolor (Daudin, 1802), Calumia godeffroyi (Günther, 1877), Calumia profunda Larson & Hoese, 1980, Calumma boettgeri (Boulenger, 1888), Calumma brevicorne (Günther, 1879), Calumma brevicorne (Günther, 1879), Calumma furcifer (Vaillant & Grandidier, 1880), Calumma globifer (Günther, 1879), Calumma guillaumeti (Brygoo, Blanc & Domergue, 1974), Calumma malthe (Günther, 1879), Calumma marojezense (Brygoo, Blanc & Domergue, 1970), Calumma nasutum (Duméril & Bibron, 1836), Calumma oshaughnessyi (Günther, 1881), Calumma parsonii (Cuvier, 1825), Calypte anna (R.Lesson, 1829), Calyptocephalella gayi (Duméril & Bibron, 1841), Calyptocephalella gayi (Duméril & Bibron, 1841), Calyptomena viridis Raffles, 1822, Calyptorhynchus banksii (Latham, 1790), Camelus dromedarius Linnaeus, 1758, Campellolebias chrysolineatus Costa, Lacerda & Brasil, 1989, Campellolebias dorsimaculatus Costa, Lacerda & Brasil, 1989, Campostoma ornatum Girard, 1856, Campylomormyrus alces (Boulenger, 1920), Campylomormyrus bredoi (Poll, 1945), Campylomormyrus cassaicus (Poll, 1967), Campylomormyrus curvirostris (Boulenger, 1898), Campylomormyrus elephas (Boulenger, 1898), Campylomormyrus luapulaensis (David & Poll, 1937), Campylomormyrus mirus (Boulenger, 1898), Campylomormyrus numenius (Boulenger, 1898), Campylomormyrus phantasticus (Pellegrin, 1927), Campylomormyrus rhynchophorus (Boulenger, 1898), Campylomormyrus tamandua (Günther, 1864), Campylopterus falcatus (Swainson, 1821), Candoia aspera (Günther, 1877), Candoia bibroni (Duméril & Bibron, 1844), Candoia carinata (Schneider, 1801), Candoia paulsoni (Stull, 1956), Candoia superciliosa (Günther, 1863), Canis adustus Sundevall, 1847, Canis latrans Say, 1823, Canis lupus Linnaeus, 1758, Canis lupus Linnaeus, 1758, Canis mesomelas Schreber, 1775, Cantherhines dumerilii (Hollard, 1854), Cantherhines pullus (Ranzani, 1842), Cantherhines sandwichiensis (Quoy & Gaimard, 1824), Cantheschenia grandisquamis Hutchins, 1977, Canthidermis maculata (Bloch, 1786), Canthigaster amboinensis (Bleeker, 1864), Canthigaster bennetti (Bleeker, 1854), Canthigaster coronata (Vaillant & Sauvage, 1875), Canthigaster epilampra (Jenkins, 1903), Canthigaster jactator (Jenkins, 1901), Canthigaster janthinoptera (Bleeker, 1855), Canthigaster leoparda Lubbock & Allen, 1979, Canthigaster punctatissima (Günther, 1870), Canthigaster rivulata (Temminck & Schlegel, 1850), Canthigaster rostrata (Bloch, 1786), Canthigaster smithae Allen & Randall, 1977, Canthigaster solandri (Richardson, 1845), Canthigaster valentini (Bleeker, 1853), Capito auratus (Dumont, 1805), Capito maculicoronatus Lawrence, 1861, Capito niger (P.L.S.Müller, 1776), Capoeta aculeata (Valenciennes, 1844), Capoeta antalyensis (Battalgil, 1943), Capoeta barroisi Lortet, 1894, Capoeta buhsei Kessler, 1877, Capoeta capoeta (Güldenstädt, 1773), Capoeta damascina (Valenciennes, 1842), Capoeta fusca Nikolskii, 1897, Capoeta pestai (Pietschmann, 1933), Capoeta sieboldii (Steindachner, 1864), Capoeta tinca (Heckel, 1843), Capoeta trutta (Heckel, 1843), Capra caucasica Güldenstaedt & Pallas, 1783, Capra falconeri (Wagner, 1839), Capra hircus Linnaeus, 1758, Capra ibex Linnaeus, 1758, Capra sibirica (Pallas, 1776), Caprichromis liemi (McKaye & Mackenzie, 1982), Caprichromis orthognathus (Trewavas, 1935), Capricornis crispus (Temminck, 1836), Caprimulgus europaeus Linnaeus, 1758, Caquetaia kraussii (Steindachner, 1878), Caquetaia myersi (Schultz, 1944), Caquetaia spectabilis (Steindachner, 1875), Caquetaia umbrifera (Meek & Hildebrand, 1913), Caracal caracal (Schreber, 1776), Caracanthus maculatus (Gray, 1831), Caracanthus madagascariensis (Guichenot, 1869), Caracara plancus (J.F.Miller, 1777), Carangoides armatus (Forsskål, 1775), Carangoides armatus (Forsskål, 1775), Carangoides coeruleopinnatus (Rüppell, 1830), Carangoides ferdau (Forsskål, 1775), Caranx rhonchus Geoffroy Saint-Hilaire, 1817, Carasobarbus chantrei (Sauvage, 1882), Carasobarbus exulatus (Banister & Clarke, 1977), Carassioides acuminatus (Richardson, 1846), Carassius carassius (Linnaeus, 1758), Carassius cuvieri Temminck & Schlegel, 1846, Carcharhinus amblyrhynchos (Bleeker, 1856), Carcharhinus leucas (Valenciennes, 1839), Carcharhinus limbatus (Müller & Henle, 1839), Carcharhinus melanopterus (Quoy & Gaimard, 1824), Carcharias taurus Rafinesque, 1810, Carcharias taurus Rafinesque, 1810, Cardinalis cardinalis (Linnaeus, 1758), Cardinalis sinuatus Bonaparte, 1838, Cardiopharynx schoutedeni Poll, 1942, Carduelis carduelis (Linnaeus, 1758), Careproctus rastrinus Gilbert & Burke, 1912, Carettochelys insculpta Ramsay, 1886, Carinotetraodon imitator Britz & Kottelat, 1999, Carinotetraodon lorteti (Tirant, 1885), Carinotetraodon salivator Lim & Kottelat, 1995, Carinotetraodon travancoricus (Hora & Nair, 1941), Carlana eigenmanni (Meek, 1912), Carlastyanax aurocaudatus (Eigenmann, 1913), Carlhubbsia kidderi (Hubbs, 1936), Carlhubbsia stuarti Rosen & Bailey, 1959, Carnegiella marthae Myers, 1927, Carnegiella myersi Fernández-Yépez, 1950, Carnegiella schereri Fernández-Yépez, 1950, Carnegiella strigata (Günther, 1864), Carollia perspicillata (Linnaeus, 1758), Carphodactylus laevis Günther, 1897, Carpodacus sibiricus (Pallas, 1773), Caryothraustes canadensis (Linnaeus, 1766), Castor fiber Linnaeus, 1758, Casuarius unappendiculatus Blyth, 1860, Catamenia analis (d'Orbigny & Lafresnaye, 1837), Catathyridium jenynsii (Günther, 1862), Cathartes aura (Linnaeus, 1758), Cathartes burrovianus Cassin, 1845, Catharus ustulatus (Nuttall, 1840), Cathorops aguadulce (Meek, 1904), Cathorops dasycephalus (Günther, 1864), Cathorops fuerthii (Steindachner, 1876), Cathorops hypophthalmus (Steindachner, 1876), Cathorops melanopus (Günther, 1864), Cathorops multiradiatus (Günther, 1864), Cathorops spixii (Agassiz, 1829), Cathorops steindachneri (Gilbert & Starks, 1904), Cathorops tuyra (Meek & Hildebrand, 1923), Catlocarpio siamensis Boulenger, 1898, Catoprion mento (Cuvier, 1819), Catostomus bernardini Girard, 1856, Catostomus cahita Siebert & Minckley, 1986, Catostomus clarkii Baird & Girard, 1854, Catostomus columbianus (Eigenmann & Eigenmann, 1893), Catostomus discobolus Cope, 1871, Catostomus insignis Baird & Girard, 1854, Catostomus latipinnis Baird & Girard, 1853, Catostomus leopoldi Siebert & Minckley, 1986, Catostomus macrocheilus Girard, 1856, Catostomus microps Rutter, 1908, Catostomus nebuliferus Garman, 1881, Catostomus occidentalis Ayres, 1854, Catostomus rimiculus Gilbert & Snyder, 1898, Catostomus snyderi Gilbert, 1898, Catostomus utawana Mather, 1886, Catostomus warnerensis Snyder, 1908, Catostomus wigginsi Herre & Brock, 1936, Causus defilippii (Jan, 1863), Causus maculatus (Hallowell, 1842), Causus rhombeatus (Lichtenstein, 1823), Cavia porcellus (Linnaeus, 1758), Cebuella pygmaea (Spix, 1823), Cebus albifrons (Humboldt, 1812), Cebus capucinus (Linnaeus, 1758), Cebus olivaceus Schomburgk, 1848, Cemophora coccinea (Blumenbach, 1788), Centrarchus macropterus (Lacepède, 1801), Centriscus scutatus Linnaeus, 1758, Centrochelys sulcata (Miller, 1779), Centrochelys sulcata (Miller, 1779), Centrochir crocodili (Humboldt, 1821), Centrodoras brachiatus (Cope, 1872), Centrodoras hasemani (Steindachner, 1915), Centromochlus altae Fowler, 1945, Centromochlus concolor (Mees, 1974), Centromochlus existimatus Mees, 1974, Centromochlus heckelii (De Filippi, 1853), Centromochlus macracanthus Soares-Porto, 2000, Centromochlus megalops Kner, 1858, Centromochlus punctatus (Mees, 1974), Centromochlus reticulatus (Mees, 1974), Centromochlus romani (Mees, 1988), Centromochlus schultzi Rössel, 1962, Centropomus undecimalis (Bloch, 1792), Centropus senegalensis (Linnaeus, 1766), Centropyge acanthops (Norman, 1922), Centropyge argi Woods & Kanazawa, 1951, Centropyge aurantonotus Burgess, 1974, Centropyge bicolor (Bloch, 1787), Centropyge bispinosa (Günther, 1860), Centropyge colini Smith-Vaniz & Randall, 1974, Centropyge eibli Klausewitz, 1963, Centropyge ferrugata Randall & Burgess, 1972, Centropyge fisheri (Snyder, 1904), Centropyge flavicauda Fraser-Brunner, 1933, Centropyge heraldi Woods & Schultz, 1953, Centropyge heraldi Woods & Schultz, 1953, Centropyge interruptus (Tanaka, 1918), Centropyge joculator Smith-Vaniz & Randall, 1974, Centropyge multicolor Randall & Wass, 1974, Centropyge multispinis (Playfair, 1867), Centropyge narcosis Pyle & Randall, 1993, Centropyge nox (Bleeker, 1853), Centropyge potteri (Jordan & Metz, 1912), Centropyge shepardi Randall & Yasuda, 1979, Centropyge tibicen (Cuvier, 1831), Cephalocassis borneensis (Bleeker, 1851), Cephalopholis boenak (Bloch, 1790), Cephalopholis cruentata (Lacepède, 1802), Cephalopholis cyanostigma (Valenciennes, 1828), Cephalopholis formosa (Shaw, 1812), Cephalopholis fulva (Linnaeus, 1758), Cephalopholis miniata (Forsskål, 1775), Cephalopholis polleni (Bleeker, 1868), Cephalopholis sexmaculata (Rüppell, 1830), Cephalopholis sonnerati (Valenciennes, 1828), Cephalopholis urodeta (Forster, 1801), Cephalophus dorsalis Gray, 1846, Cephalophus natalensis A.Smith, 1834, Cephalophus niger Gray, 1846, Cephalophus rufilatus Gray, 1846, Cephalopterus ornatus E.Geoffroy Saint-Hilaire, 1809, Cephalopterus penduliger P.L.Sclater, 1859, Cephalorhynchus commersonii (Lacépède, 1804), Cephalosilurus albomarginatus (Eigenmann, 1912), Cephalosilurus apurensis (Mees, 1978), Cephalosilurus fowleri Haseman, 1911, Cephalosilurus nigricaudus (Mees, 1974), Cerastes cerastes Linnaeus, 1758, Cerastes vipera (Linnaeus, 1758), Ceratobranchia binghami Eigenmann, 1927, Ceratobranchia delotaenia Chernoff & Machado-Allison, 1990, Ceratobranchia elatior Tortonese, 1942, Ceratobranchia joanae Chernoff & Machado-Allison, 1990, Ceratobranchia obtusirostris Eigenmann, 1914, Ceratoglanis scleronema (Bleeker, 1862), Ceratogymna atrata (Temminck, 1835), Ceratogymna elata (Temminck, 1831), Ceratophora stoddartii Gray, 1834, Ceratophora tennentii Günther, 1861, Ceratophrys aurita (Raddi, 1823), Ceratophrys calcarata Boulenger, 1890, Ceratophrys cornuta (Linnaeus, 1758), Ceratophrys cranwelli Barrio, 1980, Ceratophrys joazeirensis Mercadal de Barrio, 1986, Ceratophrys ornata (Bell, 1843), Ceratophrys stolzmanni Steindachner, 1882, Ceratotherium simum (Burchell, 1817), Cercopithecus ascanius (Audebert, 1799), Cercopithecus cephus (Linnaeus, 1758), Cercopithecus diana (Linnaeus, 1758), Cercopithecus mona (Schreber, 1775), Cercopithecus neglectus Schlegel, 1876, Cercopithecus petaurista (Schreber, 1774), Cercopithecus wolfi Meyer, 1891, Cerdocyon thous (Linnaeus, 1766), Cereopsis novaehollandiae Latham, 1802, Cerrophidion godmani (Günther, 1863), Cervus elaphus Linnaeus, 1758, Cervus nippon Temminck, 1838, Ceryle rudis (Linnaeus, 1758), Cestraeus goldiei (Macleay, 1883), Cestraeus plicatilis Valenciennes, 1836, Cetopsis coecutiens (Lichtenstein, 1819), Cetopsis parma Oliveira, Vari & Ferraris, 2001, Cetopsorhamdia boquillae Eigenmann, 1922, Cetopsorhamdia iheringi Schubart & Gomes, 1959, Cetopsorhamdia insidiosa (Steindachner, 1915), Cetopsorhamdia molinae Miles, 1943, Cetopsorhamdia nasus Eigenmann & Fisher, 1916, Cetopsorhamdia orinoco Schultz, 1944, Cetopsorhamdia phantasia Stewart, 1985, Cetopsorhamdia picklei Schultz, 1944, Cetoscarus bicolor (Rüppell, 1829), Ceyx pictus (Boddaert, 1783), Chaca bankanensis Bleeker, 1852, Chaca burmensis Brown & Ferraris, 1988, Chaca chaca (Hamilton, 1822), Chacophrys pierottii (Vellard, 1948), Chaenopsis alepidota (Gilbert, 1890), Chaeropus ecaudatus (Ogilby, 1838), Chaetobranchopsis australis Eigenmann & Ward, 1907, Chaetobranchopsis orbicularis (Steindachner, 1875), Chaetobranchus flavescens Heckel, 1840, Chaetobranchus semifasciatus Steindachner, 1875, Chaetodipterus faber (Broussonet, 1782), Chaetodon adiergastos Seale, 1910, Chaetodon argentatus Smith & Radcliffe, 1911, Chaetodon aureofasciatus Macleay, 1878, Chaetodon auriga Forsskål, 1775, Chaetodon austriacus Rüppell, 1836, Chaetodon bennetti Cuvier, 1831, Chaetodon blackburnii Desjardins, 1836, Chaetodon burgessi Allen & Starck, 1973, Chaetodon capistratus Linnaeus, 1758, Chaetodon citrinellus Cuvier, 1831, Chaetodon collare Bloch, 1787, Chaetodon daedalma Jordan & Fowler, 1902, Chaetodon declivis Randall, 1975, Chaetodon decussatus Cuvier, 1829, Chaetodon dolosus Ahl, 1923, Chaetodon ephippium Cuvier, 1831, Chaetodon falcula Bloch, 1795, Chaetodon fasciatus Houttuyn, 1787, Chaetodon flavirostris Günther, 1874, Chaetodon fremblii Bennett, 1828, Chaetodon gardineri Norman, 1939, Chaetodon guentheri Ahl, 1923, Chaetodon guttatissimus Bennett, 1833, Chaetodon humeralis Günther, 1860, Chaetodon interruptus Ahl, 1923, Chaetodon kleinii Bloch, 1790, Chaetodon larvatus Cuvier, 1831, Chaetodon leucopleura Playfair, 1867, Chaetodon lineolatus Cuvier, 1831, Chaetodon lunula (Lacepède, 1802), Chaetodon lunula (Lacepède, 1802), Chaetodon lunulatus Quoy & Gaimard, 1825, Chaetodon madagaskariensis Ahl, 1923, Chaetodon melannotus Bloch & Schneider, 1801, Chaetodon melapterus Guichenot, 1863, Chaetodon mertensii Cuvier, 1831, Chaetodon mesoleucos Forsskål, 1775, Chaetodon meyeri Bloch & Schneider, 1801, Chaetodon miliaris Quoy & Gaimard, 1825, Chaetodon mitratus Günther, 1860, Chaetodon multicinctus Garrett, 1863, Chaetodon ocellatus Gronow, 1854, Chaetodon octofasciatus Bloch, 1787, Chaetodon ornatissimus Cuvier, 1831, Chaetodon paucifasciatus Ahl, 1923, Chaetodon pelewensis Kner, 1868, Chaetodon plebeius Cuvier, 1831, Chaetodon punctatofasciatus Cuvier, 1831, Chaetodon quadrimaculatus Gray, 1831, Chaetodon rafflesii Anonymous, Chaetodon rainfordi McCulloch, 1923, Chaetodon reticulatus Houttuyn, 1787, Chaetodon sedentarius Poey, 1860, Chaetodon semeion Bleeker, 1855, Chaetodon semilarvatus Cuvier, 1831, Chaetodon speculum Cuvier, 1831, Chaetodon striatus Linnaeus, 1758, Chaetodon tinkeri Schultz, 1951, Chaetodon trichrous Günther, 1874, Chaetodon trifascialis Quoy & Gaimard, 1825, Chaetodon trifasciatus Park, 1797, Chaetodon ulietensis Cuvier, 1831, Chaetodon unimaculatus Bloch, 1787, Chaetodon vagabundus Linnaeus, 1758, Chaetodon xanthocephalus Bennett, 1833, Chaetodon xanthurus Bleeker, 1857, Chaetodontoplus caeruleopunctatus Yasuda & Tominaga, 1976, Chaetodontoplus chrysocephalus (Bleeker, 1855), Chaetodontoplus chrysocephalus (Bleeker, 1855), Chaetodontoplus conspicillatus (Waite, 1900), Chaetodontoplus duboulayi (Günther, 1867), Chaetodontoplus melanosoma (Bleeker, 1853), Chaetodontoplus mesoleucus (Bloch, 1787), Chaetodontoplus personifer (McCulloch, 1914), Chaetodontoplus septentrionalis (Temminck & Schlegel, 1844), Chaetostoma anale (Fowler, 1943), Chaetostoma anomalum Regan, 1903, Chaetostoma branickii Steindachner, 1881, Chaetostoma breve Regan, 1904, Chaetostoma brevilabiatum Dahl, 1942, Chaetostoma dorsale Eigenmann, 1922, Chaetostoma guairense Steindachner, 1881, Chaetostoma jegui Rapp Py-Daniel, 1991, Chaetostoma leucomelas Eigenmann, 1918, Chaetostoma lineopunctatum Eigenmann & Allen, 1942, Chaetostoma marginatum Regan, 1904, Chaetostoma marmorescens Eigenmann & Allen, 1942, Chaetostoma microps Günther, 1864, Chaetostoma milesi Fowler, 1941, Chaetostoma patiae Fowler, 1945, Chaetostoma sovichthys Schultz, 1944, Chaetostoma stannii Lütken, 1874, Chaetostoma taczanowskii Steindachner, 1882, Chaetostoma thomsoni Regan, 1904, Chaetostoma yurubiense Ceas & Page, 1996, Chagunius baileyi Rainboth, 1986, Chagunius chagunio (Hamilton, 1822), Chagunius nicholsi (Myers, 1924), Chalarodon madagascariensis (Peters, 1854), Chalceus epakros Zanata & Toledo-Piza, 2004, Chalceus erythrurus (Cope, 1870), Chalceus guaporensis Zanata & Toledo-Piza, 2004, Chalceus macrolepidotus Cuvier, 1818, Chalceus spilogyros Zanata & Toledo-Piza, 2004, Chalcophaps indica (Linnaeus, 1758), Chalcopsitta cardinalis (G.R.Gray, 1849), Chalinochromis brichardi Poll, 1974, Chamaeleo africanus Laurenti, 1768, Chamaeleo calcaricarens Böhme, 1985, Chamaeleo calyptratus Duméril, Bibron In Duméril & Duméril, 1851, Chamaeleo chamaeleon (Linnaeus, 1758), Chamaeleo dilepis Leach, 1819, Chamaeleo dilepis Leach, 1819, Chamaeleo dilepis Leach, 1819, Chamaeleo gracilis Hallowell, 1844, Chamaeleo senegalensis Daudin, 1802, Chamaeleo zeylanicus Laurenti, 1768, Champsochromis caeruleus (Boulenger, 1908), Champsochromis spilorhynchus (Regan, 1922), Channa asiatica (Linnaeus, 1758), Channa aurantimaculata Musikasinthorn, 2000, Channa bankanensis (Bleeker, 1853), Channa barca (Hamilton, 1822), Channa bleheri Vierke, 1991, Channa burmanica Chaudhuri, 1919, Channa diplogramma (Day, 1865), Channa gachua (Hamilton, 1822), Channa harcourtbutleri (Annandale, 1918), Channa lucius (Cuvier, 1831), Channa marulioides (Bleeker, 1851), Channa melasoma (Bleeker, 1851), Channa micropeltes (Cuvier, 1831), Channa orientalis Bloch & Schneider, 1801, Channa panaw Musikasinthorn, 1998, Channa punctata (Bloch, 1793), Channa stewartii (Playfair, 1867), Channa striata (Bloch, 1793), Channallabes apus (Günther, 1873), Chanodichthys erythropterus (Basilewsky, 1855), Chanodichthys mongolicus (Basilewsky, 1855), Chanos chanos (Forsskål, 1775), Chapalichthys encaustus (Jordan & Snyder, 1899), Chapalichthys pardalis Álvarez, 1963, Chapalichthys peraticus Álvarez, 1963, Characidium alipioi Travassos, 1955, Characidium bimaculatum Fowler, 1941, Characidium boavistae Steindachner, 1915, Characidium boehlkei Géry, 1972, Characidium bolivianum Pearson, 1924, Characidium borellii (Boulenger, 1895), Characidium caucanum Eigenmann, 1912, Characidium chupa Schultz, 1944, Characidium crandellii Steindachner, 1915, Characidium declivirostre Steindachner, 1915, Characidium etheostoma Cope, 1872, Characidium fasciatum Reinhardt, 1867, Characidium gomesi Travassos, 1956, Characidium grajahuensis Travassos, 1944, Characidium hasemani Steindachner, 1915, Characidium interruptum Pellegrin, 1909, Characidium japuhybense Travassos, 1949, Characidium lanei Travassos, 1967, Characidium laterale Eigenmann, 1909, Characidium lauroi Travassos, 1949, Characidium marshi Breder, 1925, Characidium occidentale Buckup & Reis, 1997, Characidium oiticicai Travassos, 1967, Characidium orientale Buckup & Reis, 1997, Characidium pellucidum Eigenmann, 1909, Characidium phoxocephalum Eigenmann, 1912, Characidium pteroides Eigenmann, 1909, Characidium pterostictum Gomes, 1947, Characidium purpuratum Steindachner, 1882, Characidium rachovii Regan, 1913, Characidium roesseli Géry, 1965, Characidium sanctjohanni Dahl, 1960, Characidium schubarti Travassos, 1955, Characidium serrano Buckup & Reis, 1997, Characidium steindachneri Cope, 1878, Characidium stigmosum Melo & Buckup, 2002, Characidium tenue (Cope, 1894), Characidium timbuiense Travassos, 1946, Characidium vidali Travassos, 1967, Characidium zebra Eigenmann, 1909, Characodon audax Smith & Miller, 1986, Charadrius alexandrinus Linnaeus, 1758, Charax apurensis Lucena, 1987, Charax caudimaculatus Lucena, 1987, Charax condei (Géry & Knöppel, 1976), Charax gibbosus (Linnaeus, 1758), Charax hemigrammus (Eigenmann, 1912), Charax leticiae Lucena, 1987, Charax macrolepis (Kner, 1858), Charax metae Eigenmann, 1922, Charax michaeli Lucena, 1989, Charax niger Lucena, 1989, Charax notulatus Lucena, 1987, Charax pauciradiatus (Günther, 1864), Charax rupununi Eigenmann, 1912, Charax stenopterus (Cope, 1894), Charax tectifer (Cope, 1870), Charina bottae (Blainville, 1835), Charina umbratica Klauber, 1943, Charmosyna papou (Scopoli, 1786), Charmosyna rubronotata (Wallace, 1862), Chasmistes cujus Cope, 1883, Chasmistes liorus Jordan, 1878, Chasmocranus brevior Eigenmann, 1912, Chasmocranus chimantanus Inger, 1956, Chasmocranus longior Eigenmann, 1912, Chasmocranus peruanus Eigenmann & Pearson, 1942, Chasmocranus quadrizonatus Pearson, 1937, Chasmocranus rosae Eigenmann, 1922, Chaudhuria caudata Annandale, 1918, Chaudhuria fusipinnis Kottelat & Britz, 2000, Cheilinus chlorourus (Bloch, 1791), Cheilinus fasciatus (Bloch, 1791), Cheilinus lunulatus (Forsskål, 1775), Cheilinus oxycephalus Bleeker, 1853, Cheilinus undulatus Rüppell, 1835, Cheilochromis euchilus (Trewavas, 1935), Cheilodipterus quinquelineatus Cuvier, 1828, Cheimarrichthys fosteri Haast, 1874, Cheirodon australe Eigenmann, 1928, Cheirodon galusdai Eigenmann, 1928, Cheirodon ibicuhiensis Eigenmann, 1915, Cheirodon interruptus (Jenyns, 1842), Cheirodon jaguaribensis Fowler, 1941, Cheirodon kiliani Campos, 1982, Cheirodon ortegai Vari & Géry, 1980, Cheirodon parahybae Eigenmann, 1915, Cheirodon pisciculus Girard, 1855, Cheirodontops geayi Schultz, 1944, Cheirogaleus medius É.Geoffroy Saint-Hilaire, 1812, Chela cachius (Hamilton, 1822), Chelaethiops bibie (Joannis, 1835), Chelaethiops congicus (Nichols & Griscom, 1917), Chelaethiops elongatus Boulenger, 1899, Chelaethiops minutus (Boulenger, 1906), Chelaethiops rukwaensis (Ricardo, 1939), Chelictinia riocourii (Temminck, 1821), Chelmon marginalis Richardson, 1842, Chelmon muelleri Klunzinger, 1879, Chelmon rostratus (Linnaeus, 1758), Chelmonops truncatus (Kner, 1859), Chelodina expansa Gray, 1857, Chelodina longicollis (Shaw, 1794), Chelodina mccordi Rhodin, 1994, Chelodina novaeguineae Boulenger, 1888, Chelodina oblonga Gray, Chelodina oblonga Gray, Chelodina oblonga Gray, Chelodina parkeri Rhodin & Mittermeier, 1976, Chelon labrosus (Risso, 1827), Chelon macrolepis (Smith, 1846), Chelonia mydas Gray, 1831, Chelonodontops patoca (Hamilton, 1822), Chelonoidis chilensis (Gray, 1870), Chelonoidis chilensis (Gray, 1870), Chelonoidis nigra (Quoy & Gaimard, 1824), Chelus fimbriata (Schneider, 1783), Chelydra acutirostris Peters, 1862, Chen caerulescens (Linnaeus, 1758), Chen caerulescens (Linnaeus, 1758), Chen canagica (Sevastianov, 1802), Chen rossii (Cassin, 1861), Chenonetta jubata (Latham, 1802), Chersina angulata (Schweigger, 1812), Chetia brevis Jubb, 1968, Chetia flaviventris Trewavas, 1961, Chetia gracilis (Greenwood, 1984), Chetia mola Balon & Stewart, 1983, Chilabothrus angulifer (Cocteau & Bibron, 1840), Chilabothrus chrysogaster (Cope, 1871), Chilabothrus fordii (Günther, 1861), Chilabothrus gracilis Fischer, 1888, Chilabothrus striatus (Fischer, 1856), Chilabothrus subflavus (Stejneger, 1901), Chilatherina alleni Price, 1997, Chilatherina axelrodi Allen, 1979, Chilatherina bleheri Allen, 1985, Chilatherina bulolo (Whitley, 1938), Chilatherina campsi (Whitley, 1957), Chilatherina crassispinosa (Weber, 1913), Chilatherina fasciata (Weber, 1913), Chilatherina pricei Allen & Renyaan, 1996, Chilobrycon deuterodon Géry & de Rham, 1981, Chilochromis duponti Boulenger, 1902, Chilodus fritillus Vari & Ortega, 1997, Chilodus gracilis Isbrücker & Nijssen, 1988, Chilodus punctatus Müller & Troschel, 1844, Chilodus zunevei Puyo, 1946, Chiloglanis asymetricaudalis De Vos, 1993, Chiloglanis batesii Boulenger, 1904, Chiloglanis bifurcus Jubb & Le Roux, 1969, Chiloglanis cameronensis Boulenger, 1904, Chiloglanis congicus Boulenger, 1920, Chiloglanis disneyi Trewavas, 1974, Chiloglanis macropterus Poll & Stewart, 1975, Chiloglanis neumanni Boulenger, 1911, Chiloglanis occidentalis Pellegrin, 1933, Chiloglanis paratus Crass, 1960, Chiloglanis polypogon Roberts, 1989, Chiloglanis pretoriae Van Der Horst, 1931, Chiloglanis somereni Whitehead, 1958, Chiloglanis trilobatus Seegers, 1996, Chilomycterus antennatus (Cuvier, 1816), Chilomycterus antillarum Jordan & Rutter, 1897, Chilomycterus schoepfii (Walbaum, 1792), Chilomycterus schoepfii (Walbaum, 1792), Chiloscyllium hasseltii Bleeker, 1852, Chiloscyllium indicum (Gmelin, 1789), Chiloscyllium plagiosum (Anonymous & Bennett, 1830), Chiloscyllium punctatum Müller & Henle, 1838, Chilotilapia rhoadesii Boulenger, 1908, Chinchilla chinchilla (Lichtenstein, 1829), Chinchilla chinchilla (Lichtenstein, 1829), Chinchilla lanigera Bennett, 1829, Chinchilla lanigera Bennett, 1829, Chioglossa lusitanica Bocage, 1864, Chirolophis nugator (Jordan & Williams, 1895), Chiromantis petersii Boulenger, 1882, Chiromantis rufescens (Günther, 1869), Chironectes minimus (Zimmermann, 1780), Chironius carinatus (Linnaeus, 1758), Chironius exoletus (Linnaeus, 1758), Chironius fuscus (Linnaeus, 1758), Chironius multiventris Schmidt & Walker, 1943, Chironius scurrulus (Wagler, 1824), Chiropotes chiropotes (Humboldt, 1811), Chirostoma aculeatum Barbour, 1973, Chirostoma arge (Jordan & Snyder, 1899), Chirostoma attenuatum Meek, 1902, Chirostoma bartoni Jordan & Evermann, 1896, Chirostoma chapalae Jordan & Snyder, 1899, Chirostoma consocium Jordan & Hubbs, 1919, Chirostoma estor Jordan, 1880, Chirostoma grandocule (Steindachner, 1894), Chirostoma humboldtianum (Valenciennes, 1835), Chirostoma jordani Woolman, 1894, Chirostoma labarcae Meek, 1902, Chirostoma lucius Boulenger, 1900, Chirostoma melanoccus Álvarez, 1963, Chirostoma patzcuaro Meek, 1902, Chirostoma promelas Jordan & Snyder, 1899, Chirostoma riojai Solórzano & López, 1966, Chirostoma sphyraena Boulenger, 1900, Chiroxiphia caudata (Shaw, 1793), Chiroxiphia lanceolata (Wagler, 1830), Chiroxiphia pareola (Linnaeus, 1766), Chitala blanci (d'Aubenton, 1965), Chitala chitala (Hamilton, 1822), Chitala lopis (Bleeker, 1851), Chitonotus pugetensis (Steindachner, 1876), Chitra chitra Nutaphand, 1986, Chitra indica (Gray, 1831), Chlamydogobius eremius (Zietz, 1896), Chlamydosaurus kingii Gray, 1825, Chlamydoselachus anguineus Garman, 1884, Chloephaga poliocephala P.L.Sclater, 1857, Chloris chloris, Chlorocebus aethiops (Linnaeus, 1758), Chlorocebus pygerythrus (F.Cuvier, 1821), Chlorocebus sabaeus (Linnaeus, 1766), Chlorochrysa calliparaea (Tschudi, 1844), Chlorophanes spiza (Linnaeus, 1758), Chlorophonia cyanea (Thunberg, 1822), Chloropsis aurifrons (Temminck, 1829), Chloropsis cochinchinensis (Gmelin, 1789), Chloropsis cyanopogon (Temminck, 1830), Chloropsis sonnerati Jardine & Selby, 1827, Chloroscombrus chrysurus (Linnaeus, 1766), Chlorospingus flavigularis (P.L.Sclater, 1852), Chlorostilbon notatus (G.C.Reich, 1793), Choerodon anchorago (Bloch, 1791), Choerodon fasciatus (Günther, 1867), Choerodon jordani (Snyder, 1908), Choloepus didactylus (Linnaeus, 1758), Choloepus hoffmanni Peters, 1858, Chologaster cornuta Agassiz, 1853, Chondrodactylus angulifer Peters, 1870, Chondrodactylus bibronii (Smith, 1846), Chondrodactylus turneri (Gray, 1864), Chondrohierax uncinatus (Temminck, 1822), Chondrostoma holmwoodii (Boulenger, 1896), Chondrostoma kinzelbachi Krupp, 1985, Chondrostoma knerii Heckel, 1843, Chondrostoma kubanicum Berg, 1914, Chondrostoma nasus (Linnaeus, 1758), Chondrostoma oxyrhynchum Kessler, 1877, Chondrostoma phoxinus Heckel, 1843, Chondrostoma regium (Heckel, 1843), Chondrostoma scodrense Elvira, 1987, Chondrostoma soetta Bonaparte, 1840, Chondrostoma vardarense Karaman, 1928, Chondrostoma variabile Yakovlev, 1870, Choridactylus multibarbus Richardson, 1848, Christinus marmoratus (Gray, 1845), Chromidotilapia guntheri (Sauvage, 1882), Chromidotilapia kingsleyae Boulenger, 1898, Chromidotilapia melaniae Lamboj, 2003, Chromidotilapia mrac Lamboj, 2002, Chromileptes altivelis (Valenciennes, 1828), Chromis acares Randall & Swerdloff, 1973, Chromis agilis Smith, 1960, Chromis analis (Cuvier, 1830), Chromis atrilobata Gill, 1862, Chromis atripectoralis Welander & Schultz, 1951, Chromis atripes Fowler & Bean, 1928, Chromis cyanea (Poey, 1860), Chromis dimidiata (Klunzinger, 1871), Chromis flavicauda (Günther, 1880), Chromis fumea (Tanaka, 1917), Chromis hanui Randall & Swerdloff, 1973, Chromis iomelas Jordan & Seale, 1906, Chromis klunzingeri Whitley, 1929, Chromis lepidolepis Bleeker, 1877, Chromis limbaughi Greenfield & Woods, 1980, Chromis margaritifer Fowler, 1946, Chromis multilineata (Guichenot, 1853), Chromis multilineata (Guichenot, 1853), Chromis nigrura Smith, 1960, Chromis nitida (Whitley, 1928), Chromis opercularis (Günther, 1867), Chromis retrofasciata Weber, 1913, Chromis scotti Emery, 1968, Chromis vanderbilti (Fowler, 1941), Chromis viridis (Cuvier, 1830), Chromis weberi Fowler & Bean, 1928, Chromis xanthura (Bleeker, 1854), Chromobotia macracanthus (Bleeker, 1852), Chrosomus cumberlandensis (Starnes & Starnes, 1978), Chrosomus eos Cope, 1861, Chrosomus erythrogaster (Rafinesque, 1820), Chrosomus erythrogaster (Rafinesque, 1820), Chrosomus saylori (Skelton, 2001), Chrosomus tennesseensis (Starnes & Jenkins, 1988), Chrysemys picta (Schneider, 1783), Chrysemys picta (Schneider, 1783), Chrysichthys aluuensis Risch, 1985, Chrysichthys auratus (Geoffroy Saint-Hilaire, 1809), Chrysichthys brachynema Boulenger, 1900, Chrysichthys brevibarbis (Boulenger, 1899), Chrysichthys cranchii (Leach, 1818), Chrysichthys helicophagus Roberts & Stewart, 1976, Chrysichthys laticeps Pellegrin, 1932, Chrysichthys longibarbis (Boulenger, 1899), Chrysichthys maurus (Valenciennes, 1840), Chrysichthys nigrodigitatus (Lacepède, 1803), Chrysichthys wagenaari Boulenger, 1899, Chrysichthys walkeri Günther, 1899, Chrysiptera bleekeri (Fowler & Bean, 1928), Chrysiptera cyanea (Quoy & Gaimard, 1825), Chrysiptera flavipinnis (Allen & Robertson, 1974), Chrysiptera galba (Allen & Randall, 1974), Chrysiptera hemicyanea (Weber, 1913), Chrysiptera leucopoma (Cuvier, 1830), Chrysiptera parasema (Fowler, 1918), Chrysiptera rex (Snyder, 1909), Chrysiptera rollandi (Whitley, 1961), Chrysiptera springeri (Allen & Lubbock, 1976), Chrysiptera starcki (Allen, 1973), Chrysiptera talboti (Allen, 1975), Chrysiptera taupou (Jordan & Seale, 1906), Chrysiptera traceyi (Woods & Schultz, 1960), Chrysiptera tricincta (Allen & Randall, 1974), Chrysobrycon hesperus (Böhlke, 1958), Chrysobrycon myersi (Weitzman & Thomerson, 1970), Chrysococcyx cupreus (Shaw, 1792), Chrysocyon brachyurus (Illiger, 1815), Chrysolophus amherstiae (Leadbeater, 1829), Chrysolophus pictus (Linnaeus, 1758), Chrysomus icterocephalus (Linnaeus, 1766), Chrysomus icterocephalus (Linnaeus, 1766), Chrysopelea ornata (Shaw, 1802), Chrysopelea paradisi Boie, 1827, Cichla intermedia Machado-Allison, 1971, Cichla monoculus Agassiz, 1831, Cichla orinocensis Humboldt, 1821, Cichla temensis Humboldt, 1821, Cichlasoma amazonarum Kullander, 1983, Cichlasoma araguaiense Kullander, 1983, Cichlasoma beani (Jordan, 1889), Cichlasoma bocourti (Vaillant & Pellegrin, 1902), Cichlasoma boliviense Kullander, 1983, Cichlasoma festae (Boulenger, 1899), Cichlasoma geddesi (Regan, 1905), Cichlasoma grammodes Taylor & Miller, 1980, Cichlasoma istlanum (Jordan & Snyder, 1899), Cichlasoma orientale Kullander, 1983, Cichlasoma orinocense Kullander, 1983, Cichlasoma paranaense Kullander, 1983, Cichlasoma sanctifranciscense Kullander, 1983, Cichlasoma taenia (Bennett, 1831), Cichlasoma trimaculatum (Günther, 1867), Cicinnurus regius (Linnaeus, 1758), Ciconia ciconia (Linnaeus, 1758), Cinetodus froggatti (Ramsay & Ogilby, 1886), Cinnyricinclus leucogaster (Boddaert, 1783), Cinnyris venustus (Shaw, 1799), Circaetus gallicus (Gmelin, 1788), Cirrhilabrus adornatus Randall & Kunzmann, 1998, Cirrhilabrus balteatus Randall, 1988, Cirrhilabrus bathyphilus Randall & Nagareda, 2002, Cirrhilabrus condei Allen & Randall, 1996, Cirrhilabrus cyanopleura (Bleeker, 1851), Cirrhilabrus cyanopleura (Bleeker, 1851), Cirrhilabrus earlei Randall & Pyle, 2001, Cirrhilabrus exquisitus Smith, 1957, Cirrhilabrus filamentosus (Klausewitz, 1976), Cirrhilabrus flavidorsalis Randall & Carpenter, 1980, Cirrhilabrus joanallenae Allen, 2000, Cirrhilabrus jordani Snyder, 1904, Cirrhilabrus katherinae Randall, 1992, Cirrhilabrus laboutei Randall & Lubbock, 1982, Cirrhilabrus lanceolatus Randall & Masuda, 1991, Cirrhilabrus lineatus Randall & Lubbock, 1982, Cirrhilabrus lubbocki Randall & Carpenter, 1980, Cirrhilabrus lunatus Randall & Masuda, 1991, Cirrhilabrus luteovittatus Randall, 1988, Cirrhilabrus melanomarginatus Randall & Shen, 1978, Cirrhilabrus punctatus Randall & Kuiter, 1989, Cirrhilabrus pylei Allen & Randall, 1996, Cirrhilabrus rhomboidalis Randall, 1988, Cirrhilabrus roseafascia Randall & Lubbock, 1982, Cirrhilabrus rubrimarginatus Randall, 1992, Cirrhilabrus rubripinnis Randall & Carpenter, 1980, Cirrhilabrus rubrisquamis Randall & Emery, 1983, Cirrhilabrus rubriventralis Springer & Randall, 1974, Cirrhilabrus scottorum Randall & Pyle, 1989, Cirrhilabrus solorensis Bleeker, 1853, Cirrhilabrus tonozukai Allen & Kuiter, 1999, Cirrhinus caudimaculatus (Fowler, 1934), Cirrhinus cirrhosus (Bloch, 1795), Cirrhinus fulungee (Sykes, 1839), Cirrhinus inornatus Roberts, 1997, Cirrhinus microlepis Sauvage, 1878, Cirrhinus molitorella (Valenciennes, 1844), Cirrhinus mrigala (Hamilton, 1822), Cirrhinus reba (Hamilton, 1822), Cirrhitichthys falco Randall, 1963, Cirrhitichthys oxycephalus (Bleeker, 1855), Cirrhitops fasciatus (Bennett, 1828), Cirrhitus pinnulatus (Forster, 1801), Cirrhitus rivulatus Valenciennes, 1846, Cirripectes polyzona (Bleeker, 1868), Cirripectes stigmaticus Strasburg & Schultz, 1953, Citharichthys gilberti Jenkins & Evermann, 1889, Citharichthys spilopterus Günther, 1862, Citharichthys stampflii (Steindachner, 1894), Citharichthys uhleri Jordan, 1889, Citharinops distichodoides (Pellegrin, 1919), Citharinus citharus (Geoffroy Saint-Hilaire, 1809), Citharinus congicus Boulenger, 1897, Citharinus eburneensis Daget, 1962, Citharinus gibbosus Boulenger, 1899, Citharinus latus Müller & Troschel, 1844, Citharinus macrolepis Boulenger, 1899, Civettictis civetta (Schreber, 1776), Clangula hyemalis (Linnaeus, 1758), Claravis pretiosa (Ferrari-Pérez, 1886), Clariallabes longicauda (Boulenger, 1902), Clariallabes melas (Boulenger, 1887), Clariallabes platyprosopos Jubb, 1965, Clarias alluaudi Boulenger, 1906, Clarias angolensis Steindachner, 1866, Clarias anguillaris (Linnaeus, 1758), Clarias batu Lim & Ng, 1999, Clarias buettikoferi Steindachner, 1894, Clarias buthupogon Sauvage, 1879, Clarias camerunensis Lönnberg, 1895, Clarias cavernicola Trewavas, 1936, Clarias ebriensis Pellegrin, 1920, Clarias gabonensis Günther, 1867, Clarias gariepinus (Burchell, 1822), Clarias jaensis Boulenger, 1909, Clarias leiacanthus Bleeker, 1851, Clarias liocephalus Boulenger, 1898, Clarias macrocephalus Günther, 1864, Clarias meladerma Bleeker, 1846, Clarias ngamensis Castelnau, 1861, Clarias nieuhofii Valenciennes, 1840, Clarias nigromarmoratus Poll, 1967, Clarias pachynema Boulenger, 1903, Clarias platycephalus Boulenger, 1902, Clarias stappersii Boulenger, 1915, Clarias submarginatus Peters, 1882, Clarias theodorae Weber, 1897, Clarias werneri Boulenger, 1906, Clarotes laticeps (Rüppell, 1829), Claudius angustatus Boulenger, 1889, Cleidopus gloriamaris De Vis, 1882, Cleithracara maronii (Steindachner, 1881), Clelia clelia (Daudin, 1803), Clemmys guttata (Schneider, 1792), Clepticus parrae (Bloch & Schneider, 1801), Clinocottus embryum (Jordan & Starks, 1895), Clupea harengus Linnaeus, 1758, Clupea pallasii Valenciennes, 1847, Clupeacharax anchoveoides Pearson, 1924, Clupisoma garua (Hamilton, 1822), Clupisoma prateri Hora, 1937, Cnemaspis africana (Werner, 1896), Cnemidophorus gularis Baird & Girard, 1852, Cnemidophorus lemniscatus (Linnaeus, 1758), Cnesterodon brevirostratus Rosa & Costa, 1993, Cnesterodon decemmaculatus (Jenyns, 1842), Cnesterodon septentrionalis Rosa & Costa, 1993, Cnidoglanis macrocephalus (Valenciennes, 1840), Cobitis arachthosensis Economidis & Nalbant, 1996, Cobitis bilineata Canestrini, 1865, Cobitis biwae Jordan & Snyder, 1901, Cobitis calderoni Băcescu, 1962, Cobitis choii Kim & Son, 1984, Cobitis dolichorhynchus Nichols, 1918, Cobitis elazigensis Coad & Sarieyyüpoglu, 1988, Cobitis elongata Heckel & Kner, 1858, Cobitis elongatoides Băcescu & Mayer, 1969, Cobitis fahirae Erk'akan, Atalay-Ekmekçi & Nalbant, 1998, Cobitis hellenica Economidis & Nalbant, 1996, Cobitis laoensis (Sauvage, 1878), Cobitis lutheri Rendahl, 1935, Cobitis maroccana Pellegrin, 1929, Cobitis matsubarai Okada & Ikeda, 1939, Cobitis melanoleuca Nichols, 1925, Cobitis pacifica Kim, Park & Nalbant, 1999, Cobitis paludica (de Buen, 1930), Cobitis satunini Gladkov, 1935, Cobitis simplicispina Hankó, 1925, Cobitis sinensis Sauvage & Dabry de Thiersant, 1874, Cobitis striata Ikeda, 1936, Cobitis strumicae Karaman, 1955, Cobitis taenia Linnaeus, 1758, Cobitis takatsuensis Mizuno, 1970, Cobitis tanaitica Băcescu & Mayer, 1969, Cobitis tetralineata Kim, Park & Nalbant, 1999, Cobitis trichonica Stephanidis, 1974, Cobitis vardarensis Karaman, 1928, Cobitis vettonica Doadrio & Perdices, 1997, Coccopygia melanotis (Temminck, 1823), Coccyzus lansbergi Bonaparte, 1850, Cochlearius cochlearius (Linnaeus, 1766), Cochranella granulosa (Taylor, 1949), Cociella crocodila (Tilesius, 1814), Coelognathus flavolineatus (Schlegel, 1837), Coelognathus radiatus (Boie, 1827), Coelognathus subradiatus (Schlegel, 1837), Coendou prehensilis (Linnaeus, 1758), Coereba flaveola (Linnaeus, 1758), Colaptes auratus (Linnaeus, 1758), Coleonyx brevis Stejneger, 1893, Coleonyx elegans Gray, 1845, Coleonyx mitratus (Peters, 1863), Coleonyx variegatus (Baird, 1858), Colibri coruscans (Gould, 1846), Colinus cristatus (Linnaeus, 1766), Colisa chuna (Hamilton, 1822), Colisa fasciata (Bloch & Schneider, 1801), Colisa labiosa (Day, 1877), Colisa lalia (Hamilton, 1822), Colisa lalia (Hamilton, 1822), Colobus guereza Rüppell, 1835, Coloeus dauuricus (Pallas, 1776), Coloeus monedula (Linnaeus, 1758), Cololabis saira (Brevoort, 1856), Colomesus asellus (Müller & Troschel, 1849), Colomesus psittacus (Bloch & Schneider, 1801), Colopus wahlbergii Peters, 1869, Colpichthys hubbsi Crabtree, 1989, Colpichthys regis (Jenkins & Evermann, 1889), Coluber constrictor Linnaeus, 1758, Coluber flagellum Shaw, 1802, Coluber lateralis (Hallowell, 1853), Coluber taeniatus (Hallowell, 1852), Columba iriditorques Cassin, 1856, Columba larvata Temminck, 1809, Columba livia J.F.Gmelin, 1789, Columba palumboides (Hume, 1873), Columba palumbus Linnaeus, 1758, Columbina buckleyi (P.L.Sclater & Salvin, 1877), Columbina minuta (Linnaeus, 1766), Columbina passerina (Linnaeus, 1758), Columbina talpacoti (Temminck, 1810), Compsura gorgonae (Evermann & Goldsborough, 1909), Compsura heterura Eigenmann, 1915, Conger conger (Linnaeus, 1758), Conger myriaster (Brevoort, 1856), Conger verreauxi Kaup, 1856, Congrogadus subducens (Richardson, 1843), Coniophanes fissidens (Günther, 1858), Connochaetes gnou (Zimmermann, 1780), Connochaetes gnou (Zimmermann, 1780), Connochaetes taurinus (Burchell, 1823), Conophis lineatus (Duméril, Bibron & Duméril, 1854), Conorhynchos conirostris (Valenciennes, 1840), Conraua alleni (Barbour & Loveridge, 1927), Conraua crassipes (Buchholz & Peters, 1875), Conraua robusta Nieden, 1908, Cookeolus japonicus (Cuvier, 1829), Copadichromis azureus Konings, 1990, Copadichromis borleyi (Iles, 1960), Copadichromis chrysonotus (Boulenger, 1908), Copadichromis geertsi Konings, 1999, Copadichromis jacksoni (Iles, 1960), Copadichromis mloto (Iles, 1960), Copadichromis pleurostigma (Trewavas, 1935), Copadichromis pleurostigmoides (Iles, 1960), Copadichromis quadrimaculatus (Regan, 1922), Copadichromis trimaculatus (Iles, 1960), Copadichromis verduyni Konings, 1990, Copadichromis virginalis (Iles, 1960), Copeina guttata (Steindachner, 1876), Copeina osgoodi Eigenmann, 1922, Copella arnoldi (Regan, 1912), Copella carsevennensis (Regan, 1912), Copella compta (Myers, 1927), Copella eigenmanni (Regan, 1912), Copella metae (Eigenmann, 1914), Copella nattereri (Steindachner, 1876), Copella nigrofasciata (Meinken, 1952), Copella vilmae Géry, 1963, Cophosaurus texanus Troschel, 1852, Cophyla milloti (Guibé, 1950), Copsychus malabaricus (Scopoli, 1786), Copsychus saularis (Linnaeus, 1758), Coptobrycon bilineatus (Ellis, 1911), Coptostomabarbus wittei David & Poll, 1937, Coracias abyssinicus Hermann, 1783, Coracias caudatus Linnaeus, 1766, Coracias caudatus Linnaeus, 1766, Coracias cyanogaster Cuvier, 1816, Coracias garrulus Linnaeus, 1758, Coracias naevius Daudin, 1800, Coracopsis nigra (Linnaeus, 1758), Coradion altivelis McCulloch, 1916, Coragyps atratus (Bechstein, 1793), Coralliozetus rosenblatti Stephens, 1963, Corallus annulatus (Cope, 1875), Corallus batesii (Gray, 1860), Corallus caninus (Linnaeus, 1758), Corallus cookii Gray, 1842, Corallus grenadensis (Barbour, 1914), Corallus ruschenbergerii (Cope, 1875), Cordylancistrus daguae (Eigenmann, 1912), Cordylancistrus perijae Pérez & Provenzano, 1996, Cordylancistrus platyrhynchus (Fowler, 1943), Cordylancistrus torbesensis (Schultz, 1944), Coregonus albellus Fatio, 1890, Coregonus albula (Linnaeus, 1758), Coregonus alpenae (Koelz, 1924), Coregonus alpinus Fatio, 1885, Coregonus arenicolus Kottelat, 1997, Coregonus autumnalis (Pallas, 1776), Coregonus bavaricus Hofer, 1909, Coregonus candidus Goll, 1883, Coregonus fera Jurine, 1825, Coregonus heglingus Schinz, 1822, Coregonus hoyi (Milner, 1874), Coregonus hoyi (Milner, 1874), Coregonus huntsmani Scott, 1987, Coregonus johannae (Wagner, 1910), Coregonus kiyi (Koelz, 1921), Coregonus laurettae Bean, 1881, Coregonus lavaretus (Linnaeus, 1758), Coregonus lucinensis Thienemann, 1933, Coregonus macrophthalmus Nüsslin, 1882, Coregonus maraena (Bloch, 1779), Coregonus migratorius (Georgi, 1775), Coregonus muksun (Pallas, 1814), Coregonus nasus (Pallas, 1776), Coregonus nigripinnis (Milner, 1874), Coregonus nigripinnis (Milner, 1874), Coregonus nobilis Haack, 1882, Coregonus oxyrinchus (Linnaeus, 1758), Coregonus palaea Cuvier, 1829, Coregonus peled (Gmelin, 1789), Coregonus pidschian (Gmelin, 1789), Coregonus pollan Thompson, 1835, Coregonus reighardi (Koelz, 1924), Coregonus renke (Schrank, 1783), Coregonus sardinella Valenciennes, 1848, Coregonus suidteri Fatio, 1885, Coregonus wartmanni (Bloch, 1784), Coregonus zenithicus (Jordan & Evermann, 1909), Coregonus zuerichensis Nüsslin, 1882, Coregonus zugensis Nüsslin, 1882, Corematodus shiranus Boulenger, 1897, Corematodus taeniatus Trewavas, 1935, Coreoleuciscus splendidus Mori, 1935, Coreoperca herzi Herzenstein, 1896, Coreoperca kawamebari (Temminck & Schlegel, 1843), Coreoperca whiteheadi Boulenger, 1900, Coris aurilineata Randall & Kuiter, 1982, Coris aygula Lacepède, 1801, Coris ballieui Vaillant & Sauvage, 1875, Coris cuvieri (Bennett, 1831), Coris dorsomacula Fowler, 1908, Coris flavovittata (Bennett, 1828), Coris formosa (Bennett, 1830), Coris gaimard (Quoy & Gaimard, 1824), Coris picta (Bloch & Schneider, 1801), Coris venusta Vaillant & Sauvage, 1875, Cornufer guentheri (Boulenger, 1884), Cornufer vitiensis (Girard, 1853), Corumbataia cuestae Britski, 1997, Corumbataia tocantinensis Britski, 1997, Corvus albus Statius Muller, 1776, Corvus brachyrhynchos C.L.Brehm, 1822, Corvus corax Linnaeus, 1758, Corvus corone Linnaeus, 1758, Corvus frugilegus Linnaeus, 1758, Corydoras acrensis Nijssen, 1972, Corydoras acutus Cope, 1872, Corydoras adolfoi Burgess, 1982, Corydoras agassizii Steindachner, 1876, Corydoras albolineatus Knaack, 2004, Corydoras amapaensis Nijssen, 1972, Corydoras ambiacus Cope, 1872, Corydoras approuaguensis Nijssen & Isbrücker, 1983, Corydoras araguaiaensis Sands, 1990, Corydoras arcuatus Elwin, 1938, Corydoras areio Knaack, 2000, Corydoras armatus (Günther, 1868), Corydoras atropersonatus Weitzman & Nijssen, 1970, Corydoras aurofrenatus Eigenmann & Kennedy, 1903, Corydoras axelrodi Rössel, 1962, Corydoras baderi Geisler, 1969, Corydoras bicolor Nijssen & Isbrücker, 1967, Corydoras bifasciatus Nijssen, 1972, Corydoras bilineatus Knaack, 2002, Corydoras blochi Nijssen, 1971, Corydoras boehlkei Nijssen & Isbrücker, 1982, Corydoras boesemani Nijssen & Isbrücker, 1967, Corydoras bondi Gosline, 1940, Corydoras breei Isbrücker & Nijssen, 1992, Corydoras brevirostris Fraser-Brunner, 1947, Corydoras burgessi Axelrod, 1987, Corydoras carlae Nijssen & Isbrücker, 1983, Corydoras caudimaculatus Rössel, 1961, Corydoras cervinus Rössel, 1962, Corydoras cochui Myers & Weitzman, 1954, Corydoras concolor Weitzman, 1961, Corydoras condiscipulus Nijssen & Isbrücker, 1980, Corydoras coppenamensis Nijssen, 1970, Corydoras crimmeni Grant, 1997, Corydoras cruziensis Knaack, 2002, Corydoras delphax Nijssen & Isbrücker, 1983, Corydoras difluviatilis Britto & Castro, 2002, Corydoras ehrhardti Steindachner, 1910, Corydoras elegans Steindachner, 1876, Corydoras ellisae Gosline, 1940, Corydoras ephippifer Nijssen, 1972, Corydoras evelynae Rössel, 1963, Corydoras filamentosus Nijssen & Isbrücker, 1983, Corydoras flaveolus Ihering, 1911, Corydoras fowleri Böhlke, 1950, Corydoras garbei Miranda Ribeiro, 1937, Corydoras geoffroy Lacepède, 1803, Corydoras geryi Nijssen & Isbrücker, 1983, Corydoras gracilis Nijssen & Isbrücker, 1976, Corydoras griseus Holly, 1940, Corydoras guapore Knaack, 1961, Corydoras guianensis Nijssen, 1970, Corydoras habrosus Weitzman, 1960, Corydoras hastatus Eigenmann & Eigenmann, 1888, Corydoras heteromorphus Nijssen, 1970, Corydoras imitator Nijssen & Isbrücker, 1983, Corydoras julii Steindachner, 1906, Corydoras kanei Grant, 1998, Corydoras lamberti Nijssen & Isbrücker, 1986, Corydoras latus Pearson, 1924, Corydoras leopardus Myers, 1933, Corydoras leucomelas Eigenmann & Allen, 1942, Corydoras loretoensis Nijssen & Isbrücker, 1986, Corydoras loxozonus Nijssen & Isbrücker, 1983, Corydoras mamore Knaack, 2002, Corydoras melanistius Regan, 1912, Corydoras melanotaenia Regan, 1912, Corydoras melini Lönnberg & Rendahl, 1930, Corydoras metae Eigenmann, 1914, Corydoras multimaculatus Steindachner, 1907, Corydoras nanus Nijssen & Isbrücker, 1967, Corydoras napoensis Nijssen & Isbrücker, 1986, Corydoras nattereri Steindachner, 1876, Corydoras negro Knaack, 2004, Corydoras oiapoquensis Nijssen, 1972, Corydoras ornatus Nijssen & Isbrücker, 1976, Corydoras osteocarus Böhlke, 1951, Corydoras oxyrhynchus Nijssen & Isbrücker, 1967, Corydoras paleatus (Jenyns, 1842), Corydoras paleatus (Jenyns, 1842), Corydoras panda Nijssen & Isbrücker, 1971, Corydoras pantanalensis Knaack, 2001, Corydoras parallelus Burgess, 1993, Corydoras pastazensis Weitzman, 1963, Corydoras pinheiroi Dinkelmeyer, 1995, Corydoras polystictus Regan, 1912, Corydoras potaroensis Myers, 1927, Corydoras punctatus (Bloch, 1794), Corydoras pygmaeus Knaack, 1966, Corydoras rabauti La Monte, 1941, Corydoras reticulatus Fraser-Brunner, 1938, Corydoras robineae Burgess, 1983, Corydoras sanchesi Nijssen & Isbrücker, 1967, Corydoras saramaccensis Nijssen, 1970, Corydoras semiaquilus Weitzman, 1964, Corydoras septentrionalis Gosline, 1940, Corydoras serratus Sands, 1995, Corydoras seussi Dinkelmeyer, 1996, Corydoras similis Hieronimus, 1991, Corydoras simulatus Weitzman & Nijssen, 1970, Corydoras sipaliwini Hoedeman, 1965, Corydoras sodalis Nijssen & Isbrücker, 1986, Corydoras solox Nijssen & Isbrücker, 1983, Corydoras spilurus Norman, 1926, Corydoras stenocephalus Eigenmann & Allen, 1942, Corydoras sterbai Knaack, 1962, Corydoras surinamensis Nijssen, 1970, Corydoras sychri Weitzman, 1960, Corydoras treitlii Steindachner, 1906, Corydoras trilineatus Cope, 1872, Corydoras tukano Britto & Lima, 2003, Corydoras undulatus Regan, 1912, Corydoras virginiae Burgess, 1993, Corydoras vittatus Nijssen, 1971, Corydoras weitzmani Nijssen, 1971, Corydoras xinguensis Nijssen, 1972, Corydoras zygatus Eigenmann & Allen, 1942, Corymbophanes andersoni Eigenmann, 1909, Corymbophanes kaiei Armbruster & Sabaj Pérez, 2000, Corynopoma riisei Gill, 1858, Coryphaena hippurus Linnaeus, 1758, Coryphopterus glaucofraenum Gill, 1863, Coryphopterus personatus (Jordan & Thompson, 1905), Coryphospingus cucullatus (P.L.Statius Müller, 1776), Corythaeola cristata (Vieillot, 1816), Corythaixoides concolor (A.Smith, 1833), Corythaixoides leucogaster (Ruppell, 1842), Corythoichthys flavofasciatus (Rüppell, 1838), Corythoichthys intestinalis (Ramsay, 1881), Corytophanes cristatus (Merrem, 1820), Corytophanes hernandesii (Wiegmann, 1831), Coscoroba coscoroba (Molina, 1782), Cosmochilus harmandi Sauvage, 1878, Cossypha albicapillus (Vieillot, 1818), Cossypha heuglini Hartlaub, 1866, Cotinga cayana (Linnaeus, 1766), Cotinga cotinga (Linnaeus, 1766), Cottus gobio Linnaeus, 1758, Coturnix japonica Temminck & Schlegel, 1849, Cranoglanis bouderius (Richardson, 1846), Craterocephalus stercusmuscarum (Günther, 1867), Craterocephalus stramineus (Whitley, 1950), Craugastor punctariolus (Peters, 1863), Crax alberti Fraser, 1852, Crax alector Linnaeus, 1766, Crax rubra Linnaeus, 1758, Creagrutus affinis Steindachner, 1880, Creagrutus amoenus Fowler, 1943, Creagrutus anary Fowler, 1913, Creagrutus atratus Vari & Harold, 2001, Creagrutus atrisignum Myers, 1927, Creagrutus barrigai Vari & Harold, 2001, Creagrutus beni Eigenmann, 1911, Creagrutus bolivari Schultz, 1944, Creagrutus brevipinnis Eigenmann, 1913, Creagrutus britskii Vari & Harold, 2001, Creagrutus calai Vari & Harold, 2001, Creagrutus caucanus Eigenmann, 1913, Creagrutus changae Vari & Harold, 2001, Creagrutus cochui Géry, 1964, Creagrutus cracentis Vari & Harold, 2001, Creagrutus figueiredoi Vari & Harold, 2001, Creagrutus flavescens Vari & Harold, 2001, Creagrutus gephyrus Böhlke & Saul, 1975, Creagrutus gracilis Vari & Harold, 2001, Creagrutus gyrospilus Vari & Harold, 2001, Creagrutus hildebrandi Schultz, 1944, Creagrutus holmi Vari & Harold, 2001, Creagrutus hysginus Harold, Vari, Machado-Allison & Provenzano, 1994, Creagrutus ignotus Vari & Harold, 2001, Creagrutus kunturus Vari, Harold & Ortega, 1995, Creagrutus lassoi Vari & Harold, 2001, Creagrutus lepidus Vari, Harold, Lasso & Machado-Allison, 1993, Creagrutus machadoi Vari & Harold, 2001, Creagrutus magdalenae Eigenmann, 1913, Creagrutus magoi Vari & Harold, 2001, Creagrutus manu Vari & Harold, 2001, Creagrutus maracaiboensis (Schultz, 1944), Creagrutus maxillaris (Myers, 1927), Creagrutus melanzonus Eigenmann, 1909, Creagrutus melasma Vari, Harold & Taphorn, 1994, Creagrutus menezesi Vari & Harold, 2001, Creagrutus meridionalis Vari & Harold, 2001, Creagrutus mucipu Vari & Harold, 2001, Creagrutus muelleri (Günther, 1859), Creagrutus nigrostigmatus Dahl, 1960, Creagrutus occidaneus Vari & Harold, 2001, Creagrutus ortegai Vari & Harold, 2001, Creagrutus ouranonastes Vari & Harold, 2001, Creagrutus paraguayensis Mahnert & Géry, 1988, Creagrutus paralacus Harold & Vari, 1994, Creagrutus pearsoni Mahnert & Géry, 1988, Creagrutus peruanus (Steindachner, 1876), Creagrutus petilus Vari & Harold, 2001, Creagrutus phasma Myers, 1927, Creagrutus pila Vari & Harold, 2001, Creagrutus planquettei Géry & Renno, 1989, Creagrutus provenzanoi Vari & Harold, 2001, Creagrutus runa Vari & Harold, 2001, Creagrutus saxatilis Vari & Harold, 2001, Creagrutus seductus Vari & Harold, 2001, Creagrutus taphorni Vari & Harold, 2001, Creagrutus tuyuka Vari & Lima, 2003, Creagrutus ungulus Vari & Harold, 2001, Creagrutus vexillapinnus Vari & Harold, 2001, Creagrutus xiphos Vari & Harold, 2001, Creagrutus zephyrus Vari & Harold, 2001, Crenicara latruncularium Kullander & Staeck, 1990, Crenicara punctulatum (Günther, 1863), Crenichthys baileyi (Gilbert, 1893), Crenicichla acutirostris Günther, 1862, Crenicichla adspersa Heckel, 1840, Crenicichla albopunctata Pellegrin, 1904, Crenicichla alta Eigenmann, 1912, Crenicichla anthurus Cope, 1872, Crenicichla britskii Kullander, 1982, Crenicichla cametana Steindachner, 1911, Crenicichla celidochilus Casciotta, 1987, Crenicichla cincta Regan, 1905, Crenicichla compressiceps Ploeg, 1986, Crenicichla coppenamensis Ploeg, 1987, Crenicichla cyanonotus Cope, 1870, Crenicichla cyclostoma Ploeg, 1986, Crenicichla edithae Ploeg, 1991, Crenicichla frenata Gill, 1858, Crenicichla geayi Pellegrin, 1903, Crenicichla haroldoi Luengo & Britski, 1974, Crenicichla heckeli Ploeg, 1989, Crenicichla hemera Kullander, 1990, Crenicichla hummelincki Ploeg, 1991, Crenicichla igara Lucena & Kullander, 1992, Crenicichla iguassuensis Haseman, 1911, Crenicichla inpa Ploeg, 1991, Crenicichla isbrueckeri Ploeg, 1991, Crenicichla jaguarensis Haseman, 1911, Crenicichla jegui Ploeg, 1986, Crenicichla johanna Heckel, 1840, Crenicichla jupiaensis Britski & Luengo, 1968, Crenicichla labrina (Spix & Agassiz, 1831), Crenicichla lacustris (Castelnau, 1855), Crenicichla lenticulata Heckel, 1840, Crenicichla lepidota Heckel, 1840, Crenicichla lucius Cope, 1870, Crenicichla lugubris Heckel, 1840, Crenicichla macrophthalma Heckel, 1840, Crenicichla marmorata Pellegrin, 1904, Crenicichla menezesi Ploeg, 1991, Crenicichla minuano Lucena & Kullander, 1992, Crenicichla missioneira Lucena & Kullander, 1992, Crenicichla mucuryna Ihering, 1914, Crenicichla multispinosa Pellegrin, 1903, Crenicichla nickeriensis Ploeg, 1987, Crenicichla niederleinii (Holmberg, 1891), Crenicichla notophthalmus Regan, 1913, Crenicichla pellegrini Ploeg, 1991, Crenicichla percna Kullander, 1991, Crenicichla phaiospilus Kullander, 1991, Crenicichla proteus Cope, 1872, Crenicichla pydanielae Ploeg, 1991, Crenicichla regani Ploeg, 1989, Crenicichla reticulata (Heckel, 1840), Crenicichla santosi Ploeg, 1991, Crenicichla saxatilis (Linnaeus, 1758), Crenicichla scottii (Eigenmann, 1907), Crenicichla sedentaria Kullander, 1986, Crenicichla semicincta Steindachner, 1892, Crenicichla semifasciata (Heckel, 1840), Crenicichla sipaliwini Ploeg, 1987, Crenicichla stocki Ploeg, 1991, Crenicichla strigata Günther, 1862, Crenicichla sveni Ploeg, 1991, Crenicichla tendybaguassu Lucena & Kullander, 1992, Crenicichla ternetzi Norman, 1926, Crenicichla tigrina Ploeg, Jégu & Ferreira, 1991, Crenicichla urosema Kullander, 1990, Crenicichla virgatula Ploeg, 1991, Crenicichla vittata Heckel, 1840, Crenicichla wallacii Regan, 1905, Crenimugil heterocheilos (Bleeker, 1855), Crenuchus spilurus Günther, 1863, Crex crex (Linnaeus, 1758), Cricetomys gambianus Waterhouse, 1840, Cricetulus barabensis (Pallas, 1773), Cricetus cricetus (Linnaeus, 1758), Crinifer piscator (Boddaert, 1783), Crinifer zonurus (Ruppell, 1835), Crithagra atrogularis (A.Smith, 1836), Crithagra citrinelloides (Rüppell, 1840), Crithagra citrinipectus (Clancey & Lawson, 1960), Crithagra dorsostriata Reichenow, 1887, Crithagra flaviventris (J.F.Gmelin, 1789), Crithagra gularis (A.Smith, 1836), Crithagra leucopygia Sundevall, 1850, Crithagra mozambica (P.L.Statius Müller, 1776), Crithagra striolata (Rüppell, 1840), Crithagra sulphurata (Linnaeus, 1766), Crocidura sibirica Dukelsky, 1930, Crocodylus intermedius (Graves, 1819), Crocodylus johnsoni Krefft, 1873, Crocodylus johnsoni Krefft, 1873, Crocodylus mindorensis Schmidt, 1935, Crocodylus moreletii (Duméril & Bibron, 1851), Crocodylus niloticus Laurenti, 1768, Crocodylus novaeguineae Schmidt, 1928, Crocodylus porosus Schneider, 1801, Crocodylus rhombifer (Cuvier, 1807), Crocodylus siamensis Schneider, 1801, Crocuta crocuta (Erxleben, 1777), Cromeria nilotica Boulenger, 1901, Crossarchus obscurus F.G.Cuvier, 1825, Crossocheilus atrilimes Kottelat, 2000, Crossocheilus burmanicus Hora, 1936, Crossocheilus cobitis (Bleeker, 1854), Crossocheilus langei Bleeker, 1860, Crossocheilus latius (Hamilton, 1822), Crossocheilus nigriloba Popta, 1904, Crossocheilus oblongus Kuhl & Van Hasselt, 1823, Crossocheilus oblongus Kuhl & Van Hasselt, 1823, Crossocheilus oblongus Kuhl & Van Hasselt, 1823, Crossocheilus reticulatus (Fowler, 1934), Crossoloricaria bahuaja Chang & Castro, 1999, Crossoloricaria cephalaspis Isbrücker, 1979, Crossoloricaria rhami Isbrücker & Nijssen, 1983, Crossoloricaria venezuelae (Schultz, 1944), Crossosalarias macrospilus Smith-Vaniz & Springer, 1971, Crotalus adamanteus Stejneger, 1895, Crotalus aquilus Klauber, 1952, Crotalus atrox Baird & Girard, 1853, Crotalus atrox Baird & Girard, 1853, Crotalus catalinensis Cliff, 1954, Crotalus cerastes Hallowell, 1854, Crotalus durissus Linnaeus, 1758, Crotalus enyo Cope, 1861, Crotalus horridus Linnaeus, 1758, Crotalus lepidus Kennicott, 1861, Crotalus mitchellii (Cope, 1861), Crotalus oreganus Klauber, 1949, Crotalus polystictus (Cope, 1865), Crotalus pricei Van Denburgh, 1895, Crotalus ravus Cope, 1865, Crotalus ravus Cope, 1865, Crotalus ruber Cope, 1892, Crotalus ruber Cope, 1892, Crotalus scutulatus Kennicott, 1861, Crotalus simus Latreille, 1801, Crotalus stephensi Klauber, 1930, Crotalus tigris Kennicott In Baird, 1859, Crotalus triseriatus Wagler, 1830, Crotalus viridis Rafinesque, 1818, Crotalus willardi Meek, 1905, Crotaphopeltis hotamboeia (Laurenti, 1768), Crotaphytus bicinctores Smith & Tanner, 1972, Crotaphytus collaris (Say, 1822), Crotaphytus insularis Van Denburgh & Slevin, 1921, Cruziohyla calcarifer (Boulenger, 1902), Cruziohyla craspedopus (Funkhouser, 1957), Cruziohyla craspedopus (Funkhouser, 1957), Cryptoblepharus boutonii (Des Jardin, 1831), Cryptocentrus caeruleomaculatus (Herre, 1933), Cryptocentrus cinctus (Herre, 1936), Cryptocentrus cyanotaenia (Bleeker, 1853), Cryptocentrus fasciatus (Playfair, 1867), Cryptocentrus inexplicatus (Herre, 1934), Cryptocentrus leptocephalus Bleeker, 1876, Cryptocentrus pavoninoides (Bleeker, 1849), Cryptomys hottentotus (Lesson, 1826), Cryptoprocta ferox Bennett, 1833, Cryptospiza reichenovii (Hartlaub, 1874), Cryptospiza salvadorii Reichenow, 1892, Crystallaria asprella (Jordan, 1878), Cteniloricaria maculata (Boeseman, 1971), Cteniloricaria platystoma (Günther, 1868), Ctenobrycon alleni (Eigenmann & McAtee, 1907), Ctenobrycon hauxwellianus (Cope, 1870), Ctenobrycon spilurus (Valenciennes, 1850), Ctenochaetus binotatus Randall, 1955, Ctenochaetus hawaiiensis Randall, 1955, Ctenochaetus marginatus (Valenciennes, 1835), Ctenochaetus striatus (Quoy & Gaimard, 1825), Ctenochaetus strigosus (Bennett, 1828), Ctenochaetus tominiensis Randall, 1955, Ctenochaetus truncatus Randall & Clements, 2001, Ctenochromis benthicola (Matthes, 1962), Ctenochromis horei (Günther, 1894), Ctenogobiops tangaroai Lubbock & Polunin, 1977, Ctenogobius shufeldti (Jordan & Eigenmann, 1887), Ctenolucius beani (Fowler, 1907), Ctenolucius hujeta (Valenciennes, 1850), Ctenopharynx intermedius (Günther, 1864), Ctenopharynx nitidus (Trewavas, 1935), Ctenopharynx pictus (Trewavas, 1935), Ctenopoma acutirostre Pellegrin, 1899, Ctenopoma kingsleyae Günther, 1896, Ctenopoma maculatum Thominot, 1886, Ctenopoma multispine Peters, 1844, Ctenopoma muriei (Boulenger, 1906), Ctenopoma nigropannosum Reichenow, 1875, Ctenopoma ocellatum Pellegrin, 1899, Ctenopoma petherici Günther, 1864, Ctenopoma weeksii Boulenger, 1896, Ctenops nobilis McClelland, 1845, Ctenosaura alfredschmidti Köhler, 1995, Ctenosaura bakeri Stejneger, 1901, Ctenosaura clarki Bailey, 1928, Ctenosaura conspicuosa Dickerson, 1919, Ctenosaura defensor (Cope, 1866), Ctenosaura flavidorsalis Köhler & Klemmer, 1994, Ctenosaura hemilopha (Cope, 1863), Ctenosaura palearis Stejneger, 1899, Ctenosaura pectinata (Wiegmann, 1834), Ctenosaura quinquecarinata (Gray, 1842), Ctenosaura quinquecarinata (Gray, 1842), Ctenosaura quinquecarinata (Gray, 1842), Ctenosaura similis (Gray, 1831), Cualac tessellatus Miller, 1956, Cubanichthys cubensis (Eigenmann, 1903), Cubanichthys pengelleyi (Fowler, 1939), Culter alburnus Basilewsky, 1855, Culter recurviceps (Richardson, 1846), Cuniculus paca (Linnaeus, 1766), Cuniculus paca (Linnaeus, 1766), Cunningtonia longiventralis Boulenger, 1906, Cuon alpinus (Pallas, 1811), Cuora amboinensis Gray, 1856, Cuora flavomarginata (Gray, 1863), Cuora galbinifrons Bourret, 1939, Cuora mouhotii (Gray, 1862), Cuora mouhotii (Gray, 1862), Cuora pani Song, 1984, Cuora trifasciata Gray, 1856, Cuora trifasciata Gray, 1856, Curimata acutirostris Vari & Reis, 1995, Curimata aspera Günther, 1868, Curimata cerasina Vari, 1984, Curimata cisandina (Allen, 1942), Curimata cyprinoides (Linnaeus, 1766), Curimata incompta Vari, 1984, Curimata inornata Vari, 1989, Curimata knerii Steindachner, 1876, Curimata macrops Eigenmann & Eigenmann, 1889, Curimata mivartii Steindachner, 1878, Curimata ocellata Eigenmann & Eigenmann, 1889, Curimata roseni Vari, 1989, Curimata vittata (Kner, 1858), Curimatella alburna (Müller & Troschel, 1844), Curimatella dorsalis (Eigenmann & Eigenmann, 1889), Curimatella immaculata (Fernández-Yépez, 1948), Curimatella lepidura (Eigenmann & Eigenmann, 1889), Curimatella meyeri (Steindachner, 1882), Curimatopsis crypticus Vari, 1982, Curimatopsis evelynae Géry, 1964, Curimatopsis macrolepis (Steindachner, 1876), Curimatopsis microlepis Eigenmann & Eigenmann, 1889, Curimatopsis myersi Vari, 1982, Cyanerpes caeruleus (Linnaeus, 1758), Cyanerpes cyaneus (Linnaeus, 1766), Cyanerpes nitidus (Hartlaub, 1847), Cyanocharax dicropotamicus Malabarba & Weitzman, 2003, Cyanocharax itaimbe Malabarba & Weitzman, 2003, Cyanocharax lepiclastus Malabarba, Weitzman & Casciotta, 2003, Cyanocompsa cyanoides (Lafresnaye, 1847), Cyanocorax mystacalis (Sparre, 1835), Cyanocorax yncas (Boddaert, 1783), Cyanoliseus patagonus (Vieillot, 1818), Cyanopica cyanus (Pallas, 1776), Cyanopica cyanus (Pallas, 1776), Cyanoramphus auriceps (Kuhl, 1820), Cyanoramphus novaezelandiae (Sparrman, 1787), Cyathochromis obliquidens Trewavas, 1935, Cyathopharynx furcifer (Boulenger, 1898), Cyclanorbis elegans (Gray, 1869), Cyclanorbis senegalensis (Duméril & Bibron, 1835), Cyclemys atripons Iverson & Mccord, 1997, Cyclemys dentata (Gray, 1831), Cyclemys pulchristriata Fritz, Gaulke & Lehr, 1997, Cycleptus elongatus (Lesueur, 1817), Cycleptus meridionalis Burr & Mayden, 1999, Cyclichthys orbicularis (Bloch, 1785), Cyclocheilichthys apogon (Valenciennes, 1842), Cyclocheilichthys heteronema (Bleeker, 1854), Cyclocheilichthys janthochir (Bleeker, 1854), Cyclocheilichthys lagleri Sontirat, 1989, Cycloderma aubryi (Duméril, 1856), Cycloderma frenatum Peters, 1854, Cyclopes didactylus (Linnaeus, 1758), Cyclophiops major (Günther, 1858), Cyclophiops multicinctus (Roux, 1907), Cyclopsitta diophthalma (Hombron & Jacquinot, 1841), Cyclopterus lumpus Linnaeus, 1758, Cyclura cornuta (Bonnaterre, 1789), Cyclura nubila (Gray, 1831), Cygnus atratus (Latham, 1790), Cygnus buccinator Richardson, 1831, Cygnus columbianus (Ord, 1815), Cygnus cygnus (Linnaeus, 1758), Cygnus melancoryphus (Molina, 1782), Cygnus melancoryphus (Molina, 1782), Cygnus olor (Gmelin, 1789), Cymatogaster aggregata Gibbons, 1854, Cynodon gibbus (Agassiz, 1829), Cynodon meionactis Géry, Le Bail & Keith, 1999, Cynodon septenarius Toledo-Piza, 2000, Cynoglossus arel (Bloch & Schneider, 1801), Cynoglossus cynoglossus (Hamilton, 1822), Cynoglossus feldmanni (Bleeker, 1854), Cynoglossus lingua Hamilton, 1822, Cynoglossus microlepis (Bleeker, 1851), Cynolebias gilbertoi Costa, 1998, Cynolebias leptocephalus Costa & Brasil, 1993, Cynomys leucurus Merriam, 1890, Cynomys ludovicianus (Ord, 1815), Cynopoecilus intimus Costa, 2002, Cynopoecilus melanotaenia (Regan, 1912), Cynopoecilus nigrovittatus Costa, 2002, Cynopotamus argenteus (Valenciennes, 1836), Cynopotamus atratoensis (Eigenmann, 1907), Cynopotamus bipunctatus Pellegrin, 1909, Cynopotamus essequibensis Eigenmann, 1912, Cynopotamus gouldingi Menezes, 1987, Cynopotamus juruenae Menezes, 1987, Cynopotamus kincaidi (Schultz, 1950), Cynopotamus magdalenae (Steindachner, 1879), Cynopotamus tocantinensis Menezes, 1987, Cynopotamus venezuelae (Schultz, 1944), Cynops cyanurus Liu, Hu & Yang, 1962, Cynops ensicauda (Hallowell, 1861), Cynops orientalis (David, 1873), Cynops pyrrhogaster (Boie, 1826), Cynops pyrrhogaster (Boie, 1826), Cynoscion nebulosus (Cuvier, 1830), Cynotilapia afra (Günther, 1894), Cynotilapia axelrodi Burgess, 1976, Cynotilapia pulpican Tawil, 2002, Cyornis poliogenys W.E.Brooks, 1880, Cypho purpurascens (De Vis, 1884), Cyphocharax abramoides (Kner, 1858), Cyphocharax festivus Vari, 1992, Cyphocharax gilbert (Quoy & Gaimard, 1824), Cyphocharax gillii (Eigenmann & Kennedy, 1903), Cyphocharax gouldingi Vari, 1992, Cyphocharax helleri (Steindachner, 1910), Cyphocharax laticlavius Vari & Blackledge, 1996, Cyphocharax leucostictus (Eigenmann & Eigenmann, 1889), Cyphocharax magdalenae (Steindachner, 1878), Cyphocharax meniscaprorus Vari, 1992, Cyphocharax mestomyllon Vari, 1992, Cyphocharax microcephalus (Eigenmann & Eigenmann, 1889), Cyphocharax modestus (Fernández-Yépez, 1948), Cyphocharax multilineatus (Myers, 1927), Cyphocharax nagelii (Steindachner, 1881), Cyphocharax nigripinnis Vari, 1992, Cyphocharax notatus (Steindachner, 1908), Cyphocharax oenas Vari, 1992, Cyphocharax pantostictos Vari & Barriga S., 1990, Cyphocharax platanus (Günther, 1880), Cyphocharax plumbeus (Eigenmann & Eigenmann, 1889), Cyphocharax punctatus (Vari & Nijssen, 1986), Cyphocharax saladensis (Meinken, 1933), Cyphocharax santacatarinae (Fernández-Yépez, 1948), Cyphocharax signatus Vari, 1992, Cyphocharax spilotus (Vari, 1987), Cyphocharax spiluropsis (Eigenmann & Eigenmann, 1889), Cyphocharax spilurus (Günther, 1864), Cyphocharax stilbolepis Vari, 1992, Cyphocharax vanderi (Britski, 1980), Cyphocharax vexillapinnus Vari, 1992, Cyphocharax voga (Hensel, 1870), Cyphotilapia frontosa (Boulenger, 1906), Cyphotilapia gibberosa Takahashi & Nakaya, 2003, Cyprichromis leptosoma (Boulenger, 1898), Cyprichromis pavo Büscher, 1994, Cyprinella alvarezdelvillari Contreras-Balderas & Lozano-Vilano, 1994, Cyprinella bocagrande (Chernoff & Miller, 1982), Cyprinella caerulea (Jordan, 1877), Cyprinella callisema (Jordan, 1877), Cyprinella callistia (Jordan, 1877), Cyprinella callitaenia (Bailey & Gibbs, 1956), Cyprinella camura (Jordan & Meek, 1884), Cyprinella chloristia (Jordan & Brayton, 1878), Cyprinella formosa (Girard, 1856), Cyprinella garmani (Jordan, 1885), Cyprinella gibbsi (Howell & Williams, 1971), Cyprinella labrosa (Cope, 1870), Cyprinella leedsi (Fowler, 1942), Cyprinella lepida Girard, 1856, Cyprinella nivea (Cope, 1870), Cyprinella ornata (Girard, 1856), Cyprinella panarcys (Hubbs & Miller, 1978), Cyprinella pyrrhomelas (Cope, 1870), Cyprinella rutila (Girard, 1856), Cyprinella stigmatura (Jordan, 1877), Cyprinella trichroistia (Jordan & Gilbert, 1878), Cyprinella whipplei Girard, 1856, Cyprinella xaenura (Jordan, 1877), Cyprinella xanthicara (Minckley & Lytle, 1969), Cyprinion acinaces Banister & Clarke, 1977, Cyprinion kais Heckel, 1843, Cyprinion macrostomum Heckel, 1843, Cyprinion mhalensis Alkahem & Behnke, 1983, Cyprinion microphthalmum (Day, 1880), Cyprinion semiplotum (McClelland, 1839), Cyprinion tenuiradius Heckel, 1847, Cyprinion watsoni (Day, 1872), Cyprinodon albivelis Minckley & Miller, 2002, Cyprinodon alvarezi Miller, 1976, Cyprinodon artifrons Hubbs, 1936, Cyprinodon atrorus Miller, 1968, Cyprinodon beltrani Álvarez, 1949, Cyprinodon bifasciatus Miller, 1968, Cyprinodon bobmilleri Lozano-Vilano & Contreras-Balderas, 1999, Cyprinodon bondi Myers, 1935, Cyprinodon bovinus Baird & Girard, 1853, Cyprinodon ceciliae Lozano-Vilano & Contreras-Balderas, 1993, Cyprinodon elegans Baird & Girard, 1853, Cyprinodon esconditus Strecker, 2002, Cyprinodon eximius Girard, 1859, Cyprinodon fontinalis Smith & Miller, 1980, Cyprinodon higuey Rodriguez & Smith, 1990, Cyprinodon hubbsi Carr, 1936, Cyprinodon inmemoriam Lozano-Vilano & Contreras-Balderas, 1993, Cyprinodon labiosus Humphries & Miller, 1981, Cyprinodon longidorsalis Lozano-Vilano & Contreras-Balderas, 1993, Cyprinodon macrolepis Miller, 1976, Cyprinodon maya Humphries & Miller, 1981, Cyprinodon meeki Miller, 1976, Cyprinodon nazas Miller, 1976, Cyprinodon nichollsi Smith, 1989, Cyprinodon pachycephalus Minckley & Minckley, 1986, Cyprinodon pecosensis Echelle & Echelle, 1978, Cyprinodon pisteri Miller & Minckley, 2002, Cyprinodon riverendi (Poey, 1860), Cyprinodon simus Humphries & Miller, 1981, Cyprinodon tularosa Miller & Echelle, 1975, Cyprinodon verecundus Humphries, 1984, Cyprinodon veronicae Lozano-Vilano & Contreras-Balderas, 1993, Cyprinus intha Annandale, 1918, Cyrtocara moorii Boulenger, 1902, Cyrtodactylus brevipalmatus (Smith, 1923), Cyrtodactylus consobrinus (Peters, 1871), Cyrtodactylus elok Dring, 1979, Cyrtodactylus fumosus (Müller, 1895), Cyrtodactylus intermedius Stuart & Emmett, 2006, Cyrtodactylus louisiadensis (De Vis, 1892), Cyrtodactylus marmoratus Gray, 1831, Cyrtodactylus peguensis (Boulenger, 1893), Cyrtodactylus pubisulcus Inger, 1958, Cyrtodactylus quadrivirgatus Taylor, 1962, Cyrtopodion scabrum (Heyden, 1827), Daboia palaestinae (Werner, 1938), Daboia russelii (Shaw & Nodder, 1797), Dacelo leachii Vigors & Horsfield, 1827, Dacelo novaeguineae (Hermann, 1783), Dacnis cayana (Linnaeus, 1766), Dacnis lineata (J.F.Gmelin, 1789), Dactylopsila trivirgata Gray, 1858, Dactyloptena orientalis (Cuvier, 1829), Dactylopus dactylopus (Valenciennes, 1837), Daector gerringi (Rendahl, 1941), Daector quadrizonatus (Eigenmann, 1922), Daector reticulata (Günther, 1864), Dallia admirabilis Chereshnev, 1980, Dama dama (Linnaeus, 1758), Damaliscus pygargus (Pallas, 1767), Danakilia franchettii (Vinciguerra, 1931), Danio albolineatus (Blyth, 1860), Danio albolineatus (Blyth, 1860), Danio choprai Hora, 1928, Danio dangila (Hamilton, 1822), Danio kerri Smith, 1931, Danio kyathit Fang, 1998, Danio nigrofasciatus (Day, 1870), Danio quangbinhensis (Nguyen, Le & Nguyen, 1999), Danio roseus Fang & Kottelat, 2000, Danionella translucida Roberts, 1986, Dario dario (Hamilton, 1822), Dario hysginon Kullander & Britz, 2002, Dascyllus albisella Gill, 1862, Dascyllus aruanus (Linnaeus, 1758), Dascyllus carneus Fischer, 1885, Dascyllus flavicaudus Randall & Allen, 1977, Dascyllus marginatus (Rüppell, 1829), Dascyllus melanurus Bleeker, 1854, Dascyllus reticulatus (Richardson, 1846), Dascyllus trimaculatus (Rüppell, 1829), Dasyatis akajei (Müller & Henle, 1841), Dasyatis americana Hildebrand & Schroeder, 1928, Dasyatis centroura (Mitchill, 1815), Dasyatis kuhlii (Müller & Henle, 1841), Dasyatis margarita (Günther, 1870), Dasyatis pastinaca (Linnaeus, 1758), Dasyatis sabina (Lesueur, 1824), Dasyatis zugei (Müller & Henle, 1841), Dasyloricaria capetensis (Meek & Hildebrand, 1913), Dasyloricaria filamentosa (Steindachner, 1878), Dasyloricaria seminuda (Eigenmann & Vance, 1912), Dasypeltis atra Sternfeld, 1912, Dasypeltis inornata Smith, 1849, Dasypeltis medici Bianconi, 1859, Dasypeltis scabra (Linnaeus, 1758), Dasyprocta azarae Lichtenstein, 1823, Dasyprocta cristata (É.Geoffroy Saint-Hilaire, 1803), Dasyprocta leporina (Linnaeus, 1758), Dasyprocta punctata Gray, 1842, Dasypus novemcinctus Linnaeus, 1758, Dasyurus maculatus (Kerr, 1792), Datnioides microlepis Bleeker, 1854, Datnioides polota (Hamilton, 1822), Datnioides pulcher (Kottelat, 1998), Datnioides undecimradiatus (Roberts & Kottelat, 1994), Daubentonia madagascariensis (Gmelin, 1788), Decodon puellaris (Poey, 1860), Deinagkistrodon acutus (Günther, 1888), Deirochelys reticularia (Latreille, 1801), Dekeyseria amazonica Rapp Py-Daniel, 1985, Dekeyseria brachyura (Kner, 1854), Dekeyseria niveata (La Monte, 1929), Dekeyseria picta (Kner, 1854), Dekeyseria pulcher (Steindachner, 1915), Dekeyseria scaphirhyncha (Kner, 1854), Delphinapterus leucas (Pallas, 1776), Deltistes luxatus (Cope, 1879), Delturus angulicauda (Steindachner, 1877), Delturus carinotus (La Monte, 1933), Dendragapus obscurus (Say, 1823), Dendrelaphis caudolineatus (Gray, 1834), Dendrelaphis formosus (Boie, 1827), Dendrelaphis pictus (Gmelin, 1789), Dendrelaphis punctulatus (Gray, 1826), Dendroaspis angusticeps (Smith, 1849), Dendroaspis jamesoni (Traill, 1843), Dendroaspis polylepis Günther, 1864, Dendroaspis viridis (Hallowell, 1844), Dendrobates leucomelas Steindachner, 1864, Dendrobates tinctorius (Schneider, 1799), Dendrobates tinctorius (Schneider, 1799), Dendrobates tinctorius (Schneider, 1799), Dendrobates truncatus (Cope, 1861), Dendrochirus barberi (Steindachner, 1900), Dendrochirus bellus (Jordan & Hubbs, 1925), Dendrochirus biocellatus (Fowler, 1938), Dendrochirus brachypterus (Cuvier, 1829), Dendrochirus zebra (Cuvier, 1829), Dendrocygna viduata (Linnaeus, 1766), Dendrohyrax dorsalis (Fraser, 1854), Dendrolagus inustus Müller, 1840, Dendrolagus matschiei Forster & Rothschild, 1907, Dendrophidion dendrophis (Schlegel, 1837), Dendropsophus ebraccatus (Cope, 1874), Dendropsophus ebraccatus (Cope, 1874), Dendropsophus leucophyllatus (Beireis, 1783), Dendropsophus leucophyllatus (Beireis, 1783), Dendropsophus marmoratus (Laurenti, 1768), Dendropsophus marmoratus (Laurenti, 1768), Dendropsophus marmoratus (Laurenti, 1768), Dendropsophus triangulum (Günther, 1869), Dentectus barbarmatus Martín Salazar, Isbrücker & Nijssen, 1982, Denticeps clupeoides Clausen, 1959, Denticetopsis royeroi Ferraris, 1996, Derhamia hoffmannorum Géry & Zarske, 2002, Dermatolepis dermatolepis (Boulenger, 1895), Dermatolepis dermatolepis (Boulenger, 1895), Dermatonotus muelleri (Boettger, 1885), Dermatopsis macrodon Ogilby, 1896, Dermogenys bispina Meisner & Collette, 1998, Dermogenys bruneiensis Meisner, 2001, Dermogenys burmanica Mukerji, 1935, Dermogenys collettei Meisner, 2001, Dermogenys orientalis (Weber, 1894), Dermogenys pusilla Kuhl & van Hasselt, 1823, Dermogenys robertsi Meisner, 2001, Dermogenys siamensis Fowler, 1934, Dermogenys sumatrana (Bleeker, 1854), Dermophis mexicanus (Duméril & Bibron, 1841), Deroptyus accipitrinus (Linnaeus, 1758), Desmodus rotundus (E.Geoffroy, 1810), Desmognathus fuscus (Green, 1818), Desmognathus quadramaculatus (Holbrook, 1840), Deuterodon iguape Eigenmann, 1907, Deuterodon langei Travassos, 1957, Deuterodon longirostris (Steindachner, 1907), Deuterodon potaroensis Eigenmann, 1909, Deuterodon singularis Lucena & Lucena, 1992, Deuterodon stigmaturus (Gomes, 1947), Devario aequipinnatus (McClelland, 1839), Devario aequipinnatus (McClelland, 1839), Devario annandalei (Chaudhuri, 1908), Devario assamensis (Barman, 1984), Devario browni (Regan, 1907), Devario chrysotaeniatus (Chu, 1981), Devario devario (Hamilton, 1822), Devario gibber (Kottelat, 2000), Devario interruptus (Day, 1870), Devario kakhienensis (Anderson, 1879), Devario laoensis (Pellegrin & Fang, 1940), Devario leptos (Fang & Kottelat, 1999), Devario maetaengensis (Fang, 1997), Devario malabaricus (Jerdon, 1849), Devario naganensis (Chaudhuri, 1912), Devario pathirana (Kottelat & Pethiyagoda, 1990), Devario regina (Fowler, 1934), Devario salmonata (Kottelat, 2000), Devario shanensis (Hora, 1928), Diademichthys lineatus (Sauvage, 1883), Diadophis punctatus (Linnaeus, 1766), Diagramma pictum (Thunberg, 1792), Dianema longibarbis Cope, 1872, Dianema urostriatum (Miranda Ribeiro, 1912), Diapoma speculiferum Cope, 1894, Diapoma terofali (Géry, 1964), Diasporus diastema (Cope, 1875), Diceros bicornis (Linnaeus, 1758), Dichotomyctere erythrotaenia (Bleeker, 1853), Dichotomyctere fluviatilis (Hamilton, 1822), Dichotomyctere nigroviridis (Marion de Procé, 1822), Dichotomyctere ocellatus (Steindachner, 1870), Dicrossus filamentosus (Ladiges, 1958), Dicrossus maculatus Steindachner, 1875, Dicrurus adsimilis (Bechstein, 1794), Didelphis albiventris Lund, 1840, Didelphis marsupialis Linnaeus, 1758, Didelphis virginiana Kerr, 1792, Dimidiochromis compressiceps (Boulenger, 1908), Dimidiochromis dimidiatus (Günther, 1864), Dimidiochromis kiwinge (Ahl, 1926), Dimidiochromis strigatus (Regan, 1922), Dinemellia dinemelli (Rüppell, 1845), Dinotopterus cunningtoni Boulenger, 1906, Diodon holocanthus Linnaeus, 1758, Diodon hystrix Linnaeus, 1758, Dionda argentosa Girard, 1856, Dionda diaboli Hubbs & Brown, 1957, Dionda episcopa Baird, 1857, Dionda melanops Girard, 1856, Dionda nigrotaeniata (Cope, 1880), Dionda serena Baird, 1857, Diopsittaca nobilis (Linnaeus, 1758), Diplectrum formosum (Linnaeus, 1766), Diplobatis ommata (Jordan & Gilbert, 1890), Diplodactylus galeatus Kluge, 1963, Diplodactylus granariensis Storr, 1979, Diplodactylus pulcher (Steindachner, 1870), Diplodactylus tessellatus (Günther, 1875), Diplodactylus vittatus Gray, 1832, Diplomystes camposensis Arratia, 1987, Diplomystes nahuelbutaensis Arratia, 1987, Diplomystes viedmensis MacDonagh, 1931, Diploprion drachi Roux-Estève, 1955, Diplotaxodon aeneus Turner & Stauffer, 1998, Diplotaxodon apogon Turner & Stauffer, 1998, Diplotaxodon argenteus Trewavas, 1935, Diplotaxodon ecclesi Burgess & Axelrod, 1973, Diplotaxodon greenwoodi Stauffer & McKaye, 1986, Diplotaxodon limnothrissa Turner, 1994, Diplotaxodon macrops Turner & Stauffer, 1998, Dipodomys phillipsii Gray, 1841, Diproctacanthus xanthurus (Bleeker, 1856), Dipsas catesbyi (Sentzen, 1796), Dipsas indica Laurenti, 1768, Dipsosaurus dorsalis (Baird & Girard, 1852), Diptychus maculatus Steindachner, 1866, Diptychus sewerzowi Kessler, 1872, Discherodontus ashmeadi (Fowler, 1937), Discherodontus halei (Duncker, 1904), Discherodontus parvus (Wu & Lin, 1977), Dischistodus melanotus (Bleeker, 1858), Dischistodus perspicillatus (Cuvier, 1830), Dischistodus prosopotaenia (Bleeker, 1852), Dischistodus pseudochrysopoecilus (Allen & Robertson, 1974), Discogobio macrophysallidos Huang, 1989, Discogobio microstoma (Mai, 1978), Discordipinna griessingeri Hoese & Fourmanoir, 1978, Dispholidus typus (Smith, 1828), Distichodus affinis Günther, 1873, Distichodus altus Boulenger, 1899, Distichodus antonii Schilthuis, 1891, Distichodus atroventralis Boulenger, 1898, Distichodus brevipinnis Günther, 1864, Distichodus decemmaculatus Pellegrin, 1926, Distichodus engycephalus Günther, 1864, Distichodus fasciolatus Boulenger, 1898, Distichodus hypostomatus Pellegrin, 1900, Distichodus kolleri Holly, 1926, Distichodus langi Nichols & Griscom, 1917, Distichodus lusosso Schilthuis, 1891, Distichodus maculatus Boulenger, 1898, Distichodus mossambicus Peters, 1852, Distichodus nefasch (Bonnaterre, 1788), Distichodus noboli Boulenger, 1899, Distichodus notospilus Günther, 1867, Distichodus petersii Pfeffer, 1896, Distichodus rostratus Günther, 1864, Distichodus rufigiensis Norman, 1922, Distichodus schenga Peters, 1852, Distichodus sexfasciatus Boulenger, 1897, Distocyclus conirostris (Eigenmann & Allen, 1942), Distocyclus goajira (Schultz, 1949), Distoechodon tumirostris Peters, 1881, Distoechurus pennatus Peters, 1874, Divandu albimarginatus Lamboj & Snoeks, 2000, Dixonius melanostictus (Taylor, 1962), Dixonius siamensis (Boulenger, 1899), Docimodus evelynae Eccles & Lewis, 1976, Docimodus johnstoni Boulenger, 1897, Dogania subplana (Geoffroy Saint-Hilaire, 1809), Dolichallabes microphthalmus Poll, 1942, Dolichancistrus atratoensis (Dahl, 1960), Dolichancistrus carnegiei (Eigenmann, 1916), Dolichancistrus cobrensis (Schultz, 1944), Dolichancistrus fuesslii (Steindachner, 1911), Dolichancistrus setosus (Boulenger, 1887), Dolichophis cypriensis (Schätti, 1985), Dolichophis jugularis (Linnaeus, 1758), Dolichotis patagonum (Zimmermann, 1780), Doraops zuloagai Schultz, 1944, Doras carinatus (Linnaeus, 1766), Doras micropoeus (Eigenmann, 1912), Dorcopsis muelleri (Lesson, 1827), Dormitator cubanus Ginsburg, 1953, Dormitator latifrons (Richardson, 1844), Dormitator maculatus (Bloch, 1792), Doryichthys boaja (Bleeker, 1850), Doryichthys contiguus Kottelat, 2000, Doryichthys deokhatoides (Bleeker, 1854), Doryichthys martensii (Peters, 1868), Doryrhamphus dactyliophorus (Bleeker, 1853), Doryrhamphus excisus Kaup, 1856, Doryrhamphus janssi (Herald & Randall, 1972), Doryrhamphus multiannulatus (Regan, 1903), Doumea alula Nichols & Griscom, 1917, Doumea chappuisi Pellegrin, 1933, Doumea thysi Skelton, 1989, Doumea typica Sauvage, 1879, Draco fimbriatus Kuhl, 1820, Draco lineatus Daudin, 1802, Draco melanopogon Boulenger, 1887, Draco volans Linnaeus, 1758, Dromaius novaehollandiae (Latham, 1790), Drombus globiceps (Hora, 1923), Dromicodryas bernieri (Duméril, Bibron & Duméril, 1854), Dromicodryas quadrilineatus (Duméril, Bibron & Duméril, 1854), Drymarchon corais (Boie, 1827), Drymarchon melanurus (Duméril, Bibron & Duméril, 1854), Drymobius margaritiferus (Schlegel, 1837), Drymoluber dichrous (Peters, 1863), Dryocalamus davisonii (Blanford, 1878), Dryophytes chrysoscelis (Cope, 1880), Dryophytes cinereus (Schneider, 1799), Dryophytes gratiosus (LeConte, 1856), Dryophytes squirellus (Daudin, 1800), Dryophytes versicolor (LeConte, 1825), Ducula aenea (Linnaeus, 1766), Ducula bicolor (Scopoli, 1786), Ducula pistrinaria Bonaparte, 1855, Ducula rubricera (Bonaparte, 1854), Ducula rufigaster (Quoy & Gaimard, 1832), Dunckerocampus baldwini Herald & Randall, 1972, Dunckerocampus chapmani Herald, 1953, Dundocharax bidentatus Poll, 1967, Duopalatinus peruanus Eigenmann & Allen, 1942, Dupouyichthys sapito Schultz, 1944, Duttaphrynus melanostictus (Schneider, 1799), Duttaphrynus melanostictus (Schneider, 1799), Dyscophus antongilii Grandidier, 1877, Dyscophus guineti (Grandidier, 1875), Dyscophus insularis Grandidier, 1872, Ebenavia inunguis Boettger, 1878, Echeneis naucrates Linnaeus, 1758, Echidna catenata (Bloch, 1795), Echidna leucotaenia Schultz, 1943, Echidna nebulosa (Ahl, 1789), Echidna nocturna (Cope, 1872), Echidna polyzona (Richardson, 1845), Echidna rhodochilus Bleeker, 1863, Echidna xanthospilos (Bleeker, 1859), Echinops telfairi Martin, 1838, Echiophis intertinctus (Richardson, 1848), Echis carinatus (Schneider, 1801), Echis coloratus Arnold & Gallagher, 1977, Echis ocellatus Stemmler, 1970, Echis pyramidum (Geoffroy Saint-Hilaire, 1827), Eclectochromis ornatus (Regan, 1922), Eclectus roratus (Statius Muller, 1776), Ecsenius bicolor (Day, 1888), Ecsenius bimaculatus Springer, 1971, Ecsenius gravieri (Pellegrin, 1906), Ecsenius lineatus Klausewitz, 1962, Ecsenius lividanalis Chapman & Schultz, 1952, Ecsenius mandibularis McCulloch, 1923, Ecsenius midas Starck, 1969, Ecsenius nalolo Smith, 1959, Ecsenius namiyei (Jordan & Evermann, 1902), Ecsenius ops Springer & Allen, 2001, Ecsenius opsifrontalis Chapman & Schultz, 1952, Ecsenius pictus McKinney & Springer, 1976, Ecsenius stigmatura Fowler, 1952, Ecsenius tigris Springer, 1988, Ectodus descampsii Boulenger, 1898, Egretta intermedia (Wagler, 1829), Egretta tricolor (Statius Muller, 1776), Eidolon helvum (Kerr, 1792), Eigenmannia humboldtii (Steindachner, 1878), Eigenmannia limbata (Schreiner & Miranda Ribeiro, 1903), Eigenmannia macrops (Boulenger, 1897), Eigenmannia microstoma (Reinhardt, 1852), Eigenmannia nigra Mago-Leccia, 1994, Eigenmannia trilineata López & Castello, 1966, Eigenmannia virescens (Valenciennes, 1836), Eira barbara (Linnaeus, 1758), Eirmotus octozona Schultz, 1959, Ekemblemaria myersi Stephens, 1963, Elacatinus chancei (Beebe & Hollister, 1933), Elacatinus evelynae (Böhlke & Robins, 1968), Elacatinus figaro Sazima, Moura & Rosa, 1997, Elacatinus macrodon (Beebe & Tee-Van, 1928), Elacatinus multifasciatus (Steindachner, 1876), Elacatinus oceanops Jordan, 1904, Elacatinus prochilos (Böhlke & Robins, 1968), Elachocharax geryi Weitzman & Kanazawa, 1978, Elachocharax junki (Géry, 1971), Elachocharax mitopterus Weitzman, 1986, Elachocharax pulcher Myers, 1927, Elaenia pallatangae P.L.Sclater, 1862, Elaphe carinata (Günther, 1864), Elaphe climacophora (Boie, 1826), Elaphe davidi (Sauvage, 1884), Elaphe dione (Pallas, 1773), Elaphe quadrivirgata (Boie, 1826), Elaphe quatuorlineata Lacepede, 1789, Elaphurus davidianus Milne-Edwards, 1866, Elassoma alabamae Mayden, 1993, Elassoma boehlkei Rohde & Arndt, 1987, Elassoma evergladei Jordan, 1884, Elassoma okatie Rohde & Arndt, 1987, Elassoma okefenokee Böhlke, 1956, Elassoma zonatum Jordan, 1877, Electrophorus electricus (Linnaeus, 1766), Eleotris acanthopoma Bleeker, 1853, Eleotris amblyopsis (Cope, 1871), Eleotris annobonensis Blanc, Cadenat & Stauch, 1968, Eleotris aquadulcis Allen & Coates, 1990, Eleotris daganensis Steindachner, 1870, Eleotris fusca (Forster, 1801), Eleotris lutea Day, 1876, Eleotris melanosoma Bleeker, 1853, Eleotris oxycephala Temminck & Schlegel, 1845, Eleotris pellegrini Maugé, 1984, Eleotris perniger (Cope, 1871), Eleotris picta Kner, 1863, Eleotris pisonis (Gmelin, 1789), Eleotris sandwicensis Vaillant & Sauvage, 1875, Eleotris senegalensis Steindachner, 1870, Eleotris tubularis Heller & Snodgrass, 1903, Eleotris vittata Duméril, 1861, Elephas maximus Linnaeus, 1758, Eleutherodactylus abbotti Cochran, 1923, Eleutherodactylus johnstonei Barbour, 1914, Eleutherodactylus martinicensis (Tschudi, 1838), Eleutheronema tetradactylum (Shaw, 1804), Eliomys quercinus (Linnaeus, 1766), Ellopostoma megalomycter (Vaillant, 1902), Ellopostoma mystax Tan & Lim, 2002, Elopichthys bambusa (Richardson, 1845), Elops lacerta Valenciennes, 1847, Elops saurus Linnaeus, 1766, Elops senegalensis Regan, 1909, Elseya branderhorsti (Ouwens, 1914), Elseya dentata (Gray, 1863), Elseya irwini Cann, 1997, Elseya novaeguineae (Meyer, 1874), Elseya schultzei (Vogt, 1911), Emberiza aureola Pallas, 1773, Emberiza flaviventris Stephens, 1815, Emberiza hortulana Linnaeus, 1758, Emberiza impetuani A.Smith, 1836, Emberiza melanocephala Scopoli, 1769, Emberiza pallasi (Cabanis, 1851), Embiotoca jacksoni Agassiz, 1853, Embiotoca lateralis Agassiz, 1854, Emblema pictum Gould, 1842, Emblemaria pandionis Evermann & Marsh, 1900, Emoia atrocostata (Lesson, 1830), Emoia caeruleocauda (De Vis, 1892), Emoia cyanura (Lesson, 1830), Empetrichthys latos Miller, 1948, Empidonax flaviventris (W.M.Baird & S.F.Baird, 1843), Emydoidea blandingii (Holbrook, 1838), Emydura macquarii (Gray, 1830), Emydura macquarii (Gray, 1830), Emydura macquarii (Gray, 1830), Emydura subglobosa (Krefft, 1876), Emydura subglobosa (Krefft, 1876), Emydura victoriae (Gray, 1842), Emys orbicularis (Linnaeus, 1758), Enchelycore nigricans (Bonnaterre, 1788), Enchelycore pardalis (Temminck & Schlegel, 1846), Enchelycore pardalis (Temminck & Schlegel, 1846), Engraulicypris sardella (Günther, 1868), Engraulisoma taeniatum Castro, 1981, Engystomops pustulosus (Cope, 1864), Enhydra lutris (Linnaeus, 1758), Enicognathus leptorhynchus (King, 1831), Enneacampus ansorgii (Boulenger, 1910), Enneacanthus chaetodon (Baird, 1855), Enneacanthus obesus (Girard, 1854), Enophrys bison (Girard, 1854), Enoplosus armatus (White, 1790), Ensatina eschscholtzii Gray, 1850, Entomocorus benjamini Eigenmann, 1917, Entomocorus gameroi Mago-Leccia, 1984, Entomocorus melaphareus Akama & Ferraris, 2003, Entomyzon cyanotis (Latham, 1802), Enyalioides palpebralis (Boulenger, 1883), Eolophus roseicapilla (Vieillot, 1817), Eolophus roseicapilla (Vieillot, 1817), Eos bornea (Linnaeus, 1758), Eos bornea (Linnaeus, 1758), Eos histrio (Statius Muller, 1776), Eos reticulata (S.Muller, 1841), Eos semilarvata Bonaparte, 1850, Eos squamata (Boddaert, 1783), Epactionotus bilineatus Reis & Schaefer, 1998, Epactionotus gracilis Reis & Schaefer, 1998, Epactionotus itaimbezinho Reis & Schaefer, 1998, Epalzeorhynchos bicolor (Smith, 1931), Epalzeorhynchos kalopterus (Bleeker, 1850), Epapterus blohmi Vari, Jewett, Taphorn & Gilbert, 1984, Epapterus dispilurus Cope, 1878, Ephippiorhynchus senegalensis (Shaw, 1800), Epibulus insidiator (Pallas, 1770), Epicrates alvarezi Abalos, Baez & Nader, 1964, Epicrates cenchria (Linnaeus, 1758), Epicrates maurus Gray, 1849, Epinephelus coioides (Hamilton, 1822), Epinephelus cyanopodus (Richardson, 1846), Epinephelus fasciatus (Forsskål, 1775), Epinephelus flavocaeruleus (Lacepède, 1802), Epinephelus fuscoguttatus (Forsskål, 1775), Epinephelus lanceolatus (Bloch, 1790), Epinephelus maculatus (Bloch, 1790), Epinephelus polystigma (Bleeker, 1853), Epipedobates anthonyi (Noble, 1921), Epipedobates boulengeri (Barbour, 1909), Epipedobates darwinwallacei Cisneros-Heredia & Yánez-Muñoz, 2011, Epipedobates tricolor (Boulenger, 1899), Epiplatys ansorgii (Boulenger, 1911), Epiplatys barmoiensis Scheel, 1968, Epiplatys bifasciatus (Steindachner, 1881), Epiplatys chaperi (Sauvage, 1882), Epiplatys chevalieri (Pellegrin, 1904), Epiplatys dageti Poll, 1953, Epiplatys fasciolatus (Günther, 1866), Epiplatys grahami (Boulenger, 1911), Epiplatys guineensis Romand, 1994, Epiplatys hildegardae Berkenkamp, 1978, Epiplatys lamottei Daget, 1954, Epiplatys longiventralis (Boulenger, 1911), Epiplatys mesogramma Huber, 1980, Epiplatys multifasciatus (Boulenger, 1913), Epiplatys neumanni Berkenkamp, 1993, Epiplatys njalaensis Neumann, 1976, Epiplatys olbrechtsi Poll, 1941, Epiplatys phoeniceps Huber, 1980, Epiplatys sexfasciatus Gill, 1862, Epiplatys singa (Boulenger, 1899), Epiplatys spilargyreius (Duméril, 1861), Eptatretus burgeri (Girard, 1855), Eptatretus okinoseanus (Dean, 1904), Eptesicus fuscus (Palisot de Beauvois, 1796), Equetus lanceolatus (Linnaeus, 1758), Equetus punctatus (Bloch & Schneider, 1801), Equus africanus Heuglin & Fitzinger, 1866, Equus grevyi Oustalet, 1882, Equus kiang Moorcroft, 1841, Equus przewalskii Poliakov, 1881, Equus quagga Boddaert, 1785, Equus quagga Boddaert, 1785, Equus zebra Linnaeus, 1758, Eremophilus mutisii Humboldt, 1805, Erethistes pusillus Müller & Troschel, 1849, Erethistoides montana Hora, 1950, Erethizon dorsatus (Linnaeus, 1758), Eretmochelys imbricata (Linnaeus, 1766), Eretmodus cyanostictus Boulenger, 1898, Erimonax monachus (Cope, 1868), Erimystax cahni (Hubbs & Crowe, 1956), Erimystax dissimilis (Kirtland, 1840), Erimystax harryi (Hubbs & Crowe, 1956), Erimystax insignis (Hubbs & Crowe, 1956), Erimystax x-punctatus (Hubbs & Crowe, 1956), Erimyzon claviformis (Girard, 1856), Erimyzon tenuis (Agassiz, 1855), Erinaceus europaeus Linnaeus, 1758, Erithacus rubecula (Linnaeus, 1758), Ernstichthys anduzei Fernández-Yépez, 1953, Ernstichthys intonsus Stewart, 1985, Ernstichthys megistus (Orcés V., 1961), Erotelis armiger (Jordan & Richardson, 1895), Erotelis smaragdus (Valenciennes, 1837), Erpetoichthys calabaricus Smith, 1865, Erpeton tentaculatum Lacépède, 1800, Erymnochelys madagascariensis (Grandidier, 1867), Erythrinus erythrinus (Bloch & Schneider, 1801), Erythrolamprus aesculapii (Linnaeus, 1758), Erythrolamprus aesculapii (Linnaeus, 1758), Erythrolamprus cobella (Linnaeus, 1758), Erythrolamprus poecilogyrus (Wied-Neuwied, 1824), Erythrolamprus reginae (Linnaeus, 1758), Erythrolamprus typhlus (Linnaeus, 1758), Erythrura cyaneovirens (Peale, 1848), Erythrura gouldiae (Gould, 1844), Erythrura gouldiae (Gould, 1844), Erythrura hyperythra (Reichenbach, 1862), Erythrura pealii Hartlaub, 1852, Erythrura prasina (Sparrman, 1788), Erythrura psittacea (Gmelin, 1789), Erythrura trichroa (Kittlitz, 1833), Erythrura tricolor (Vieillot, 1817), Eryx colubrinus (Linnaeus, 1758), Eryx conicus (Schneider, 1801), Eryx elegans (Gray, 1849), Eryx jaculus (Linnaeus, 1758), Eryx jayakari Boulenger, 1888, Eryx johnii Boulenger, 1893, Eryx miliaris (Pallas, 1773), Eryx muelleri (Boulenger, 1892), Eryx tataricus Tzarevsky, 1915, Eryx whitakeri Das, 1991, Esomus ahli Hora & Mukerji, 1928, Esomus altus (Blyth, 1860), Esomus barbatus (Jerdon, 1849), Esomus caudiocellatus Ahl, 1923, Esomus danricus (Hamilton, 1822), Esomus lineatus Ahl, 1923, Esomus longimanus (Lunel, 1881), Esomus metallicus Ahl, 1923, Esomus thermoicos (Valenciennes, 1842), Esox reichertii Dybowski, 1869, Espadarana prosoblepon (Boettger, 1892), Estrilda astrild (Linnaeus, 1758), Estrilda caerulescens (Vieillot, 1817), Estrilda charmosyna (Reichenow, 1881), Estrilda erythronotos (Vieillot, 1817), Estrilda melpoda (Vieillot, 1817), Estrilda rhodopyga Sundevall, 1850, Estrilda troglodytes (Lichtenstein, 1823), Etheostoma acuticeps Bailey, 1959, Etheostoma akatulo Layman & Mayden, 2009, Etheostoma artesiae (Hay, 1881), Etheostoma asprigene (Forbes, 1878), Etheostoma atripinne (Jordan, 1877), Etheostoma australe Jordan, 1889, Etheostoma baileyi Page & Burr, 1982, Etheostoma barbouri Kuehne & Small, 1971, Etheostoma barrenense Burr & Page, 1982, Etheostoma bellator Suttkus & Bailey, 1993, Etheostoma bellum Zorach, 1968, Etheostoma bison Ceas & Page, 1997, Etheostoma blennius Gilbert & Swain, 1887, Etheostoma boschungi Wall & Williams, 1974, Etheostoma brevirostrum Suttkus & Etnier, 1991, Etheostoma brevispinum (Coker, 1926), Etheostoma burri Ceas & Page, 1997, Etheostoma camurum (Cope, 1870), Etheostoma cervus Powers & Mayden, 2003, Etheostoma chermocki Boschung, Mayden & Tomelleri, 1992, Etheostoma chienense Page & Ceas, 1992, Etheostoma chlorobranchium Zorach, 1972, Etheostoma chlorosomum (Hay, 1881), Etheostoma chuckwachatte Mayden & Wood, 1993, Etheostoma cinereum Storer, 1845, Etheostoma collettei Birdsong & Knapp, 1969, Etheostoma collis (Hubbs & Cannon, 1935), Etheostoma colorosum Suttkus & Bailey, 1993, Etheostoma coosae (Fowler, 1945), Etheostoma corona Page & Ceas, 1992, Etheostoma crossopterum Braasch & Mayden, 1985, Etheostoma davisoni Hay, 1885, Etheostoma denoncourti Stauffer & van Snik, 1997, Etheostoma derivativum Page, Hardman & Near, 2003, Etheostoma ditrema Ramsey & Suttkus, 1965, Etheostoma douglasi Wood & Mayden, 1993, Etheostoma duryi Henshall, 1889, Etheostoma etnieri Bouchard, 1977, Etheostoma etowahae Wood & Mayden, 1993, Etheostoma euzonum (Hubbs & Black, 1940), Etheostoma flabellare Rafinesque, 1819, Etheostoma flavum Etnier & Bailey, 1989, Etheostoma fonticola (Jordan & Gilbert, 1886), Etheostoma forbesi Page & Ceas, 1992, Etheostoma fragi Distler, 1968, Etheostoma fricksium Hildebrand, 1923, Etheostoma gracile (Girard, 1859), Etheostoma grahami (Girard, 1859), Etheostoma gutselli (Hildebrand, 1932), Etheostoma histrio Jordan & Gilbert, 1887, Etheostoma hopkinsi (Fowler, 1945), Etheostoma inscriptum (Jordan & Brayton, 1878), Etheostoma jessiae (Jordan & Brayton, 1878), Etheostoma jordani Gilbert, 1891, Etheostoma juliae Meek, 1891, Etheostoma kanawhae (Raney, 1941), Etheostoma kantuckeense Ceas & Page, 1997, Etheostoma kennicotti (Putnam, 1863), Etheostoma lachneri Suttkus & Bailey, 1994, Etheostoma lawrencei Ceas & Burr, 2002, Etheostoma lemniscatum Blanton, 2008, Etheostoma lepidum (Baird & Girard, 1853), Etheostoma longimanum Jordan, 1888, Etheostoma lugoi Norris & Minckley, 1997, Etheostoma luteovinctum Gilbert & Swain, 1887, Etheostoma lynceum Hay, 1885, Etheostoma maculatum Kirtland, 1840, Etheostoma mariae (Fowler, 1947), Etheostoma marmorpinnum Blanton & Jenkins, 2008, Etheostoma meridianum (Williams, 1975), Etheostoma microperca Jordan & Gilbert, 1888, Etheostoma moorei Raney & Suttkus, 1964, Etheostoma neopterum Howell & Dingerkus, 1978, Etheostoma nianguae Gilbert & Meek, 1887, Etheostoma nigripinne Braasch & Mayden, 1985, Etheostoma obeyense Kirsch, 1892, Etheostoma okaloosae (Fowler, 1941), Etheostoma olivaceum Braasch & Page, 1979, Etheostoma oophylax Ceas & Page, 1992, Etheostoma osburni (Hubbs & Trautman, 1932), Etheostoma pallididorsum Distler & Metcalf, 1962, Etheostoma parvipinne Gilbert & Swain, 1887, Etheostoma percnurum Jenkins, 1994, Etheostoma perlongum (Hubbs & Raney, 1946), Etheostoma phytophilum Bart & Taylor, 1999, Etheostoma podostemone Jordan & Jenkins, 1889, Etheostoma pottsii (Girard, 1859), Etheostoma proeliare (Hay, 1881), Etheostoma pseudovulatum Page & Ceas, 1992, Etheostoma punctulatum (Agassiz, 1854), Etheostoma pyrrhogaster Bailey & Etnier, 1988, Etheostoma radiosum (Hubbs & Black, 1941), Etheostoma rafinesquei Burr & Page, 1982, Etheostoma ramseyi Suttkus & Bailey, 1994, Etheostoma raneyi Suttkus & Bart, 1994, Etheostoma rubrum Raney & Suttkus, 1966, Etheostoma rupestre Gilbert & Swain, 1887, Etheostoma sagitta (Jordan & Swain, 1883), Etheostoma saludae (Hubbs & Cannon, 1935), Etheostoma scotti Bauer, Etnier & Burkhead, 1995, Etheostoma sellare (Radcliffe & Welsh, 1913), Etheostoma sequatchiense Burr, 1979, Etheostoma serrifer (Hubbs & Cannon, 1935), Etheostoma sitikuense Blanton, 2008, Etheostoma smithi Page & Braasch, 1976, Etheostoma spectabile (Agassiz, 1854), Etheostoma spilotum Gilbert, 1887, Etheostoma squamiceps Jordan, 1877, Etheostoma stigmaeum (Jordan, 1877), Etheostoma striatulum Page & Braasch, 1977, Etheostoma susanae (Jordan & Swain, 1883), Etheostoma swaini (Jordan, 1884), Etheostoma swannanoa Jordan & Evermann, 1889, Etheostoma tallapoosae Suttkus & Etnier, 1991, Etheostoma tecumsehi Ceas & Page, 1997, Etheostoma tetrazonum (Hubbs & Black, 1940), Etheostoma thalassinum (Jordan & Brayton, 1878), Etheostoma tippecanoe Jordan & Evermann, 1890, Etheostoma trisella Bailey & Richards, 1963, Etheostoma tuscumbia Gilbert & Swain, 1887, Etheostoma uniporum Distler, 1968, Etheostoma variatum Kirtland, 1840, Etheostoma virgatum (Jordan, 1880), Etheostoma vitreum (Cope, 1870), Etheostoma vulneratum (Cope, 1870), Etheostoma wapiti Etnier & Williams, 1989, Etheostoma whipplei (Girard, 1859), Etheostoma zonifer (Hubbs & Cannon, 1935), Etheostoma zonistium Bailey & Etnier, 1988, Etia nguti Schliewen & Stiassny, 2003, Etroplus canarensis Day, 1877, Etroplus maculatus (Bloch, 1795), Etroplus suratensis (Bloch, 1790), Eublepharis angramainyu Anderson & Leviton, 1966, Eublepharis hardwickii Gray, 1827, Eublepharis macularius (Blyth, 1854), Euchilichthys boulengeri Nichols & La Monte, 1934, Euchilichthys dybowskii (Vaillant, 1892), Euchilichthys guentheri (Schilthuis, 1891), Euchilichthys royauxi Boulenger, 1902, Eucrossorhinus dasypogon (Bleeker, 1867), Eucyclogobius newberryi (Girard, 1856), Eudocimus albus (Linnaeus, 1758), Eudocimus ruber (Linnaeus, 1758), Eudromia elegans I.Geoffroy Saint-Hilaire, 1832, Eudyptes chrysocome (J.R.Forster, 1781), Eudyptes chrysolophus (Brandt, 1837), Eudyptula minor (J.R.Forster, 1781), Eugnathichthys eetveldii Boulenger, 1898, Eugnathichthys macroterolepis Boulenger, 1899, Eugongylus albofasciolatus (Günther, 1872), Eulemur collaris (É.Geoffroy Saint-Hilaire, 1812), Eulemur macaco (Linnaeus, 1766), Eulemur mongoz (Linnaeus, 1766), Euleptorhamphus viridis (van Hasselt, 1823), Eumeces egregius (Baird, 1858), Eumeces fasciatus (Linnaeus, 1758), Eumeces laticeps (Schneider, 1801), Eumeces skiltonianus (Baird & Girard, 1852), Eumetopias jubatus (Schreber, 1776), Eumicrotremus orbis (Günther, 1861), Eumomota superciliosa (Sandbach, 1837), Eunectes murinus (Linnaeus, 1758), Eunectes notaeus Cope, 1862, Euodice cantans (Gmelin, 1789), Euodice malabarica (Linnaeus, 1758), Euphonia chlorotica (Linnaeus, 1766), Euphonia finschi P.L.Sclater & Salvin, 1877, Euphonia fulvicrissa P.L.Sclater, 1857, Euphonia hirundinacea Bonaparte, 1838, Euphonia luteicapilla (Cabanis, 1861), Euphonia minuta Cabanis, 1849, Euphonia musica (J.F.Gmelin, 1789), Euphonia violacea (Linnaeus, 1758), Euphonia xanthogaster Sundevall, 1834, Euphractus sexcinctus (Linnaeus, 1758), Euphyllia cristata Chevalier, 1971, Euplectes afer (Gmelin, 1789), Euplectes ardens (Boddaert, 1783), Euplectes franciscanus (Isert, 1789), Euplectes hordeaceus (Linnaeus, 1758), Euplectes macroura (Gmelin, 1789), Euplectes nigroventris Cassin, 1848, Euplectes orix (Linnaeus, 1758), Euprepiophis mandarinus (Cantor, 1842), Eurycea bislineata (Green, 1818), Eurycea guttolineata (Holbrook, 1838), Eurycea nana Bishop, 1941, Eurycea quadridigitata (Holbrook, 1842), Eurycheilichthys pantherinus (Reis & Schaefer, 1992), Eurydactylodes agricolae Henkel & Böhme, 2001, Eurydactylodes vieillardi (Bavay, 1869), Eurypegasus draconis (Linnaeus, 1766), Eurypyga helias (Pallas, 1781), Euschistospiza dybowskii (Oustalet, 1892), Eutropiichthys vacha (Hamilton, 1822), Eviota bifasciata Lachner & Karnella, 1980, Eviota nigriventris Giltay, 1933, Eviota pellucida Larson, 1976, Eviota punctulata Jewett & Lachner, 1983, Evorthodus lyricus (Girard, 1858), Exallias brevis (Kner, 1868), Exallodontus aguanai Lundberg, Mago-Leccia & Nass, 1991, Exastilithoxus fimbriatus (Steindachner, 1915), Exastilithoxus hoedemani Isbrücker & Nijssen, 1985, Exochochromis anagenys Oliver, 1989, Exodon paradoxus Müller & Troschel, 1844, Exostoma labiatum (McClelland, 1842), Exyrias belissimus (Smith, 1959), Falcipennis falcipennis (Hartlaub, 1855), Falco biarmicus Temminck, 1825, Falco cherrug J.E.Gray, 1834, Falco chicquera Daudin, 1800, Falco columbarius Linnaeus, 1758, Falco deiroleucus Temminck, 1825, Falco eleonorae Gene, 1839, Falco fasciinucha Reichenow & Neumann, 1895, Falco femoralis Temminck, 1822, Falco jugger J.E.Gray, 1834, Falco mexicanus Schlegel, 1850, Falco pelegrinoides Temminck, 1829, Falco peregrinus Tunstall, 1771, Falco rupicoloides A.Smith, 1829, Falco rusticolus Linnaeus, 1758, Falco sparverius Linnaeus, 1758, Falco tinnunculus Linnaeus, 1758, Falco vespertinus Linnaeus, 1766, Farancia abacura (Holbrook, 1836), Farlowella acus (Kner, 1853), Farlowella amazonum (Günther, 1864), Farlowella colombiensis Retzer & Page, 1997, Farlowella curtirostra Myers, 1942, Farlowella gracilis Regan, 1904, Farlowella hahni Meinken, 1937, Farlowella hasemani Eigenmann & Vance, 1917, Farlowella henriquei Miranda Ribeiro, 1918, Farlowella isbruckeri Retzer & Page, 1997, Farlowella jauruensis Eigenmann & Vance, 1917, Farlowella knerii (Steindachner, 1882), Farlowella mariaelenae Martín Salazar, 1964, Farlowella nattereri Steindachner, 1910, Farlowella odontotumulus Retzer & Page, 1997, Farlowella oxyrryncha (Kner, 1853), Farlowella paraguayensis Retzer & Page, 1997, Farlowella reticulata Boeseman, 1971, Farlowella rugosa Boeseman, 1971, Farlowella schreitmuelleri Ahl, 1937, Farlowella smithi Fowler, 1913, Farlowella taphorni Retzer & Page, 1997, Farlowella vittata Myers, 1942, Fejervarya cancrivora (Gravenhorst, 1829), Fejervarya limnocharis (Gravenhorst, 1829), Felis catus Linnaeus, 1758, Felis chaus Guldenstaedt, 1776, Felis manul Pallas, 1776, Felis manul Pallas, 1776, Felis margarita Loche, 1858, Felis nigripes Burchell, 1824, Felis silvestris Schreber, 1777, Fistularia commersonii Rüppell, 1838, Floridichthys carpio (Günther, 1866), Floridichthys polyommus Hubbs, 1936, Florisuga mellivora (Linnaeus, 1758), Fluviphylax obscurus Costa, 1996, Fluviphylax pygmaeus (Myers & Carvalho, 1955), Fluviphylax zonatus Costa, 1996, Foerschichthys flavipinnis (Meinken, 1932), Forbesichthys agassizii (Putnam, 1872), Forcipiger flavissimus Jordan & McGregor, 1898, Forcipiger longirostris (Broussonet, 1782), Forpus coelestis (Lesson, 1847), Forpus cyanopygius (Souance, 1856), Forpus modestus (Cabanis, 1848), Forpus passerinus (Linnaeus, 1758), Forpus xanthops (Salvin, 1895), Fossa fossana (Müller, 1776), Fossorochromis rostratus (Boulenger, 1899), Fowleria variegata (Fourmanoir & Crosnier, 1964), Fowleria variegata (Fourmanoir & Crosnier, 1964), Franciscodoras marmoratus (Lütken, 1874), Francolinus sephaena (A.Smith, 1836), Francolinus swainsonii (A.Smith, 1836), Fratercula arctica (Linnaeus, 1758), Fringilla coelebs Linnaeus, 1758, Funambulus pennantii Wroughton, 1905, Fundulopanchax filamentosus Meinken, 1933, Fundulopanchax filamentosus Meinken, 1933, Fundulopanchax gardneri (Boulenger, 1911), Fundulopanchax gularis (Boulenger, 1902), Fundulopanchax mirabilis (Radda, 1970), Fundulopanchax walkeri (Boulenger, 1911), Fundulus bermudae Günther, 1874, Fundulus bifax Cashner & Rogers, 1988, Fundulus blairae Wiley & Hall, 1975, Fundulus cingulatus Valenciennes, 1846, Fundulus cingulatus Valenciennes, 1846, Fundulus confluentus Goode & Bean, 1879, Fundulus dispar (Agassiz, 1854), Fundulus escambiae (Bollman, 1887), Fundulus euryzonus Suttkus & Cashner, 1981, Fundulus grandissimus Hubbs, 1936, Fundulus jenkinsi (Evermann, 1892), Fundulus julisia Williams & Etnier, 1982, Fundulus lima Vaillant, 1894, Fundulus lineolatus (Agassiz, 1854), Fundulus luciae (Baird, 1855), Fundulus majalis (Walbaum, 1792), Fundulus notti (Agassiz, 1854), Fundulus olivaceus (Storer, 1845), Fundulus parvipinnis Girard, 1854, Fundulus persimilis Miller, 1955, Fundulus pulvereus (Evermann, 1892), Fundulus rathbuni Jordan & Meek, 1889, Fundulus similis (Baird & Girard, 1853), Fundulus waccamensis Hubbs & Raney, 1946, Furcifer angeli (Brygoo & Domergue, 1968), Furcifer antimena (Grandidier, 1872), Furcifer balteatus (Duméril & Bibron, 1851), Furcifer bifidus (Brongniart, 1800), Furcifer campani (Grandidier, 1872), Furcifer cephalolepis (Günther, 1880), Furcifer lateralis (Gray, 1831), Furcifer minor (Günther, 1879), Furcifer oustaleti (Mocquard, 1894), Furcifer pardalis (Cuvier, 1829), Furcifer petteri (Brygoo & Domergue, 1966), Furcifer polleni (Peters, 1874), Furcifer verrucosus Cuvier, 1829, Furcifer viridis Florio, Ingram, Rakotondravony, Louis Jr & Raxworthy, 2012, Furcifer willsii (Günther, 1890), Furcodontichthys novaesi Rapp Py-Daniel, 1981, Gadopsis bispinosus Sanger, 1984, Gadopsis marmoratus Richardson, 1848, Gadus macrocephalus Tilesius, 1810, Gadus morhua Linnaeus, 1758, Gagata cenia (Hamilton, 1822), Gagata dolichonema He, 1996, Gagata gagata (Hamilton, 1822), Gagata itchkeea (Sykes, 1839), Gagata melanopterus Roberts & Ferraris, 1998, Gagata sexualis Tilak, 1970, Galago moholi A.Smith, 1836, Galaxias anomalus Stokell, 1959, Galaxias argenteus (Gmelin, 1789), Galaxias auratus Johnston, 1883, Galaxias brevipinnis Günther, 1866, Galaxias cobitinis McDowall & Waters, 2002, Galaxias depressiceps McDowall & Wallis, 1996, Galaxias divergens Stokell, 1959, Galaxias eldoni McDowall, 1997, Galaxias fasciatus Gray, 1842, Galaxias fontanus Fulton, 1978, Galaxias globiceps Eigenmann, 1928, Galaxias gollumoides McDowall & Chadderton, 1999, Galaxias gracilis McDowall, 1967, Galaxias johnstoni Scott, 1936, Galaxias maculatus (Jenyns, 1842), Galaxias neocaledonicus Weber & de Beaufort, 1913, Galaxias niger Andrews, 1985, Galaxias occidentalis Ogilby, 1899, Galaxias olidus Günther, 1866, Galaxias parvus Frankenberg, 1968, Galaxias paucispondylus Stokell, 1938, Galaxias pedderensis Frankenberg, 1968, Galaxias platei Steindachner, 1898, Galaxias postvectis Clarke, 1899, Galaxias prognathus Stokell, 1940, Galaxias pullus McDowall, 1997, Galaxias rostratus Klunzinger, 1872, Galaxias tanycephalus Fulton, 1978, Galaxias truttaceus Valenciennes, 1846, Galaxias vulgaris Stokell, 1949, Galaxias zebratus (Castelnau, 1861), Galaxiella munda McDowall, 1978, Galaxiella nigrostriata (Shipway, 1953), Galaxiella pusilla (Mack, 1936), Galeichthys feliceps Valenciennes, 1840, Galeichthys peruvianus Lütken, 1874, Galeocerdo cuvier (Péron & Lesueur, 1822), Galeocharax gulo (Cope, 1870), Galeocharax humeralis (Valenciennes, 1834), Galeocharax knerii (Steindachner, 1879), Galeoides decadactylus (Bloch, 1795), Galictis cuja (Molina, 1782), Galictis vittata (Schreber, 1776), Galidia elegans I.Geoffroy Saint-Hilaire, 1837, Gallicolumba luzonica (Scopoli, 1786), Gallinula chloropus (Linnaeus, 1758), Gallirallus owstoni (Rothschild, 1895), Gallus gallus (Linnaeus, 1758), Gallus lafayetii Lesson, 1831, Gallus lafayetii Lesson, 1831, Gallus varius (Shaw, 1798), Gambelia wislizenii (Baird & Girard, 1852), Gambusia alvarezi Hubbs & Springer, 1957, Gambusia amistadensis Peden, 1973, Gambusia aurata Miller & Minckley, 1970, Gambusia clarkhubbsi Garrett & Edwards, 2003, Gambusia dominicensis Regan, 1913, Gambusia echeagarayi (Álvarez, 1952), Gambusia eurystoma Miller, 1975, Gambusia gaigei Hubbs, 1929, Gambusia georgei Hubbs & Peden, 1969, Gambusia heterochir Hubbs, 1957, Gambusia hispaniolae Fink, 1971, Gambusia hurtadoi Hubbs & Springer, 1957, Gambusia krumholzi Minckley, 1963, Gambusia lemaitrei Fowler, 1950, Gambusia longispinis Minckley, 1962, Gambusia luma Rosen & Bailey, 1963, Gambusia marshi Minckley & Craddock, 1962, Gambusia nicaraguensis Günther, 1866, Gambusia panuco Hubbs, 1926, Gambusia pseudopunctata Rivas, 1969, Gambusia punctata Poey, 1854, Gambusia puncticulata Poey, 1854, Gambusia rachowi (Regan, 1914), Gambusia regani Hubbs, 1926, Gambusia rhizophorae Rivas, 1969, Gambusia senilis Girard, 1859, Gambusia sexradiata Hubbs, 1936, Gambusia speciosa Girard, 1859, Gambusia vittata Hubbs, 1926, Gambusia wrayi Regan, 1913, Gambusia xanthosoma Greenfield, 1983, Gambusia yucatana Regan, 1914, Garmanella pulchra Hubbs, 1936, Garra annandalei Hora, 1921, Garra barreimiae Fowler & Steinitz, 1956, Garra bicornuta Narayan Rao, 1920, Garra borneensis (Vaillant, 1902), Garra bourreti (Pellegrin, 1928), Garra buettikeri Krupp, 1983, Garra cambodgiensis (Tirant, 1883), Garra ceylonensis Bleeker, 1863, Garra congoensis Poll, 1959, Garra cyrano Kottelat, 2000, Garra dembeensis (Rüppell, 1835), Garra dunsirei Banister, 1987, Garra fasciacauda Fowler, 1937, Garra flavatra Kullander & Fang, 2004, Garra fuliginosa Fowler, 1934, Garra ghorensis Krupp, 1982, Garra gotyla (Gray, 1830), Garra gracilis (Pellegrin & Chevey, 1936), Garra gravelyi (Annandale, 1919), Garra hughi Silas, 1955, Garra ignestii (Gianferrari, 1925), Garra imberbis (Vinciguerra, 1890), Garra kalakadensis Rema Devi, 1993, Garra kempi Hora, 1921, Garra laichowensis Mai, Garra lamta (Hamilton, 1822), Garra lissorhynchus (McClelland, 1842), Garra litanensis Vishwanath, 1993, Garra makiensis (Boulenger, 1904), Garra mcclellandi (Jerdon, 1849), Garra mullya (Sykes, 1839), Garra nasuta (McClelland, 1838), Garra notata (Blyth, 1860), Garra orientalis Nichols, 1925, Garra ornata (Nichols & Griscom, 1917), Garra persica Berg, 1914, Garra poecilura Kullander & Fang, 2004, Garra poilanei Petit & Tchang, 1933, Garra qiaojiensis Wu & Yao, 1977, Garra quadrimaculata (Rüppell, 1835), Garra rossica (Nikolskii, 1900), Garra rufa (Heckel, 1843), Garra sahilia Krupp, 1983, Garra salweenica Hora & Mukerji, 1934, Garra spilota Kullander & Fang, 2004, Garra tengchongensis Zhang & Chen, 2002, Garra theunensis Kottelat, 1998, Garra variabilis (Heckel, 1843), Garra vittatula Kullander & Fang, 2004, Garra waterloti (Pellegrin, 1935), Garrulax canorus (Linnaeus, 1758), Garrulax chinensis (Scopoli, 1786), Garrulax leucolophus (Hardwicke, 1816), Garrulus glandarius (Linnaeus, 1758), Gasteropelecus levis (Eigenmann, 1909), Gasteropelecus maculatus Steindachner, 1879, Gasteropelecus sternicla (Linnaeus, 1758), Gasterosteus wheatlandi Putnam, 1867, Gastromyzon borneensis Günther, 1874, Gastromyzon ctenocephalus Roberts, 1982, Gastromyzon danumensis Chin & Inger, 1989, Gastromyzon punctulatus Inger & Chin, 1961, Gastrophryne carolinensis (Holbrook, 1835), Gastrotheca marsupiata (Duméril & Bibron, 1841), Gastrotheca monticola Barbour & Noble, 1920, Gastrotheca peruana (Boulenger, 1900), Gavia pacifica (Lawrence, 1858), Gavialis gangeticus (Gmelin, 1789), Geckolepis maculata Peters, 1880, Geckolepis polylepis Boettger, 1893, Geckolepis typica Grandidier, 1867, Gehyra baliola (Duméril, 1851), Gehyra fehlmanni (Taylor, 1962), Gehyra marginata Boulenger, 1887, Gehyra mutilata (Wiegmann, 1834), Gehyra oceanica (Lesson, 1830), Gehyra vorax Girard, 1858, Gekko badenii Szczerbak & Nekrasova, 1994, Gekko gecko (Linnaeus, 1758), Gekko grossmanni Günther, 1994, Gekko hokouensis Pope, 1928, Gekko japonicus (Schlegel, 1836), Gekko monarchus (Schlegel, 1836), Gekko petricolus Taylor, 1962, Gekko siamensis Grossmann & Ulber, 1990, Gekko smithii Gray, 1842, Gekko vittatus Houttuyn, 1782, Gelanoglanis nanonocticolus Soares-Porto, Walsh, Nico & Netto, 1999, Genetta genetta (Linnaeus, 1758), Genetta tigrina (Schreber, 1776), Genicanthus bellus Randall, 1975, Genicanthus caudovittatus (Günther, 1860), Genicanthus lamarck (Lacepède, 1802), Genicanthus melanospilos (Bleeker, 1857), Genicanthus semifasciatus (Kamohara, 1934), Genicanthus watanabei (Yasuda & Tominaga, 1970), Genidens genidens (Cuvier, 1829), Genycharax tarpon Eigenmann, 1912, Genyochromis mento Trewavas, 1935, Genyomyrus donnyi Boulenger, 1898, Geochelone elegans (Schoepff, 1795), Geoclemys hamiltonii (Gray, 1831), Geococcyx californianus (Lesson, 1829), Geoemyda japonica Fan, 1931, Geoemyda spengleri (Gmelin, 1789), Geopelia cuneata (Latham, 1801), Geophagus abalios López-Fernández & Taphorn, 2004, Geophagus argyrostictus Kullander, 1991, Geophagus brachybranchus Kullander & Nijssen, 1989, Geophagus brasiliensis (Quoy & Gaimard, 1824), Geophagus brokopondo Kullander & Nijssen, 1989, Geophagus camopiensis Pellegrin, 1903, Geophagus crassilabris Steindachner, 1876, Geophagus dicrozoster López-Fernández & Taphorn, 2004, Geophagus grammepareius Kullander & Taphorn, 1992, Geophagus harreri Gosse, 1976, Geophagus iporangensis Haseman, 1911, Geophagus itapicuruensis Haseman, 1911, Geophagus megasema Heckel, 1840, Geophagus obscurus (Castelnau, 1855), Geophagus pellegrini Regan, 1912, Geophagus proximus (Castelnau, 1855), Geophagus steindachneri Eigenmann & Hildebrand, 1922, Geophagus taeniopareius Kullander & Royero, 1992, Geophagus winemilleri López-Fernández & Taphorn, 2004, Geospiza fuliginosa Gould, 1837, Geotrygon montana (Linnaeus, 1758), Geotrygon versicolor (Lafresnaye, 1846), Geotrypetes seraphini (Duméril, 1859), Gephyrocharax atracaudatus (Meek & Hildebrand, 1912), Gephyrocharax caucanus Eigenmann, 1912, Gephyrocharax chaparae Fowler, 1940, Gephyrocharax chocoensis Eigenmann, 1912, Gephyrocharax intermedius Meek & Hildebrand, 1916, Gephyrocharax major Myers, 1929, Gephyrocharax melanocheir Eigenmann, 1912, Gephyrocharax sinuensis Dahl, 1964, Gephyrocharax valencia Eigenmann, 1920, Gephyrocharax venezuelae Schultz, 1944, Gephyrochromis lawsi Fryer, 1957, Geranoaetus melanoleucus (Vieillot, 1819), Gerbillus gerbillus (Olivier, 1800), Geronticus calvus (Boddaert, 1783), Gibelion catla (Hamilton, 1822), Gila brevicauda Norris, Fischer & Minckley, 2003, Gila coerulea (Girard, 1856), Gila conspersa Garman, 1881, Gila cypha Miller, 1946, Gila ditaenia Miller, 1945, Gila elegans Baird & Girard, 1853, Gila eremica DeMarais, 1991, Gila intermedia (Girard, 1856), Gila minacae Meek, 1902, Gila modesta (Garman, 1881), Gila nigra Cope, 1875, Gila nigrescens (Girard, 1856), Gila pulchra (Girard, 1856), Gila purpurea (Girard, 1856), Gila robusta Baird & Girard, 1853, Gila seminuda Cope & Yarrow, 1875, Gilbertolus alatus (Steindachner, 1878), Gilbertolus atratoensis Schultz, 1943, Gilbertolus maracaiboensis Schultz, 1943, Ginglymostoma cirratum (Bonnaterre, 1788), Ginsburgellus novemlineatus (Fowler, 1950), Giraffa camelopardalis (Linnaeus, 1758), Girardinichthys mult
Keywords: GBIF; biodiversity; species occurrences